Sulodexide protects against sepsis-induced liver injury in neonatal rat by attenuating oxidative stress, apoptosis, and NF-κB/MAPK signaling - Wei Lu; Kang Fu; Xinming Zhang; Pedro Antonio Valdes-Sosa; Jun Wang; Fuzhong Xing (Molecular Biology Reports, 2026)

Metabolic reprogramming of immune cells in the battle against intracellular bacterial chronic infections: novel mechanisms and breakthroughs - Rongrong Jiang; Xiao Liu; Fangtao Xing; Yurong Fu; Zhengjun Yi (Molecular Biology Reports, 2026)

An efficient lumped mass model for seismic response analysis of triple-layer seismic isolation super high-rise structures - Yuan Zhang; Qi Luo; Liulei Lu; Qionglin Fu; Dewen Liu; Junfeng Wang; Feng Xing (Soil Dynamics and Earthquake Engineering, 2026)

Chitinase-primed ultrasound enhances Saccharomyces cerevisiae cell-wall deconstruction and yeast-protein remodelling in two complementary model systems - Talha Riaz; Xianjiang Ye; Te Yu; Zhijun Xia; Muhammad Moeid Khan; Xuan Yao; Rabiya Riaz; Sadia Ansar; Zhou Chen; Muhammad Atiq Ashraf; Chuanyan Pan; Yongguo Jin; et al. (Food Research International, 2026)

Assessing present-day tectonic stability, sea-level change, and tsunami hazards from a coastal multi-hazard GNSS station in the southern South China Sea - Qiang Qiu; Linlin Li; Mai Ye; Hongqiang Yang; Xingyu Song; Jian Ping Yin; Tingting Zheng; Jinghe Cao; Peitao Wang; Zhanying Chen; Zhiwen Zhang; Kuilin Xiao; et al. (Engineering Geology, 2026)

Integrating human perceptions into ecological restoration: Analyzing the mismatches and barriers between ecological components, ecosystem services, and human perceptions in riparian green spaces - Ce Wen; Fan Yang; Xing Zhang; Hongda Fang; Yuanpeng Fu; Xuxi Zhou; Changzhou Yan (Ecological Engineering, 2026)

A burned-skin-inspired Janus membrane for efficient and antifouling solar evaporation - Aoxiang Zhang; Huiying Zhou; Yuhang Li; Xing Gao; Xiaotong Lu; Yu Fu (Desalination, 2026)

Decadal gelatinization and phenological advancement of small jellyfish in Laizhou Bay, Bohai Sea - Ping Fu; Shan Sun; Huichao Jiang; Jianlong He; Ling Cheng; Bo Su; Hongyan Xing; Yuanqing Ma; Lijuan Liu; Yuting Zhao; Juan Zhang; Xiaowen Zhang (Marine Pollution Bulletin, 2026)

Three 9-amino-1,10-anthracenedione derivatives with anti-MRSA/VRE activity from Fusarium sp. - fermented Cassia obtusifolia seeds - Zhi-Da Jin; Dai-Hua Fu; Guang-Sen Mou; Yi-Nong Wang; Xiao-Dong Luo; Hao Zhou; Shu-Kun Tang; Li-Xing Zhao (Phytochemistry, 2026)

Efficient dye decolorization via synergistic degradation and adsorption by MnSiBAl metallic glass - Lansong Yang; Junlei Shi; Chen Yang; Shixin Tan; Peixin Fu; Shun-Xing Liang; Yuanzheng Yang (Journal of Environmental Chemical Engineering, 2026)

Preparation and performance analysis of a novel composite dust suppressant considering wind and train vibration effects - Hao-kui Wang; Ming-yi Chen; Zi-ting Pei; Fu-chao Tian; Yue Ren; Xing-jun Ma; Ming-xin Li (Journal of Environmental Chemical Engineering, 2026)

The bioavailability trap: Shewanella putrefaciens induces false-positive remediation signals via metabolic state-dependent bioemulsification and biosorption - Chao Yang; Enlu Xing; Jintao Fu; Zhongyuan Li; Feng Zhang; Rongbing Fu (Journal of Environmental Chemical Engineering, 2026)

Biodegradable lead-free piezoelectric nanofibrous scaffold enables motion-activated meniscal tear repair - Xiaolong Yang; Xing Huang; Yulai Zhang; Yi Zhou; Zhe Xu; Yi Zhang; Laiming Jiang; Weili Fu; Jiagang Wu (Chemical Engineering Journal, 2026)

Lignin carbon dots with engineered graphitic N and sp2 domains: Visible-light-driven oxidase-like activity and green fluorescence for smartphone-assisted dual-mode nitrite detection - Pengyu Hu; Longwen Lei; Chenglong Fu; Yi Wang; Haiming Li; Xing Wang; Zhiwei Wang; Lan Yao; Yanzhu Guo (Chemical Engineering Journal, 2026)

Metabolic division of labor drives synergistic production of biomass, lipid and α-tocopherol in Euglena gracilis–Chlorella pyrenoidosa co-cultures - Zhen Wang; Qisheng Tian; Liling Fu; Xiaofan Xing; Wei Liu; Changhong Liu; Lei Zheng (Bioresource Technology, 2026)

Unveiling the pathogenesis and therapeutic strategies of Alzheimer’s disease through cuproptosis - Shuangfeng Xu; Jing Mu; Zhifeng Wang; Jiao Yang; Daman Tian; Ting Shi; Junfeng Lan; Pengfen He; Zhihui Hao; Youchuan Fu; Liwei Xing; Jianzhou Ye; et al. (BioMetals, 2026)

Microscopic deformation mechanism of clay aggregates in view of the montmorillonite particles rearrangements under cyclic loading-unloading conditions - Zi-Yu Ding; Kai-Wen Tong; Yong-Gui Chen; Qiong Wang; Wen-Jie Dai; Xing-Guang Zhao; Chang-Fu Wei; Zhi-Jun Zhang (Applied Clay Science, 2026)

Quantifying responses of concurrent PM2.5-O3 pollution to their precursors in the Yangtze River Delta megacity Cluster of China - Mingliang Ma; Mengjiao Liu; Mengnan Liu; Yihong Jiao; Fei Meng; Pingjie Fu; Jingxue Bi; Tongshuai Rong; Yangyang Liu; Yuqiang Wang; Huaqiao Xing (Environment, Development and Sustainability, 2026)

Legacy-to-Alternative Shift of Brominated Flame Retardants in the East China Sea Revealed by Multimedia Observations and Coupled Modeling - Jie Fu; Xing Liu; Gu Tao; Haibo Zhang; Ye Kong; Zhen He; Chun-Ying Liu; Dong-Liang Lu; Gui-Peng Yang (Water Research, 2026)

A Transformer-Mamba framework for cross-regional long-term forecasting of key water quality in aquaculture - Ying Li; Huanhai Yang; Haoran Xing; Lingyu Fu; Ningrui Gu; Shue Liu; Dashe Li (Water Research, 2026)

Algal blooms drive plasmid-mediated ARG conjugation in eutrophic lakes: Mechanistic insights from field mobilome to molecular regulation - Chao-Nan Wang; Er-Xue Gu; Xing-Yan Xue; Cun-Lu Li; Dong-Feng Liu; Fu-Liu Xu (Water Research, 2026)

Growth-mode-independent glutamine/glutamate/aspartate metabolic shift and urea cycle remodeling driven by FOXA1 in benzo[a]pyrene-transformed human bronchial epithelial cells - Yujin Fu; Yanmin Qi; Yunkun Xing; Yitong Lin; Zhiyu Liu; Juanling Fu; Biyun Yao; Peng Zhao (Toxicology and Applied Pharmacology, 2026)

Nanoplastics shift arbuscular mycorrhizal fungal mediation of bacterial community assembly from diversity to compositional stability under arsenic stress - Song Liu; Xuemin Jing; Yan Wang; Maolin He; Xuan Chen; Xueli Wang; Jingwen Zhang; Qin Zeng; Xing Fan; Wei Fu; Baodong Chen; Xin Zhang; et al. (Journal of Hazardous Materials, 2026)

The Micro-battlefield under climate change: the domino effect of freeze-thaw cycles on Tributyl phosphate accumulation in grains via nutritional, metabolomic, and microbial profiling - Jinke Hu; Ningning Xing; Guozhang Bao; Wenjie Ma; Qinan Ban; Yujia Mou; Jinyi Wang; Zimin Fu (Food Research International, 2026)

Quantifying the impact of vegetation changes on runoff in alpine basins using the Budyko framework integrating glacier effect - Zehui Zhou; Weidong Huang; Jiaxin Jin; Lei Yu; Wanqiu Xing; Jianyu Fu; Dianchen Sun; Bin Yong (Environmental Research, 2026)

Rapid and multimodal responsive composite hydrogel actuator with enhanced mechanical performance and reprogrammability for complex application scenarios in soft robotics - Zhilin Zhang; Xingchen Cui; Xing Gao; Xu Zhai; Zijing Huang; Jianwei Sun; Yi Tang; Yan Wang; Yu Fu; Tieqiang Wang (Chemical Engineering Journal, 2026)

Effects of soil nematode communities and micro-food web energy flux on ecosystem multifunctionality under 12-year field nitrogen addition in a boreal forest - Gang Fu; Guancheng Liu; Ligong Wang; Yuguo Gao; Zhicheng Yao; Yajuan Xing; Qinggui Wang (Applied Soil Ecology, 2026)

Satellite evidence shows global vegetation resilience undergoing unexpected abrupt changes - Hui Chen; Xing Li; Wei He; Songhan Wang; Zheng Fu; Xiuzhi Chen (Agricultural and Forest Meteorology, 2026)

Novel Hepatopancreas-Predominant C-Type Lectin (LvCTL) Contributes to Resistance Against Vibrio parahaemolyticus in Shrimp Litopenaeus vannamei - Ning Fu; Mengxin Xing; Yuyu Wang; Linwei Yang; Di Wang; Taolin Fan; Bang Xiao; Shengwen Niu (Fishes, 2026)
C-type lectins (CTLs) are important pattern recognition receptors (PRRs) involved in innate immune defense in crustaceans. In this study, a novel C-type lectin, designated LvCTL, was identified and functionally characterized from Litopenaeus vannamei. Sequence analysis revealed that the open reading frame (ORF) of LvCTL is 495 bp in length and encodes a 164-amino acid polypeptide containing a typical C-type lectin-like domain but lacking the classical carbohydrate-binding motifs. Notably, two novel EPF motifs were identified in the CTLD region, suggesting a potential non-canonical ligand recognition pattern. Phylogenetic analysis revealed that LvCTL clustered with other crustacean CTLs. Tissue expression analysis revealed that LvCTL exhibited the highest transcript level in the hepatopancreas. After immune stimulation, LvCTL expression in the hepatopancreas was significantly regulated by LPS, Vibrio parahaemolyticus, Staphylococcus aureus, WSSV and Poly(I: C), indicating its involvement in antimicrobial immune responses. RNA interference assays showed that knockdown of LvCTL significantly increased the bacterial burden and reduced the survival rate of shrimp after V. parahaemolyticus infection. Furthermore, recombinant LvCTL displayed broad bacterial binding activity to Gram-negative and Gram-positive bacteria and induced calcium-dependent agglutination of V. parahaemolyticus and S. aureus. Taken together, these results demonstrate that LvCTL functions as an important immune recognition molecule and contributes to antibacterial defense against V. parahaemolyticus in L. vannamei. These findings broaden our understanding of the functional diversity of shrimp CTLs and their contributions to crustacean innate immunity.

Retraction notice to “Recent progresses, challenges, and opportunities of carbon-based materials applied in heavy metal polluted soil remediation” [Sci. Total Environ. 856 (2023) 158810] - Tianhong Fu; Baige Zhang; Xing Gao; Shihao Cui; Chung-Yu Guan; Yujin Zhang; Bangxi Zhang; Yutao Peng (Science of The Total Environment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Discovery of isotope 153Hf near the proton drip line via isochronous mass spectrometry: extending the nuclear landscape with HIAF - Hongfu Li; Min Zhang; Hongyang Jiao; Xing Xu; Chaoyi Fu; Jinyang Shi; Jiahao Lv; Xu Zhou; Yuanming Xing; Mingze Sun; Yuhu Zhang; Xiaohong Zhou; et al. (Science Bulletin, 2026)

Arbuscular mycorrhizal symbiosis decouples arsenic risk from saponin biosynthesis in Panax notoginseng (Araliaceae) by reprogramming rhizosphere and root processes - Xing-Kai Zhang; Xian-Nv Long; Shu-Shuang Tang; Tai-Xiong Zheng; Di Chen; Fu-Gang Wei; Yan-Lin Wang; Yue Wu; Kai Dai; Guan-Hua Cao; Sen He (Journal of Hazardous Materials, 2026)

Constructing Fe3N/MnO heterojunction via heteroatom doping for degrading dye wastewater by heterogeneous electro-fenton system - Yi Wang; Yunliang Fan; Xiaocong Liu; Fuping Zhang; Hangdao Qin; Bo Xing; Xingyong Liu; Chaoting Fu; Yan Luo; Guo Yang; Ning Gou (Journal of Environmental Sciences, 2026)

Quantitative visualization of stress wave propagation and dynamic wave–interface coupling in faulted rock tunnels using 3D-printed photoelasticity - Yang Ju; Guoming Fu; Changbing Wan; Bofan Dai; Dongyi Xing (International Journal of Rock Mechanics and Mining Sciences, 2026)

Rational design of Core-Shell ZSM-5@Beta zeolite for selective production of C8–C15 aromatics toward sustainable aviation fuel precursors - Zihang Wang; Xing Zhang; Yujing Wu; Jinliang Yan; Zhiyu Li; Peng Fu (Fuel, 2026)

Interactive effect between different growth duration variety and cutting height on grain yield and quality in ratoon rice - Jinjuan Zhu; Qimeng Lan; Xinchen Zhang; Hongshun Xiang; Yifan Fu; Huiping Wang; Changzai Zhou; Chen Yang; Guodong Yang; Xing Yu; Chang Zheng; Shen Yuan; et al. (Field Crops Research, 2026)

LNP-mRNA-engineered fibroblasts delivering TNF-α antibodies alleviate intervertebral disc degeneration by modulating the inflammatory microenvironment - Jianan Chen; Tong Xing; Jialei Song; Hang Zhang; Shaotian Fu; Lizhi Jiang; Yiqi Xu; Lei He; Huatao Liu; Hailong Ma; Xin Wang; Tangjun Zhou; et al. (Chemical Engineering Journal, 2026)

Mechanistic insights into nitrogen-doping-assisted biomass-derived graphitization carbon catalyzed by iron nitrate - Guangda Fu; Zhengshuai Sun; Baojun Yi; Jiaqi Deng; Xing Wu; Dongyi Kong (Biomass and Bioenergy, 2026)

17β-estradiol reshapes the reproductive dose–response to polystyrene nanoplastics in the rotifer Brachionus calyciflorus - Qi-bin Zhu; Yi-fan Feng; Yi-fu Xing; Yu Zhang; Jiang-hua Yang; Cui Han; Xiao-jie Liu; Jia-xin Yang (Aquatic Toxicology, 2026)

Activation-induced cytidine deaminase (AID) suppresses the activity of HBV EnhII/CP by downregulating FANCE expression - Weiping Zhou; Biao Yang; Ye Sun; Yuxin Bai; Xuanhe Fu; Bing Nie; Ying Li; Xing Tian; Zhongjia Jiang; Guangyan Liu (Virus Genes, 2026)

Identification and Motion Trajectory Analysis of High-Position Dangerous Rock Mass in the Lanhuazhai Collapse Triggered by the 2022 Luding Ms 6.8 Earthquake - Jingyu Kang; Xiaodong Fu; Kai Wu; Qian Sheng; Xing Wang; Miao Liang; Shuai Huang (Journal of Earth Science, 2026)

Gray Anchoring: A New Computational Theory for Biological Color Constancy - Kai-Fu Yang; Dajun Xing; Yong-Jie Li (Neuroscience Bulletin, 2026)

Chemical composition of the endogenous fungus Fusarium sp. L-3 derived from Chinese Qinan agarwood - Ming-Li Han; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Na Xiao; You-Xing Zhao (Natural Product Research, 2026)

A new species and a newly recorded species of the genus Hua (Gastropoda: Semisulcospiridae) from the Chishui River, Yunnan, China - Jian-Fu Wei; Yuan-Chao Chen; Xue-Hua Li; Guang-Can Zhou; Qi-Yan Zhu; Ting-Song Yu; Jun-Xing Yang; Xiao-Ai Wang (Molluscan Research, 2026)

Climate warming and sulfide exposure jointly disrupt intestinal microbiota and barrier homeostasis in the freshwater crab Eriocheir sinensis - Yi-fu Xing; Jian Tian; Xuan-yi Zhu; Yi-fan Feng; Qi-bin Zhu; Long-long Fu; Jia-xin Yang (Aquaculture, 2026)

Soil microbial communities and reactive oxygen species reshape MAOC-driven PAH accumulation under seasonal trade-offs between forest filtering and cold trapping - Weijie Liu; Xinli Xing; Ying Liu; Andrew J. Sweetman; Kevin C. Jones; Shizhen Zhao; Yanqi Ma; Yichen Lu; Qinglong Fu; Tianpeng Hu; Jiaquan Zhang; Shihua Qi (Journal of Hazardous Materials, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Grazing season overrides intensity in driving plant subordinate species-mediated community dynamics across contrasting elevations of typical steppe - Yu-Wen Zhang; Lan Li; Zhao-Xia Guo; Zhao-Ling Da; Wen-Jun Wang; Xing-Qi Wang; Fu-Jiang Hou; Ji-Zhou Ren (Global and Planetary Change, 2026)

Transglutaminase-induced crosslinking of soy protein isolate in crowded environments: effects of dextran concentration and molecular weight - Kaiyun Luo; Siqi Fu; Yunhao Xing; Xiaohong He; Maolong Chen; Zhou Xu; Ye Jiao; Yunhui Cheng; Xufeng Wang (Food Chemistry, 2026)

Symmetry-mismatch-guided topological evolution in pore-space-partitioned metal-organic frameworks for enhanced ethylene purification - Zhang-Lei Zhong; Chen-Chen Xing; Yan-Yu Zhang; Ai-Ming Zhang; Le-Wei Zheng; Yu Wang; Wenyu Yuan; Ying Wang; Shun-Fu Du; Quan-Guo Zhai (Chemical Engineering Journal, 2026)

Molecular attribute-driven hybrid SEI engineering for durable silicon anodes - Yijie Lin; Yingkang Deng; Yuling Fu; Mingjun Ma; Haolei Chen; Xinqi Chen; Shuhan Chen; Jiarong He; Lidan Xing; Weishan Li (Chemical Engineering Journal, 2026)

A secreted alpha-amylase effectively induces reproductive cyst formation both within and across Colpoda species, key soil-dwelling protists - Zixin Cheng; Zhongqiao Song; Kejia Fu; Yuan Wang; Kai Chen; Jing Zhang; Che Hu; Xiaocui Chai; Shuai Luo; Fang Zhou; Yuan Xiao; Zhenfei Xing; et al. (Science China Life Sciences, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Targeted gene delivery in cyprinid fish oocytes mediated by VtgN: A strategy for fish genetic manipulation - Jing Huang; Yunpeng Fan; Mingui Jiang; Xing Guo; Guangjing Zhang; Kaiyue Zhao; Hanqi Xiao; Liangyue Peng; Wen Fu; Jinhui Liu; Wenbin Liu; Yamei Xiao (Aquaculture, 2026)

Lysozyme as a protein-based carrier for bioactives: advances in delivery systems and gut environment interactions - Te Yu; Yuzhong Zheng; Yongping Huang; Yuan Ma; Grażyna Neunert; Jie Cao; Xing Fu (Trends in Food Science & Technology, 2026)

Polystyrene nanoplastics disrupt iron homeostasis by promoting FPN1 ubiquitination in GC-2spd(ts) cells - Xinru Cui; Yitong Shang; Liyang Ding; Zhen Zhang; Yu Deng; Tengjiao He; Bo Xu; Xufeng Fu; Xing Du; Hang Han (Toxicology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Regulation of root microbiota: A strategic mechanism for sustaining rice yield stability under salt stress - Qianyu Wu; Fan Wang; Fu Yang; Xing Wang; Daoshun Zhang; Haisheng Wang; Rongfeng Huang; Juan Wang; Xiaoxia Zhang (Rhizosphere, 2026)

Identification of pennogenin synthases in Paris polyphylla reveals enzyme plasticity underlying paralog evolution - Shuyu Li; Jingjing Liao; Jingjing Zhang; Chunjin Fu; Haining Lyu; Yuxiang Huang; Zhangrui Tang; Xinwei Zhang; Yuyang Liu; Xin Chai; Jiale Xing; Xin Zhao; et al. (Molecular Plant, 2026)

The EAR-motif-containing adaptor protein ECAP enhances the assembly of PYR1–ABI1 complex to promote ABA signaling in Arabidopsis - Xing Li; Changjiang Li; Gaofeng Lv; Lei Shi; Shulong Tan; Xi Li; Kaixi Liu; Anxing Li; Lei Zhu; Guanghui Yang; Jigang Li; Ying Fu (Molecular Plant, 2026)

Decoupled synergistic control of airborne infection risk and thermal comfort in open layout dental clinics: Integration of indoor airflow pattern, physical barrier, and air purifier - Jingwen Chen; Xinchao Fu; Shuhui Fei; Xing Li; Zhuangbo Feng (Journal of Hazardous Materials, 2026)

Dual-network synergistic lignin-based polyurethane elastomers with high strength, toughness, and broad-temperature-range damping - Debiao Fu; Xing Su; Shenglin Wei; Jialu Shang; Xiaodong Li; Jin Xu; Tianhao Wu; Wei Zhang; Hao Jiang; Dichang Xue; Lu Jin; Kai Liu; et al. (Chemical Engineering Journal, 2026)

Dependence of Runoff Simulation on Selection of Precipitation Products and Calibration Strategies: A Case Study in the Ganjiang River Basin - Xiaolei Jiang; Jing Shen; Fengchun Luo; Luofujie Guo; Xing Xu; Qin Ju; Huanghe Gu; Xiaolei Fu (Journal of Meteorological Research, 2026)

Advances, opportunities, and challenges in microbial community construction: from environmental remediation to biomanufacturing - Mengxue Li; Xiang Xing; Kangqing Fei; Zhenni Cheng; Jiayu Zhang; Rongbo Guo; Xiaokui Zhang; Shanfei Fu; Xiaolei Fan (Archives of Microbiology, 2026)

Assessment of Spirulina Residue Meal as a Substitute for Fish Meal in Juvenile Rainbow Trout (Oncorhynchus mykiss) Diets: Impact on Growth, Antioxidative Capacity, Carcass Composition and Hepatointestinal Health - Ning Fu; Yuyu Wang; Shengwen Niu; Mengxin Xing; Meiling An; Lu Zhao; Gefeng Xu; Hairui Yu; Jiubo Cui (Fishes, 2026)
A 7-week study was conducted to investigate the effects of replacing fish meal (FM) with Spirulina residue meal (SPRM) on the growth, feed utilization, carcass composition, antioxidant ability, liver and intestinal histology of juvenile rainbow trout (Oncorhynchus mykiss) (initial body weight 5.36 ± 0.04 g). Four isonitrogenous (42%) and isolipidic (16%) diets were formulated to replace FM protein with SPRM at 0 (SPRM0), 10% (SPRM10), 20% (SPRM20) and 30% (SPRM30), respectively. Results showed that growth, feed utilization, carcass amino acid profile, serum biochemical indices, antioxidant ability, intestinal and liver histology were not significantly affected by dietary SPRM levels. Whole-body lipid content decreased as dietary SPRM replacement levels increased, and fish fed diet SPRM30 had lower lipid content than that fish fed diet SPRM0 (p 0.05). The muscle C22:6n-3 (DHA) content decreased, but C18:3n-6 and n-6/n-3 polyunsaturated fatty acid (PUFA) ratio increased with increasing SPRM levels, and fish fed diet SPRM30 had significantly lower DHA content and higher n-6/n-3 ratio than the group fed SPRM0 (p 0.05), but higher than the SPRM10 and SPRM20 groups (p

Toxicological effects of polypropylene nanoparticles similar in size to nanoplastics in plastic-bottled injections on mice and zebrafish - Hui-Min Sun; Jie Wang; Xian-Fu Wu; Zhong-Lan Chen; Hui-Ying Yang; Zhi Lin; Shuang-Xing Li; Zhe Qu; Hua Chen; Shang-Chen Yao (Science of The Total Environment, 2026)

Analysis of different fermentation processes of jujube-hawthorn fermented beverage based on untargeted metabolomics and GC–MS - Zhibin Xing; Yueyao Li; Hao Huang; Hexi Yuan; Xiaoqiang Zhang; Xinrui Liu; Chunhui Shan; Xizhe Fu; Yinglin Du (Food Research International, 2026)

Processing sequence as a design lever: pectin pre-complexation enhances ultrasound-driven interfacial loading, functionality, and volatile profile of yeast protein - Talha Riaz; Yuan Ma; Zhijun Xia; Muhammad Moeid Khan; Xianjiang Ye; Muhammad Atiq Ashraf; Rabiya Riaz; Xing Fu; Yongguo Jin (Food Research International, 2026)

Comparison between direct-seeded and transplanted ratoon rice in grain yield and nitrogen use efficiency - Hongshun Xiang; Jiaqi Yin; Yifan Fu; Guodong Yang; Jinjuan Zhu; Changzai Zhou; Huiping Wang; Xinchen Zhang; Xing Yu; Shen Yuan; Jianliang Huang; Dongliang Xiong; et al. (Field Crops Research, 2026)

Emissions of nitrogen oxide from household gaseous cooking - Yongqiang Zhang; Jian Fu; Tianyao Huang; Jieyang Gao; Hanchen Wang; Ke Jiang; Ran Xing; Guofeng Shen; Shu Tao (Environmental Pollution, 2026)

Nitrogen inhibitors enhance ecosystem multifunctionality through microbial networks in alpine grasslands of the Tibetan Plateau - Fang-Kun Yang; Peng-Yang Wang; Ze-Yang Liu; Fu-Ying Niu; Cheng-Yi Xie; Yi-Ming Gao; Yan-Mei Ma; Yu-Xing Wang; Jia-Cheng Guo; Wen-Ying Wang (Applied Soil Ecology, 2026)

The trojan horse in agricultural water: How microbe-mediated interactions of nanoplastics and flame retardants drive multiscale toxicity and seed transmission in rye - Jinke Hu; Wenglong Hu; Guozhang Bao; Ziming Fu; Yiyang Li; Ningning Xing (Water Research, 2026)

Sustainable valorization of shield tunneling spoil via silane-coupled recycled mask fibers: Interfacial enhancement and engineering performance - Yu-Zhang Bi; Xin-Po Sun; Chun-Ying Wang; Tian-Xing Ma; Xian-Lei Fu; Zhe-Yuan Jiang (Sustainable Chemistry and Pharmacy, 2026)

Two new aromatic meroterpenoids from the fruiting bodies of Ganoderma calidophilum - Wei Liu; Li Yang; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Yan Hua; You-Xing Zhao (Phytochemistry Letters, 2026)

Response of runoff and sediment transport process to climate change in the headwater regions of Yangtze River - Li Wang; Fan Zhang; Xiaonan Shi; Chen Zeng; Yao Chen; Xing Xu; Xudong Fu (Journal of Hydrology, 2026)

Partial substitution of pork lean meat with black soldier fly larvae protein: Enhancing the quality and volatile flavor of low-salt sausages - Yue Tian; Xi Zeng; Yuzhong Zheng; Yongping Huang; Bingyu Wang; Xing Fu (Food Research International, 2026)

Novel stomach-predominant C-type lectin (LvnCTL) triggers immune response against Vibrio parahaemolyticus and WSSV in shrimp Litopenaeus vannamei - Shengwen Niu; Ning Fu; Yuyu Wang; Mengxin Xing; Meiling An; Hongli Xu; Bang Xiao; Weiyan Song; Yongqing Zeng; Orlando Borras-Hidalgo; Hui Wang (Fish & Shellfish Immunology, 2026)

Seasonal temperature rise influences nitrous oxide and methane accumulation in freshwater habitats via distinctive microbial processes - Teng-Fei Ma; Wen-Ke Liu; Chong-Yang Xing; Ya-Song Chen; Hui-Min Fu; Ji-Chun Bai; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Meng-Wen Peng (Environmental Pollution, 2026)

Orchestrating macrophage-tubular crosstalk with antioxidant nanotherapeutics to treat acute kidney injury via metabolic reprogramming - Liya Wang; Zhuyun Zhang; Yajun Fu; Shaoyong Zhuang; Baihai Su; Xing Zhao (Chemical Engineering Journal, 2026)

Electrochemical aptamer sensor based on nanocomposites composite material for rapid on-site detection of enrofloxacin in aquaculture - Bo Long; Qi Liu; Yizhuan Li; Qiongqiong Xing; Chuxiong Lan; Rui You; Liying Deng; Fangfang Qu; Meng An; Yingchun Fu; Shenghang Zhang; Dapeng Ye; et al. (Chemical Engineering Journal, 2026)

Engineering stress tolerance in Saccharomyces cerevisiae by overexpressing PIR3 and SPI1 for efficient ethanol production from high-concentration sugarcane molasses - Wei-Yang Wang; Bei Liao; Ping Zheng; Ming-Yue Huang; Yu-Tuo Wei; Fu-Xing Niu (Bioresource Technology, 2026)

Assessing reactor configuration and bioaugmentation to enhance methane recovery from continuous anaerobic treatment of high-salinity pharmaceutical wastewater - Xing Cai; Chuang Liu; Sida Fu; Wansheng Shi; Zhenxing Huang; Mingxing Zhao (Bioresource Technology, 2026)

A multilevel regression model to explain disparities in residential cooling infrastructure across heat-threatened regions - Yang Yang; Haoying Han; Shuyang Li; Jiayi Fu; Xing Su; Chao Fan (Applied Geography, 2026)

Metabolic Engineering of Selenocysteine Biosynthesis and Insertion Pathway in Lactococcus Lactis - Jing-Jing Peng; Yao Qin; Shi-Yang Yue; Ping Shi; Ling-Yu Wang; Chen-Xing Liu; Yu-Hui Fang; Xiao-Dong Pei; Fu-Tian Yu; Xin-Bi Huang; Xiao-Ling Liu; Cheng-Hua Wang (Biological Trace Element Research, 2026)

PRRSV nucleocapsid and nonstructural proteins dual-regulate CD40 expression via ATF-2 and AP-1 pathways - Chaolun Fu; Hongyan Gao; Yingchao Li; Chang Liu; Yuzhong Zhao; Youbo Li; Zhong Liu; Man Lu; Yang Shen; Yajing Xing; Yu Wang; Xiaotong Wu; et al. (Veterinary Microbiology, 2026)

Multi-satellite derived data reveals spatiotemporal dynamics of carbon-water coupling and its drivers in tropical ecosystems - Xiang Wang; Zheng Fu; Philippe Ciais; Josep Peñuelas; Jingfeng Xiao; Xing Li; Xiangzhong Luo; Chi Chen; Haoyu Xia; Tao Zhou; Paul C. Stoy; Julia K. Green; et al. (Remote Sensing of Environment, 2026)

Research on spontaneous combustion thermal generation and transfer effects of coal–based activated carbon and its precursors - Hui-Fei Lyu; Fu-Xing Shen; Yue Li; Cai-Ping Wang; Jun Deng; Wei-Feng Wang (Process Safety and Environmental Protection, 2026)

A dynamic Bayesian network-based probabilistic analysis method for urban gas pipelines from the perspective of “Accident-Barrier-Resilience” - Fu-qiang Yang; Hai-feng Liu; Shi-yi Li; Xing-lin Chen; Zong-hou Huang (Process Safety and Environmental Protection, 2026)

From resistance to detection: The role of nanomaterials in plant stress responses - Jing-wan Zhang; Rui-Rui Hao; Abolghassem Emamverdian; Wen-Xun Su; Xing-Hao Zhang; Meisam Zargar; Mo-Xian Chen; Fu-Yuan Zhu (Plant Science, 2026)

The plant ontology of cell types - Hongyu Chen; Pu Liang; Xiaolin Lu; Shuai Jiang; Jingjing Jin; Jiaqi Cai; Yaqian Lu; Dihuai Zheng; Jie Yao; Qinjie Chu; Huixia Shou; Chengxin Fu; et al. (Molecular Plant, 2026)

Multi-Feature and Multi-Step Monthly Rainfall Forecasting with the Hybrid VMD-LSTM-CATNet Model in Diverse Climatic Regions - Man-Hong Fan; Xiao-Ying Ma; Shi-Qi Xu; Rui-Lin Fu; Zhong-Xing Tao (Water Resources Management, 2026)

Overexpression of DWARF14-LIKE2 in Arabidopsis thaliana alters multiple traits related to plant morphology and osmotic and salt stress tolerance - Xiaofan Nie; Liangliang Li; Chenbo Zhu; Kaixin Yang; Qingtian Li; Jiahe Fu; Minghui Xing; Mingming Wang; David C. Nelson; Xianzhong Feng; Jiuhai Zhao; Zhengwei Liang; et al. (Plant Cell Reports, 2026)

Two new compounds from Atractylodes japonica Koidz. ex Kitam - Mei Yi; Jing Wang; Jie Sun; Yan Liu; Zhen-Xing Fang; Lei Fu; Yuan-Yuan Zhou (Natural Product Research, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Hydrogeochemical characteristics and controlling factors of groundwater in a typical oasis in arid regions - Xing Wei; Qingmei Zhang; Yulin Zhou; Libo Ran; Delun Chen; Xueting Dou; Yanan Fu; Gang Wu (Acta Geophysica, 2026)

Eliminating Microcystis aeruginosa and secondary pollutants via photo-Fenton process over Iron-MOF - Hong- Yu Chu; Zheng-Xing Liu; Jian-Feng Wang; Xuchun Qiu; Fu-Xue Wang; Shao-Long Chen; Hui-Min Yu; Fei Wang; Guang-Chi Liu; Ruo-Xuan Mei; Xin-Jie Li; Xiao-Hang Xu; et al. (Water Research, 2026)

Crustal structure and tectonic implications of the Southern Central Asian Orogenic Belt: New insights from gravity, magnetic, and magnetotelluric imaging - Chutong Chen; Na Li; Lingxiao Zhang; Hongying An; Chang’an Guo; Xing Fu; Songda Lei; Guicai Yang; Junjie Fan; Weiheng Yuan; Hao Wang; Bin Wang; et al. (Tectonophysics, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Molecular crystal memristor-based edge AI platform for energy-efficient and real-time smart grid inspection - Pengfei Guan; Lanhao Qin; Ke Ning; Jie Liu; Decai Ouyang; Yimeng Yu; Jinsong Wu; Xing Lu; Yingshuang Fu; Yuan Li; Huiqiao Li; Tianyou Zhai (Science Bulletin, 2026)

Two new compounds isolated from a sponge-derived fungus Diaporthe sp. ZYX-Z-582 - Jia-Le Chang; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Hai-Tao Li; Jiao-Cen Guo; Hao-Fu Dai; Sha-Sha Liu; You-Xing Zhao (Phytochemistry Letters, 2026)

Spatial distribution, source identification, and risk assessment of polycyclic aromatic hydrocarbons and their alkylated derivatives in China's coastal zones - Tao Liu; Jie Fu; Xi Liu; Xing Liu; Ziwei Yao (Marine Environmental Research, 2026)

Silica reversal reveals the lithium super-enrichment during the extreme differentiation of granitic magmas - Chun-Li Guo; Roberto F. Weinberg; Fu-Yuan Wu; Jun-Xing Zhao; Xiao-Chi Liu; Bin-Wu Zhang (Lithos, 2026)

Microplastics found in Weddell seal placenta in Antarctica, potential threatening marine ecosystem health - Xing Miao; Conghui Peng; Renxin Zhang; Baohong Chen; Zongzheng Chen; Hui Lin; Tingting Fu; Yuan Li; Longshan Lin (Journal of Hazardous Materials, 2026)

Piezo-augmented peroxymonosulfate activation over Fe-TCPP with ultrasound-propelling ability for water decontamination - Chen Zhao; Yilan Fu; Zhihui Guo; Zixuan Zhao; Xiaokuo Shi; Xing Zhou; Chengjie Gao; Yawen Li; Hongmei Chen; Huifen Fu (Journal of Environmental Chemical Engineering, 2026)

Effects of ScCO2-H2O on the macromolecular structure and adsorption characteristics of low-rank coal in the Ordos Basin - Huanshuang Xing; Yi Du; Changqing Fu; Zhejun Pan; Zhenliang Wang; Jinfeng Ma; Wei Gao; Li Ma (Fuel, 2026)

A phytoalexin-inspired, natural product-based marine antifouling coating with synergistic active antimicrobial and passive anti-adhesive performances - Liang Ma; Xing-Yu Lei; Qi Xu; Ya-Fu Li; Yu-Hao Li; Peng-Fei Chen; Jian-Cai Chen; Hui-Jing Li; Yan-Chao Wu (Chemical Engineering Journal, 2026)

Synergistic Al@MgH2 composites for on-demand power generation in fuel cells - Yu Xiong; Wenshang Chen; Lizhong Duan; Huihu Wang; Shenghao Jiang; Chenhuinan Wei; Xing Xiang; Yun Zhao; Qianyu Wang; Xudong Fu; Ben Chen (Chemical Engineering Journal, 2026)

Impact of carboxymethyl cellulose on the gelation and digestive characteristics of myofibrillar protein and its application for encapsulation of puerarin - Qiao-bo Zhang; Shi-Meng Liang; Yan-wei Yuan; Xue-xing Yin; Jing-jing Fu; Yue-wen Chen; Wen-qiang Cai (Carbohydrate Polymers, 2026)

Abundance, composition, and environmental implications of iron minerals in highly permeable sandy beaches - Yan Zhang; Cheng Xing; Liuqian Yu; Tian Fu; Shuoyu Zhang; Yi Liu (Chemical Geology, 2026)

Integrated physiological and multi-omics insights into Chlorella mutagenized by atmospheric and room temperature plasma for enhanced saline aquaculture wastewater treatment and bioresource production - Xiao-Ya Liu; Fan-Xing He; Tong-Chao Qu; Zhao-Hong Weng; Peng-Fei Li; Jie Ye; Hai-Yan Fu (Bioresource Technology, 2026)

Manganese cycle-mediated synchronous bacteria-algae/anammox coupled denitrification system under low-temperature conditions: Performance and mechanisms - Peng-fei Yu; Dian-lin Jiang; Ding Wang; Xing-guan Ma; Jun-Li; Li-yao Han; Ao Wang; Yu-bo Fu; Xing Jin (Bioresource Technology, 2026)

Spatiotemporal Variation Analysis of Yangtze River Basin Water Quality in Chong Qing, China During 2021–2023 Based on Improved Water Quality Assessment - Libo Ran; Xing Wei; Yulin Zhou; Qingmei Zhang; Yanan Fu; Zikan Deng (Water, Air, & Soil Pollution, 2026)

Design and synthesis of stilbene analogs based on resveratrol as NF-κB inhibitors for the treatment of breast cancer - Shaojuan Fu; Yu Zhang; Yuanli Yang; Xing Lu; Yanni Wang; Lingling Lei; Junjie Lan; Huan He; Silong Zhang; Weidong Pan (Molecular Diversity, 2026)

Study on the effect of high temperature on the seismic performance and rotor dynamic characteristics of the molten salt pump for reactor - Xing-Chao Shen; Yuan Fu; Jian-Yu Zhang; Jin Yang; Xiao-Yan Wang; Zhi-Jun Li (Annals of Nuclear Energy, 2026)

Genetic origins and climate‐induced erosion in economically important Asian walnuts - Peng‐Zhen Fan; Guang‐Fu Zhu; Moses C. Wambulwa; Richard I. Milne; Zeng‐Yuan Wu; Ya‐Huang Luo; Robabeh Shahi Shavvon; Alistair S. Jump; Debabrata Maity; Lian‐Ming Gao; Hai‐Ling Qi; Hong‐Yu Wu; et al. (Conservation Biology, 2026)
The global climate is undergoing unprecedented changes, posing significant threats to species persistence. However, the spatiotemporal impacts on genetic diversity remain poorly understood, hindering species conservation and management. Walnuts, generally referred to as Juglans regia and J. sigillata , are economically vital in Asia, but little is known about their genetic origins and how the species will be affected by future climate change. Using 31 microsatellites, we genotyped 5282 individuals from 233 populations of walnuts in Asia. We assessed genetic diversity patterns and demographic history and investigated potential future genetic erosion risks. Genetic diversity of walnuts was high in the Himalaya and Hengduan Mountains. The 2 species diverged during the Pleistocene (around 1.41 Ma BP), and J. regia contained 2 genetic groups (JR1 and JR2). The JR2 group had the lowest diversity and likely arrived in northern China around 9.77 ka BP, perhaps via human transport. The Western Himalaya likely served both as a glacial refugium and the center of origin for J. regia , and the Eastern Himalaya appears to have been the refugium for J. sigillata . The 2 species appear to have hybridized in the Central Himalaya and the Sichuan basin and surroundings, forming two distinct hybrid zones. Our results indicate that genetic diversity will be reduced by up to 9.03% due to range loss under future climate change and dramatic genetic structure turnover in the Himalaya and Hengduan Mountains. In situ conservation in the Himalaya is essential for safeguarding genetic diversity and adaptive potential in Asian walnuts, while ex situ preservation of genetically unique wild germplasm, coupled with its integration into breeding programs, will enhance climate resilience. The findings advance our understanding of the origin of Asian walnuts and how future climatic change may affect their genetic diversity, offering a model for conservation and breeding strategies in other tree species facing similar threats.

Lanostane triterpenoids from the fruiting bodies of Ganoderma multipileum and their anti-inflammatory activities - Mei-Juan Li; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Yan Hua; You-Xing Zhao (Natural Product Research, 2026)

Two new compounds isolated from an endophytic fungus Eutypella sp. XLE005 derived from Conus leopardus - Xin-Ming Li; Li Yang; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Du-Qiang Luo; You-Xing Zhao (Natural Product Research, 2026)

Cochliomycin H, a new 12-membered resorcylic acid lactone from sponge-derived fungus Curvularia sp. ZYX-Z-4 - Jiu-Jiu Zhou; Li Yang; Qing-Yun Ma; Qing-Yi Xie; Hao-Fu Dai; You-Hua Liu; Zhao You-Xing (Natural Product Research, 2026)

Persteroid, a new steroid from the marine-derived fungus Penicillium sp. ZYX-Z-143 - Lu-Ting Dai; Li Yang; Zi-Peng Wang; Jiao-Cen Guo; Qing-Yun Ma; Qing-Yi Xie; Hao-Fu Dai; Zhi-Fang Yu; You-Xing Zhao (Natural Product Research, 2026)

Few-shot natural frequency prediction of Camellia oleifera for vibration harvesting enabled by synthetic data generation - Feng Liu; Dongying Mo; Han Fu; Shaozheng Yu; Xuan Chu; Nan She; Xing Xu; Weizu Wang; Jieli Duan (Computers and Electronics in Agriculture, 2026)

The effects of thermal stress on the morphology, physiological functions, gut microbiota, and metabolism of Penaeus vannamei under seawater and low-salinity conditions - Xuan-yi Zhu; Yi-fu Xing; Xiao-ting Zheng; Jian-hua Huang; Jian Qin; Jia-song Zhang (Aquaculture, 2026)

The novel model INEDM and two traditional models for estimating the carrying capacity of Hong Kong oyster (Crassostrea hongkongensis) in two aquaculture systems in Guangdong Province of China [Aquaculture Volume 609, July 2025.] - Xing-Chi Guo; Wen-Ding Liu; Xiao-Yan Ye; Ting-Long Hou; Yao-Wu Fu; Qi-Zhong Zhang (Aquaculture, 2026)

Smart detection of biofouling: A deep learning framework for water infrastructure surveillance - Xuanwei Xing; Mengzhen Xu; Congcong Wang; Xinyang Li; Yongxian Zhang; Yuan Xue; Xudong Fu (Water Research, 2026)

Increased microbial extracellular polymeric substances as a key factor in deep soil organic carbon accumulation - Mengxi Feng; Ming Zhang; Peng Cai; Yichao Wu; Qingling Fu; Xin Zhang; Fei Miao; Wen Xing; Shuiqing Chen; Ke-Qing Xiao; Yong-Guan Zhu (Soil Biology and Biochemistry, 2026)

Carbon isotope stratigraphy of the Doushantuo Formation in basinal facies of South China: Constraints on the Shuram excursion in a deep ocean environment - Rui Fu; Chaochao Xing; Lei Zhang; Meng Ning; Fangbing Li; Xianguo Lang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Mechanistic role of chloride in enhancing carbamazepine degradation by dithionite-activated sodium hypochlorite - Wei Song; Hongze Fang; Zhitao Zhang; Caixia Fu; Xing Du; Bingzhi Liu; Bin Li; Ruigang Wang; Chunyan Huang; Zhihong Wang; Zhiwei Zhao (Journal of Hazardous Materials, 2026)

Occurrence, fate, and integrated risk profiling of legacy and novel brominated flame retardants in the Yellow and Bohai Seas - Jie Fu; Xing Liu; Mingliang Zhao; Longkun Sun; Huian Jin; Wenqing Wang; Helin Sun; Dong-Liang Lu; Gui-Peng Yang (Journal of Hazardous Materials, 2026)

Enhanced flotation upgrading of high-ash fine waste coal with a novel compound collector: High-value and clean utilization of waste - Zili Yang; Yuhao Chang; Yanzhen Fu; Qieyuan Gao; Guoxiao Wang; Yangchao Xia; Yaowen Xing; Xiahui Gui (Journal of Cleaner Production, 2026)

Antibacterial mechanism of vitamin C against Staphylococcus aureus, reduction of toxicity of metabolites and its application in pasteurized milk - Lei Tian; Chunyang Huang; Xing Liu; Yuxin Zhang; Ting Zhou; Ying Yu; Chunling Zhang; Hu Pan; Yanna Dai; Jifeng Pu; Chengyu Fu; Pengfei Zhang; et al. (International Journal of Food Microbiology, 2026)

Thermal polymerization and structural analysis of ovotransferrin fibrils: Antibacterial activity and mechanism of action - Xianjiang Ye; Wei Hu; Xi Zeng; Pengfei Geng; Yixin Zhang; Jihan Mohamed Kassem; Xing Fu (Food Research International, 2026)

Prenatal and postnatal exposure to environmental level arsenic declines male reproductive function by affecting spermatogenesis and maturation in offspring - Xiaochao Song; Xu Yang; Weixiang Fu; Ying Xing; Chenkai Cheng; Xiaohui Tian; Wei Yang; Liying Zhao; Yiguang Lu; Xiang Li; Ao Cheng; Shu Liu; et al. (Environmental Research, 2026)

Facile molten salt synthesis of Co@N-C catalysts enables highly efficient HMF-to-FDCA conversion under mild conditions - Hao-Yue Ma; Jun-Fei Gu; Xing-Chuan Li; Zhan Chen; Qi-Yu Fu; Francis Verpoort; Wen-Jie Mo; Zheng Liu; Cheng Chen; Soon Hyeok Hong; Zongkui Kou (Chemical Engineering Journal, 2026)

Fabrication of Prussian blue mixed matrix membranes based on the synchronous growth for water treatment - Xiaotong Lu; Xing Gao; Xiaojiao Hou; Bingbing Chen; Peining Han; Tieqiang Wang; Fanbao Meng; Yu Fu (Chemical Engineering Journal, 2026)

Dynamic magnetic field enhances aerobic composting humification: Biotic and abiotic mechanisms - Ruizhi Xing; Jiali Wang; Ziyi Fu; Xiaoyan Chen; Zhouwen Yang; Yunrui Xu; Jianhui Huang; Jian Lü; Hao Lin; Zhi Chen; Shungui Zhou (Chemical Engineering Journal, 2026)

Closed-form solution method for mechanical response of isolated-span transmission line after ice shedding based on state discretization - Zhao Yan; Si-yuan Wu; Xing Fu; Hong-nan Li; Hao Li; Zeng-hao Huang (Cold Regions Science and Technology, 2026)

High-resolution chronostratigraphic framework and spatiotemporal evolution of Carboniferous-Permian source rocks in the Junggar Basin and its periphery - Zhangshuai Hou; Xiangdong Wang; Dongming Zhi; Yong Tang; Qiong Wu; Hua Zhang; Jian Cao; Dongsheng Xiao; Guobin Fu; Menglin Zheng; Xuefeng Qi; Yaofeng Cai; et al. (Science China Earth Sciences, 2026)

Microscopic probing into plasmodesmata (PD) and PD-derived intercellular gateways (PdIGs): Beyond morphology - Ming-fang Lv; Wei-na Shang; Yuan-xing Dai; Jun-ying Li; Yi Li; Shuai Fu; Jian Hong; Li Xie; Heng-Mu Zhang (Protoplasma, 2026)

Interpretability-Enhanced Mineral Prospectivity Models: A Synergistic Approach Using Large Language Models, Knowledge Graphs, and Machine Learning - Zhen-Jie Zhang; Zi-Xing Yang; Fu-Yuan Jian; Si-Yuan Ban; Yi-Ming Wang (Mathematical Geosciences, 2026)

Nanoconfinement-enhanced lanthanum-biochar composites for simultaneous adsorption and catalytic hydrolysis of organic phosphorus pollutants - Shiyun Xu; Xing Yan; Yuchen Wei; Yanyang Zhang; Wanyi Fu; Zhichao Yang; Chao Shan; Bingcai Pan (Water Research, 2025)

Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

High-resolution spatial mapping of electrocorticographic activities with NeuroCam: a 4096-channel, multiplexed flexible thin-film transistor array - Yang Xie; Zepeng Zhang; Muyang Liu; Jinhong Guo; Miao Xu; Lei Zhou; Lei Zhang; Lihao Yao; Xiaolin Zhou; Zhengwei Hu; Liang Ma; Xiaojian Li; et al. (Science Bulletin, 2025)

Multidimensional mechanistic analysis elucidates spermatogenesis disruption induced by bisphenol S - Lei Xu; Bin Huang; Shengliang Gu; Yitao Xing; Fugang Zhang; Wei Fu; Ting Chen; Zhuojun Yuan; Guozheng Qin (Reproductive Toxicology, 2025)

Selective recycling of rare earth elements from high alumina fly ash by phase separation assisted mechanochemical extraction process - Mingfei Xing; Shuofei Fu; Pengyong Zheng; Mingshi Wang; Li Zhao; Fayang Guo; Fengcheng Jiang; Chengjie Li (Process Safety and Environmental Protection, 2025)

Spatial and temporal distribution of Sthenoteuthis oualaniensis in the Northwest Indian Ocean during different life stages of cyclonic eddies - Fu Yingyue; Wu Xiaoci; Jin Pengchao; Zhang Zhong; Xing Qinwang; Yu Wei (Journal of Marine Systems, 2025)

Effects of representative Chinese cattle breeds on the eating quality and microstructure of braised beef - Jian Hu; Xiaoke Fu; Yijie Cai; Ronglan Wang; Rui Xu; Chengrong Zheng; Xing Chen; Bowen Yan (International Journal of Gastronomy and Food Science, 2025)

Early Miocene fossils from Shaoma, China, evidence Eurasia-North America ruminant exchange - Shi-Qi Wang; Tao Deng; Tingjiang Peng; Bian Wang; Qigao Jiangzuo; Jiao Fu; Danhui Sun; Luda Xing (Geobios, 2025)

Ultrasound-assisted shear homogenization for preparing chitin nanocrystal-stabilized Pickering emulsions - Yimeng Lou; Te Yu; Binyan Zeng; Muhammad Moeid Khan; Nikolai Kuhnert; Ok-Hwan Lee; Xing Fu (Food Chemistry, 2025)

Combining untargeted metabolomics and chemometrics to reveal the metabolic profiles of jujube-hawthorn fermented beverages at different fermentation stages - Zhibin Xing; Tarun Belwal; Hao Huang; Xiang Li; Liangxia Han; Yahui Yin; Chunhui Shan; Xizhe Fu; Yinglin Du (Food Chemistry, 2025)

Application of Fe-CuO bimetallic oxide nanozyme-based colorimetric sensing for highly sensitive detection of tetracycline: theoretical and experimental studies - Ying Fu; Di Wu; Yuanyuan Du; Ruixue Wang; Jinfeng Tian; Xing Gao; Chao Guo (Food Chemistry, 2025)

Multigraph fusion neural network for predicting available cadmium levels in farmland soils - Ren-Jie Zhang; Shu-Fang Pan; Huai-Zeng Xing; Tian-Hao Dong; Sai-Hua Liu; Tao Xue; Fa-Xiang Tian; Hong-Yu Fu; Yun-He Xie; Xiong-Hui Ji (Environmental Pollution, 2025)

Ohmic contact interface engineering of fullerene-derived long-range ordered porous carbon-based anodes for durable sodium-ion capacitors - Jundong Shao; Mingming Gao; Ying Huang; Songlin Liu; Junke Li; Xiaosong Xiong; Antonio Gaetano Ricciardulli; Sheng Yang; Yubin Fu; Faxing Wang; Chun Fang; Panpan Zhang; et al. (Chemical Engineering Journal, 2025)

Stretching a single sugar chain - Yun-Long Chen; Chen-Chen Zheng; Fu-Jia Tian; Tai-Lang Yin; Xing-Hua Zhang (Carbohydrate Polymers, 2025)

Chemical and Isotopic Characteristics of Groundwater in Typical Cities of Three Gorges Reservoir Area in China and Its Suitability for Agricultural Irrigation - Xing Wei; Libo Ran; Yulin Zhou; Mengen Chen; Kaiyu Jiang; Yanan Fu (Water, Air, & Soil Pollution, 2025)

Co-expression analysis provides a new strategy for mining key metabolites and genes in response to drought stress in Agropyron mongolicum - Jing Wang; Shoujiang Sun; Shuxia Li; Wenxue Song; Xing Wang; Shuaiqi Guo; Xiaoya Hu; Xueqin Gao; Bingzhe Fu (Plant Molecular Biology, 2025)

Araloside A Induces Raf/MEK/ERK-Dependent Autophagy to Mitigate Alzheimer’s and Parkinson’s Pathology in Cellular and C. elegans Models - Xue Chen; Xing-Yue Zhou; Cai Lan; Hai-Jun Fu; Zhi-Chao Li; Meng-Yi Chen; Yong-Ping Wen; Lu Yu; Da-Lian Qin; An-Guo Wu; Jian-Ming Wu; Xiao-Gang Zhou (Molecular Neurobiology, 2025)

Logging intensity and biome type mediate the effects of forest logging on soil greenhouse gas emissions - Chenjun Du; Xing Wu; Hao Shi; Bojie Fu; Ting Li; Yihe Lü; Lingfan Wan; Shuang Zhang; Binbin Huang; Yibin Shi (Agriculture, Ecosystems & Environment, 2025)

Microbial nitrogen removal processes under PFAS stress: mechanisms, functional evolution, and research outlook - Wenting Fu; Xianglan Ao; Yuan Zhou; Mengxue Xing; Zhilin Xing (Biodegradation, 2025)

Quantitative estimation of the spatiotemporal responses of PM2.5 and O3 synergistic pollution to precursors in the Chengdu-Chongqing City Group of China - Mingliang Ma; Yihong Jiao; Mengjiao Liu; Mengnan Liu; Fei Meng; Huaqiao Xing; Jingxue Bi; Yuqiang Wang; Tongwen Liu; Pingjie Fu (Air Quality, Atmosphere & Health, 2025)

Spatial-temporal evolution of ecological-economic-disaster synergies and their dynamic response to land use efficiency: evidence from China - Boyi Li; Xing Zhu; Hao Zhu; Ruotong Yuan; Xiaodi Fu; Dongmei Liu; Xugong Jia; Min Tang (Environment, Development and Sustainability, 2025)

Dexmedetomidine alleviates ferroptosis caused by traumatic brain injury via the NRF2/HO-1/GPX4 pathway - Jin-Jing Hao; Xue-lian Fang; Yi-Yang Chen; Zi-jun Meng; Fu-xing Dong; Xiao-fang Yang; Zheng Chu; Jin-xia Kuai; Haijun Bao (Metabolic Brain Disease, 2025)

Per- and polyfluoroalkyl substances in tissues of intermediate egrets (Ardea intermedia) from the South China Sea - Ling Mo; Jun Xiang; Ming-Yang Wang; Yu-Quan Zhang; Qin-Wei Hao; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Jing Zheng; Qiao Xing; Bin Tang; Li-Cheng Wang (Marine Pollution Bulletin, 2025)

Research advances of nano chitin in the food industry: Focusing on physiological mechanisms of gut modulation - Yue Tian; Zhou Chen; Jiran Lv; Yongguo Jin; Ok-Hwan Lee; Nikolai Kuhnert; Shaoqing Yang; Zhengqiang Jiang; Xing Fu (Trends in Food Science & Technology, 2025)

Chitin nanofiber-stabilized pickering emulsions loaded with citrus essential oil: Characterization and application for pork preservation - Ge Wang; Te Yu; Jiran Lv; Linhua Huang; Ok-Hwan Lee; Xing Fu (Food Research International, 2025)

Ku proteins play a positive role in the immune response against WSSV infection in Litopenaeus vannamei - Huiling Xing; Wei Xiao; Guoqing Dai; Zhibin Fu; Sheng Ke; Lili Shi (Fish & Shellfish Immunology, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

The recovery mechanism of granular sludge fragmentation and re-granulation caused by long-term high-concentration organic matter erosion in the SAD process: performance, sludge evolution, and metagenomic sequencing - Peng-fei Yu; Ding Wang; Yu-bo Fu; Xing-guan Ma; Hao Zheng; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Xing Jin (Bioresource Technology, 2025)

Decadal landslide susceptibility mapping: Impacts of sampling methods on prediction accuracy - Xiaodi Fu; Xing Zhu; Qiang Xu; Hao Zhu; Ruotong Yuan; Jiang Li (Journal of Mountain Science, 2025)

Tailored novel geminal dicationic magnetic ionic liquid for rapid and efficient extraction of tetracyclines: Performance and mechanism - Lirong Nie; Xiang He; Pengkun Fu; Zixin Xing; Rongwei Sun; Ziyin Tang; Tingting Tang; Zhi Zhu (Analytica Chimica Acta, 2025)

Integrating remote sensing and mechanistic model for spatial evaluation of shelterbelt porosity and windbreak effectiveness in agricultural landscapes - Xing Zhang; Bolin Fu; Rongxin Deng; Ying Li; Jingwen Li; Jianwu Jiang; Jing Tang (Agricultural and Forest Meteorology, 2025)

Crop height retrieval from polarimetric SAR data using machine learning: A comparative and validation study - Shuaifeng Hu; Qinghua Xie; Xing Peng; Qi Dou; Jinfei Wang; Juan M. Lopez-Sanchez; Jiali Shang; Haiqiang Fu; Jianjun Zhu; Wenming Zhou (Computers and Electronics in Agriculture, 2025)

The novel model INEDM and two traditional models for estimating the carrying capacity of Hong Kong oyster (Crassostrea hongkongensis) in two aquaculture systems in Guangdong Province of China - Xing-Chi Guo; Wen-Ding Liu; Xiao-Yan Ye; Ting-Long Hou; Yao-Wu Fu; Qi-Zhong Zhang (Aquaculture, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Reinventing a sustainable Green Revolution by breeding and planting semi-dwarf maize - Senlin Xiao; Wei Song; Ronghuan Wang; Shuang Zhang; Mengyuan Liu; Ruyang Zhang; Tianjun Xu; Hui Liu; Jie Hu; Jinfeng Xing; Xiaqing Wang; Tianyi Wang; et al. (Molecular Plant, 2025)

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

The impact of the interaction between trace chloramphenicol, biofilm, and corrosion products on disinfection by-products and microbial risks in chlorinated drinking water distribution systems - Xinkai Liu; Yanliang Lin; Kaifeng Shen; Youyi Chen; Pojun Zhang; Zihui Chen; Yaning Zhang; Jing Huang; Leixuan Fu; Sibo Liu; Chun Hu; Xueci Xing; et al. (Journal of Water Process Engineering, 2025)

U-RNN high-resolution spatiotemporal nowcasting of urban flooding - Xiaoyan Cao; Baoying Wang; Yao Yao; Lin Zhang; Yanwen Xing; Junqi Mao; Runqiao Zhang; Guangtao Fu; Alistair G.L. Borthwick; Huapeng Qin (Journal of Hydrology, 2025)

Nitrogen and phosphorus addition affected soil organic carbon storage and arbuscular mycorrhizal fungi contributions - Shengchao Ma; Rui Guo; Yue Wang; Yan Yan; Qianwen Chu; Nan Cui; Yifei Zhang; Lei Zhang; Li Jiang; Lianxuan Shi; Jixun Guo; Yingzhi Gao; et al. (Journal of Environmental Management, 2025)

Discovery of dietary beneficial compounds for healthy aging: From worm to human - Xianjiang Ye; Hao Wang; Yuxuan Han; Xing Fu; Jiuliang Zhang; Tao Zhang (Food Research International, 2025)

Preparation and characterization of ovomucin-xanthan gum stabilized pickering emulsions: Microstructure, rheology, and stability - Binyan Zeng; Zhou Chen; Yimeng Lou; Yujuan Tian; Yongguo Jin; Xing Fu (Food Chemistry, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

One-step gel membrane fabrication via soft spray technique for dye/salt separation and desalination - Yuhang Li; Bingbing Chen; Huiyan Gao; Qiuyue Hu; Xing Gao; Yuanlin Fu; Aoxiang Zhang; Tieqiang Wang; Jun Zhou; Yu Fu (Desalination, 2025)

Photothermal-driven micromotor for enhanced lithium extraction from salt-lake brines - Shihao Ding; Wenqian Xing; Ling Chen; Linhui Fu; Xinle Zhang; Zhen Luo; Qianqian Li; Mengting Qin; Jiang Gong; Jinping Qu; Ran Niu (Chemical Engineering Journal, 2025)

Multi-level metalized PBO composite fabric for polar extreme environments: integrating electromagnetic protection, stable electric thermal conversion, and high-strength - Che Zhou; Dan Yu; Canglong Xing; Zhichao Zhu; Zeyu Yang; Xinhai He; Tao Fu; Zhongxiao Song; Wei Fan; Dongzhen Chen (Chemical Engineering Journal, 2025)

Microalgal glutaredoxin 1 interacts with transcription factor bZIP to resist cadmium stress via lipid metabolism alteration - Chao Xing; Xuan Fu; Yaru Du; Kui Liu; Hongli Yuan; Jin Liu; Jinshui Yang (Bioresource Technology, 2025)

Hydroxyl Radical‐Driven Oxidation as a Key Pathway for Greenhouse Gas Production During Soil Drying–Rewetting - Xing Guo; Yongxing Lu; Jungang Yang; Fan Du; Yakov Kuzyakov; Yuanhe Yang; Shen Yu; Shuping Qin; Qinglong Fu; Xiaoying Rong; Benfeng Yin; Kai Shi; et al. (Global Change Biology, 2025)
The drying‐rewetting of soil can increase the release of greenhouse gases over a short time period and is one of the key pathways for greenhouse gas emissions in many terrestrial ecosystems, particularly in drylands. The mechanisms underlying this pulse of greenhouse gas emissions remain nearly unknown. Here, we conducted simulated soil rewetting experiments using typical cover of dryland soils (bareland, cyanobacteria/lichen‐covered soil, and moss‐covered soil). The 13 C, 15 N, and 18 O labeling techniques allowed to explore the intrinsic mechanisms of rapid carbon (C) and nitrogen (N) release from the soils following rewetting. We found that the hydroxyl radical (˙OH) was produced after soil rewetting via the rapid activation of microorganisms. The carbon dioxide (CO 2 ) and nitrous oxide (N 2 O) production strongly decreased after ˙OH removal, whereas the methane (CH 4 ) production was not affected. The synergistic action between ˙OH oxidation and microbial enzymatic reactions increased CO 2 production. The ˙OH also stimulated the oxidation of NH 4 + to NO 3 − and dominated the N 2 O production. Our results confirm the role of ˙OH in the production of greenhouse gases and indicate that microbially mediated ˙OH oxidation mechanisms are an overlooked key pathway for the emission of greenhouse gases during the soil rewetting. In the context of climate change, the extreme weather‐induced drying‐rewetting cycles in soils are becoming more frequent, making greenhouse gas emissions via the ˙OH oxidation pathway increasingly important.

Identification of chemical composition and prediction of in vitro anti-inflammatory activity mechanism of ethyl acetate fraction of Lagenaraia siceraria seed - Yurong Wang; Xiaoyu Fu; Shuyu Xu; Xianyan Li; Siyu Zhao; Yating Zheng; Nanping Jiang; Xin Chen; Xing Wang; Hezhong Jiang (Natural Product Research, 2025)

Immune responses of Ctenopharyngodon idella juveniles against the ciliated parasite's reinfection induced by Ichthyophthirius multifiliis theronts at the threshold density - Ting-Long Hou; Yao-Wu Fu; Xing-Chi Guo; Shu-Guan Guo; Shi-Lu Huang; Qi-Zhong Zhang (Aquaculture, 2025)

Investigating the particle size effect of calcareous sand using a critical state-based model with the covariance matrix adaptation evolutionary strategies algorithm optimization - Xing Wang; Zhen-Yu Yin; Yin-Fu Jin; Mao-Zhu Peng; Jie Cui (Transportation Geotechnics, 2025)

Evaluating the potential impacts of mesoscale eddies on the distribution and abundance of an environmentally sensitive squid species (Sthenoteuthis oualaniensis) in the Arabian Sea - Yingyue Fu; Xiaoci Wu; Pengchao Jin; Xinjun Chen; Qinwang Xing; Fei Chai; Jie Cao; Wei Yu (Marine Environmental Research, 2025)

Neurotoxicity of chronic nano-neodymium oxide exposure in zebrafish: Behavioral and molecular insights - Bao-Fu Zhang; Xing-Zhe Wu; Jin-Xia Wang; Yan-Ling Liao; Zi-Xin Cai; Yiyun Liu; De-Sheng Pei (Journal of Hazardous Materials, 2025)

Greenhouse gas emission reduction strategies for petrochemical wastewater treatment: Life cycle assessment of retrofitting scenarios - Xin Bao; Song Gao; Hong Yao; Xiaoping Fu; Xinyu Gao; Hui Wang; Wei Xing (Journal of Cleaner Production, 2025)

Mechanisms and effects of the digital economy on agricultural modernization: A sustainable development perspective - Yinghui Li; Xing You; Junzhi Fu; WenJing Zhou (Journal of Environmental Management, 2025)

Quality characteristics and structure-function relationships of peanut proteins from different phase sources by aqueous enzymatic extraction - Xin Guo; Wen-ye Xie; Hui Hu; Feng-ying Gu; Fu-sheng Chen; Xing-feng Guo; Bo Jiao; Qiang Wang (Food Chemistry, 2025)

Paeoniae Radix alba polysaccharide modulates gut microbiota to restore metabolites and promote the enteric nervous system development in colitis mice - Chao-Wen Zhang; Si-Zhe Shui; Shuang Liao; Yu-Chao Kuang; Dai-Zheng Yin; Yi Gu; Banaz Jalil; Michael Heinrich; Xing-Fu Chen; Zhong-Qiong Yin; Chun Wu; Xu Song; et al. (Food Bioscience, 2025)

Earth pressure on rotating-about-top excavation retaining walls adjacent to existing structures - Xin-yi Huang; Chang Chen; Fu-quan Chen; Yi-xing Kuang (Computers and Geotechnics, 2025)

Degradation of mesotrione in bioelectrochemical system: Performance, mechanisms, and microbial communities - Zhibing Xing; Qiang Fu; Hong-Yu Ren; Lihong Wang; Fanying Kong (Chemical Engineering Journal, 2025)

A unique demersal fish fauna in the Chukchi Borderland, Central Arctic Ocean - Ran Zhang; Hai Li; Puqing Song; Rui Wang; Jing Zhang; Tianci Wang; Shusen Fu; Shigang Liu; Yuan Li; Xing Miao; Lei Yang; Longshan Lin (Reviews in Fish Biology and Fisheries, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Nitrite and sulfide stress induces hepatopancreatic oxidative stress, lipid metabolism disorders, ferroptosis and apoptosis in the Chinese mitten crab, Eriocheir sinensis - Yi-Fu Xing; Yi-Fan Feng; Jian Tian; Qi-Bin Zhu; Cui Han; Xiao-Jie Liu; Jiang-Hua Yang; Jia-Xin Yang (Aquaculture, 2025)

Scandium and gallium in weathered basalts as unconventional resources - Mei-Fu Zhou; Wen Winston Zhao; Zhenchao Wang; Min Wang; Shengbiao Yang; Lei Meng; Liang Qi; Guangfu Xing; Xiang Li; Dai Zhou (Journal of Asian Earth Sciences, 2025)

Continuous reduction in socio-ecological system vulnerability on the Qinghai–Tibet Plateau from 2000 to 2050 under an intermediate protection scenario - Zhengyuan Zhao; Bojie Fu; Yihe Lü; Ting Li; Yuelu Wang; Haoyue Wang; Binbin Huang; Xing Wu (Environmental Impact Assessment Review, 2025)

Viscosity-activated reversible fluorescent probe for monitoring the diabetic refractory wound microenvironment - Wen-Juan Fu; Wei Wei; Jia Chen Shen; Chao Wang; Xing Pan; Dong Bing Liang; Dong Zhu (Chemical Engineering Journal, 2025)

Biodegradable Mg–Cu alloy inhibits HBV replication and hepatocellular carcinoma progression - Heyu Zheng; Weiping Zhou; Meiqi Mao; Yiwei Wang; Xing Tian; Biao Yang; Lu Zhao; Shu Li; Ye Sun; Zhongjia Jiang; Ronghua Fan; Yuxin Bai; et al. (BioMetals, 2025)

Ore-forming fluid for the formation of banded iron formation-hosted high-grade magnetite ores of the North China Craton: Constraints from pyrite trace elements and sulfur isotopes - Yi Wang; Li-Xing Li; Hou-Min Li; Jian-Fei Fu; Yang Dai; Xiao-Hui Wang; Xuan Wu (Journal of Asian Earth Sciences, 2025)

Investigating coalbed gas productivity response from hydrogeochemical and microbial perspectives: A case study of the Liulin block, eastern Ordos Basin, China - Yueguo Li; Haijiao Fu; Xianbo Su; Detian Yan; Gang Wang; Shuguang Yang; Xing Chen; Jianzhang Liu; Jintao Kong (International Journal of Coal Geology, 2025)

An improved direct analysis method of transmission towers incorporating geometric defects and bolt slippage effects - Yu Zhu; Hong-Nan Li; Xing Fu; Jia-Xiang Li; Rui-Zeng Wei (Engineering Structures, 2025)

pH-responsive drug-targeted delivery system: Dual-drug loading hollow mesoporous silica for synergistic therapy bacterial enteritis of Micropterus salmoides - Yuan-shuai Fu; Yue Lin; Wen-jun Zhong; Xing-yu Wang; Xi-ke Li; Yun-ao Li; Sheng-bo Ye; Wen-juan Li; Yong-heng Zhu (Chemical Engineering Journal, 2025)

Nitrogen addition affects tree trait expression by altering endophytic microbe diversity - Guoyong Yan; Xi Luo; Guancheng Liu; Binbin Huang; Honglin Wang; Xingyu Sun; Gang Fu; Lei Liu; Yajuan Xing; Qinggui Wang (Plant and Soil, 2025)

Conditioned Medium of BMSCs Alleviates H2O2-Induced Oxidative Damage in PC12 Cells Through the LDLR Pathway - MingDong Li; Zhongquan Fu; Xing Gao; Yuchen Zhang; Zengxin Gao (Molecular Neurobiology, 2025)

Mechanism study of the effects of astragaloside IV and quercetin on idiopathic pulmonary fibrosis - Ye Luo; Chang-jun Xu; Xing-hui Ai; Yu-ping Li; Xing Zhu; Chang-fu Yang (Journal of Natural Medicines, 2025)

The Complete Mitochondrial Genome of Acrossocheilus spinifer (Osteichthyes: Cyprinidae) and Its Phylogenetic Analysis - Jian Gong; Shi-Qi She; Guang-Fu Liu; Xing-Xing Zhao; Le-Yang Yuan; E Zhang (Fishes, 2025)
In this study, we sequenced and characterized the complete mitochondrial genome of Acorssocheilus spinifer, an endemic stream-dwelling cyprinid species from South China first described in 2006. The mitogenome is 16,591 bp in length and contains the standard set of 37 genes (13 protein-coding genes, 22 tRNA genes, 2 rRNA genes) plus a control region. The genome exhibits typical cyprinid characteristics, with most genes encoded on the H-strand and a nucleotide composition biased toward A + T (55.9%). All tRNA genes display the typical cloverleaf secondary structure, except for tRNASer (GCU), which lacks the dihydrouridine (DHU) arm. Phylogenetic analysis using complete mitogenomes from 14 Acrossocheilus species revealed that 12 species form a monophyletic assemblage with three distinct clades. Within this framework, A. spinifer clusters closely with A. beijiangensis, supporting previous morphological observations. Our findings provide valuable genetic data for further taxonomic refinement and conservation efforts for Chinese barred species of Cyprinidae.

Insight into homogeneous activation of sodium hypochlorite by dithionite coupled with dissolved oxygen (DO@NaClO/DTN) for carbamazepine degradation - Wei Song; Hongze Fang; Zhaosheng Lei; Ruigang Wang; Caixia Fu; Fei Wang; Yuning Fang; Xing Du; Zhihong Wang; Zhiwei Zhao (Water Research, 2025)

Biodegradable and antibacterial edible films based on egg yolk granules/gelatin/CMC with e-poly-l-lysine: Application in fresh chicken meat preservation - Muhammad Moeid Khan; Shuguo Sun; Ran Shi; Lv Aichun; Ok-Hwan Lee; Xing Fu (Food Chemistry, 2025)

Pullulanase-catalyzed hydrolysis of V-type starch produced high-adsorbency V-type porous starch attaching by nano-spherical particles - Xing Zhou; Yanxin Chen; Miaomiao Fu; Zhengye Sun; Tizazu Yirga Bereka; Mudassar Hussain; Guo Chen; Ren Wang; Zhengyu Jin (Food Bioscience, 2025)

Distribution, origins, impact factors and ecological risks of metallic elements in the sediment from Changhua River estuary, Hainan Island, China - Jiyong Ma; You Gou; Zeheng Chen; Kaizhe Fu; Dongming Wu; Dayu Bian; Jianhua Guo; Shiyou Zhang; Zhuang Xing; Dongxu Jiang (Frontiers in Marine Science, 2025)
Within the framework of global biogeochemical cycles, estuaries function as a critical interface that connects terrestrial and marine ecosystems. We assessed the heavy metal pollution risk in the Changhua River estuary area. The assessment focused on pollution characteristics, spatial distribution, and ecological risks, while also identifying potential origins of metallic elements through the application of correlation analysis, principal component analysis (PCA), and Positive Matrix Factorization (PMF) models. The results showed that: (1) Sediments were predominantly sandy and weakly alkaline properties, with significant spatial heterogeneity in metallic concentrations. The concentration of metals, compared to their background values (BVs), could be ranked as: Nearshore: Pb > As > Cd > Cu > Zn > Hg > Ni > Cr; Inshore: Cd > Hg > Pb > Zn > Cu > As > Ni > Cr; Estuary: Pb > Cd > Hg > Cu > Zn > Ni > Cr. Particularly, Cd and Hg in inshore sediments registered a mean concentration surpassing their BVs by 417.95% and 187.33%, respectively. (2) The sampling locations presented varying levels of ecological risk. Moderate ecological risk (150 ≤ RI < 300) accounted for 24.14% of the sites, primarily located in inshore and estuarine areas, while extreme ecological risk (300≤RI) was observed in 6.90% of the sites, concentrated within inshore regions. Hg and Cd were identified as the most hazardous metals. (3) Regarding metallic sources, Hg mainly originated from coal burning, while Pb, Zn, and Cd were likely linked to anthropogenic activities associated with port operations. In contrast, Cr, Ni, and Cu were primarily derived from natural and agricultural sources, and As was mainly associated with the residual accumulation of fertilizers and herbicides. Overall, human activities, including agriculture, aquaculture, and port transport, are the primary origins of metallic contamination in the estuarine sediments. Effective management and regular monitoring of port activities are essential for the governance of the estuarine environment. Such practices can yield valuable insights for continuous risk analysis, thereby supporting the ecological health and resilience of these vital environments.

Sensor with Strong Solid Emission for Fluorescence Colormetric Detection of 1, 4-Dioxane in Water and Vapor Based on the Keto-Enol Isomerisation - Jing Wang; Zi-Ao Zong; Shi-Fu Huang; Mohd. Muddassir; Zhi-Yong Xing; Na-Na Li; Wen-Qiong Jiang (Journal of Fluorescence, 2025)

Microplastics in groundwater: Environmental fate and possible interactions with coexisting contaminants - Shengfeng Liu; Chengcheng Li; Jochen Bundschuh; Xubo Gao; Xing Gong; Huihui Li; Mengyun Zhu; Ling Yi; Wenxuan Fu; Fengze Yu (Environmental Pollution, 2025)

Advances and applications in single-cell and spatial genomics - Jingjing Wang; Fang Ye; Haoxi Chai; Yujia Jiang; Teng Wang; Xia Ran; Qimin Xia; Ziye Xu; Yuting Fu; Guodong Zhang; Hanyu Wu; Guoji Guo; et al. (Science China Life Sciences, 2025)

Chemical constituents of Pedicularis rex C. B. Clarke and their hepatoprotective activities - Yang Fei-Yu; Liu Huai-Qin; Fu-Rui Wang; Zhang Li-Jie; Liao Xing-Jiang; Guo-Bo Xu; Qin-Feng Zhu; Shang-Gao Liao (Natural Product Research, 2025)

Adsorption characteristics of sulfate reducing bacteria Clostridium sp. on lignite surface - Huan He; Zi Yang Zhou; Di Zhan; Yong Zhang; Wen Cheng Xia; Bo Fu; Feng Juan Lan; Xiu Xiang Tao; Zai Xing Huang (Environmental Science and Pollution Research, 2025)

Impacts of sulfamethoxazole on heterotrophic nitrification-aerobic denitrification bacteria and its response strategies: Insights from physiology to proteomics - Teng-Fei Ma; Xiao-Yao Yu; Chong-Yang Xing; Hui-Min Fu; Hao-Yang Duan; You-Peng Chen (Journal of Environmental Management, 2025)

Physiological and proteomic insights into silver nanoparticle-induced stress responses and resistance mechanisms in aerobic denitrifying Enterobacter cloacae HNR - Teng-Fei Ma; Hong-Xi Ma; Chong-Yang Xing; Hui-Min Fu; Yu Shen; You-Peng Chen; Xiang-Yang Wei (Journal of Environmental Chemical Engineering, 2025)

Chitin nanofiber-stabilized pickering emulsion interacting with egg white protein: Structural features, interfacial properties, and stability - Zhouyi Xiong; Te Yu; Jiran Lv; Jihui Wang; Xing Fu (Food Hydrocolloids, 2025)

Hybrid crosslinking cellulose nanofibers-reinforced zwitterionic poly (ionic liquid) organohydrogel with high-stretchable, anti-freezing, anti-drying as strain sensor application - Dong Fu; Linhui Xing; Yang Xie; Peng Li; Fan Yang; Xin Sui; Jiaying Liu; Jialong Chi; Bo Huang; Jun Shen (Carbohydrate Polymers, 2025)

Hesperidin alleviates endothelial cell inflammation and apoptosis of Kawasaki disease through inhibiting the TLR4/IĸBα/NF-ĸB pathway - Yuting Guan; Jinghua Ruan; Pingping Tan; Songwei Qian; Size Zhou; Ao Zhang; Yuchong Fu; Shuhui Zhao; Yuqing Ran; Xing Feng; Yijia Wang; Xinlei Wu; et al. (Chemico-Biological Interactions, 2025)

Seismic interaction and improved design method of substation equipment with multiple electrical configurations - Enrui Guo-Dai; Xing Fu; Gang Li; Hongnan Li; Liang Ren (Earthquake Engineering and Engineering Vibration, 2025)

N-doped carbon nanotubes encapsulated Ni3ZnC0.7 nanoparticles catalyst for peroxymonosulfate activation: Heterojunction structure and N-doping enhance electron transfer capability - Qihao Sun; Huiyuan Deng; Na Zhao; Junjie You; Zhicheng Pan; Bo Xing; Yuling Ye; Bo Lai; Xinye Yang; Xinjie Wang; Yunhui Lu; Jian Li; et al. (Chemosphere, 2025)

The Tonian sedimentary records in the southwestern West Qinling orogen, central China, reveal an active margin setting - Zhidong Gu; Xing Jian; Guixia Liu; Hanjing Fu; Xiaotian Shen; Xiufen Zhai; Hua Jiang (Precambrian Research, 2025)

Altered precipitation affects soil enzyme activity related to nitrogen and phosphorous but not carbon cycling: A meta-analysis - Xiaowei Liu; Qing Bai; Ke Liang; Mengting Pei; Ji Chen; Biao Zhu; Qiang Yu; Changhui Peng; Fu Xing; Liang Guo (Journal of Environmental Management, 2025)

Effects of organophosphate esters on thyroid function during pregnancy: Risk of endocrine disruptors during early- and mid-pregnancy - Yang Li; YouRong Fu; Xing Liao; Pan Yi; Pan Liu; Jianqiu Chen; Changxin Shen; Yanhua Liu (Journal of Environmental Management, 2025)

Enhancing anammox granular sludge for mainstream anammox process by adding iron-loaded diatomite: Performance and intrinsic mechanism - Fanghua Xing; Xuejie Ma; Binbin Sun; Tao Wang; Fei Lian; Luyao Wang; Ziyi Fu (Environmental Research, 2025)

Hollow FeNi Prussian blue nanocages with enhanced peroxidase-mimicking activity for colorimetric detection of mercury ions and L-cysteine - Dai Lu; Xing Tian; Zixuan Fu; Sizhao Yang; Yixing Qiu; Yupei Yang; Bin Li; Wei Wang (Chemical Engineering Journal, 2025)

Rhizosphere bacterial communities mediate the effect of maize-soybean strip intercropping and nitrogen management on cadmium phytoextraction - Yuze Li; Ting Xing; Zhidan Fu; Tian Pu; Peng Ding; Yushan Wu; Feng Yang; Xiaochun Wang; Taiwen Yong; Wenyu Yang (Applied Soil Ecology, 2025)

Mulberry leaf extract reduces damage by regulating the oxidative response, immune response and intestinal flora of largemouth bass (Micropterus salmoides) under chronic heat stress - Bing Fu; Donglai Zhou; Xiaotong Qiu; Jieqiu Zheng; Qiong Yang; Yang Xiao; Sentai Liao; Qingrong Li; Dongxu Xing (Frontiers in Marine Science, 2025)
Chronic heat stress (HS) induces oxidative damage, low immunity, and intestinal flora disturbance of fish, posing great challenges to the aquaculture industry. As an important plant extract, mulberry leaf extract (MLE) has been shown to have antioxidant and immune-boosting properties. This study evaluated the protective effect of dietary MLE on HS-induced liver injury and intestinal flora disturbance in Largemouth bass ( Micropterus salmoides ) based on oxidative damage parameters, immune parameters, and intestinal flora composition. Fish were randomly assigned into three groups: CON group (ambient temperature, 26°C, basal diet), HS group (33°C, basal diet), and HS + MLE group (33°C, basal diet supplemented with 9 g/kg MLE). HS significantly decreased the final body weight, specific growth rate, intestinal villus length, muscular layer thickness, ACE and Chao1 indices, and lipase, trypsin, total superoxide dismutase (T-SOD), glutathione peroxidase (GPx), alkaline phosphatase (AKP), and lysozyme (LZM) activities, but significantly increased the feed conversion rate, aspartate aminotransferase (AST) activity, reactive oxygen species (ROS), malondialdehyde (MDA), complement 3 (C3) contents, and the relative abundances of Proteobacteria and Plesiomonas . Compared with the HS group, dietary MLE significantly improved lipase, trypsin, GPx, ACP, and LZM activities, and ACE and Chao1 indices in intestine, but significantly decreased the numbers of vacuoles and inflammatory cells, AST activity, and the GLU, MDA, and ROS contents. Dietary MLE also significantly up-regulated the mRNA expressions of gpx , tg f-β , il-10 , jnk2 , and bcl-2 , but down-regulated the mRNA expressions of il-8 , tnf-α , caspase-3 , atf4 , chop , ire1, traf2 , jnk1 , TRPV , MCU , and VDAC in liver. In conclusion, dietary supplementation with 9 g/kg MLE could improve the growth, immunity, and diversity of intestinal flora in heat-stressed largemouth bass, and alleviate hepatic injuries by regulating inflammation, oxidative stress, and apoptosis, providing a theoretical basis for the development of MLE as a treatment against HS.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Source-rock, grain-size, weathering, and recycling controls on the feldspar/quartz ratio in silt-sized sediments - Hanjing Fu; Xing Jian; Zhihua Zhang; Hanqing Pan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A scale for evaluating the willingness of national forest farm to participate in forest carbon sink project - Guanqing Wu; Degang Fu; Yingchao Xing; Huizhen Duan; Yifan Wang; Jihuai Hu; Yanping Wang; Fengjuan Zhang (Journal of Environmental Management, 2025)

Conversion of Lignin to Cyclohexanol via Mild Catalytic Depolymerization Coupled with Hydrogenation - Xiaoting Xing; Wenlong Cao; Jinliang Yan; Yuchun Zhang; Payam Ghorbannezhad; Zhiyu Li; Peng Fu (Journal of Environmental Chemical Engineering, 2025)

Characterization of pea protein-different types of glycoside flavonoid complex interactions and functional properties - Zihao Chen; Min Fu; Jun Chen; Guowen Zhang; Qin Geng; Xing Hu; Yihui Wang; Ti Li; Ruihong Liang; Taotao Dai (Food Research International, 2025)

An improved method to accelerate the acquisition efficiency of the T1-T2 spectrum based on the IR-BSSFP-CPMG pulse sequence∗ - Fu Zuo; Xinmin Ge; Lanchang Xing; Bohan Wu; Yiren Fan; Jackson Jervis Junior; Bin Wang (Computers & Geosciences, 2025)

Bibliometric analysis of microplastics research: Advances and future directions (2020–2024) - Zhilin Xing; Wenting Fu; Liangjie Li; Shan Wu (Continental Shelf Research, 2025)

The response mechanism of high-quality grass to typical poisonous weed root exudates and litter: Using Leymus chinensis and Stellera chamaejasme as examples - Ruohui Zhang; Shanmin Qu; Bin Zhang; Ying Gao; Fu Xing (Applied Soil Ecology, 2025)

Early Cretaceous dinosaur, bird and turtle tracks from the Lanzhou-Minhe Basin, Gansu Province, Northwest China - Lida Xing; Daqing Li; Qiyan Chen; Junyan Fu; Chunyong Chou; Lijun Zhang; Wenze You; Kexin Shi; Hendrik Klein (Cretaceous Research, 2025)

Nitrite and sulfide stress affects physiological and metabolic functions of gills in crab Eriocheir sinensis - Yi-fu Xing; Yi-fan Feng; Jian Tian; Yu Zhang; Cui Han; Xiao-jie Liu; Jia-xin Yang (Aquaculture, 2025)

Dissolved oxygen activated by single-atom-state iron coupled with sodium dithionite for norfloxacin degradation: Efficiency and mechanism - Wei Song; Sen Xu; Caixia Fu; Ruiyi Huang; Hongze Fang; Li Li; Dachao Lin; Yuning Fang; Xing Du; Zhihong Wang (Journal of Cleaner Production, 2025)

Insight into the impact of various processing stages on metabolites and flavors in jujube jam - Jun Liu; Zhe Wu; Jiamin Zhu; Xiaoyu Fu; Mengnan Wang; Jun Xing; Xinzheng Qin; Yixian Tu; Yun-Guo Liu (Food Research International, 2025)

Magnetic polydopamine nanoparticles as stabilisers for enzyme-Pickering emulsions: Application in the interfacial catalytic reaction of olive oil - Ziqi Lin; Linhua Huang; Adil Mohamed Abker; Deog-Hwan Oh; Jihan Mohamed Kassem; Mohamed Salama; Ran Shi; Xing Fu (Food Chemistry, 2025)

Effects of slurry ice treatment on the physicochemical changes and proteome of large yellow croaker (Larimichthys crocea) - Yan-wei Yuan; Yu-ting Liu; Xing-tong Zhu; Jin-xiu Yu; Jun-long Mao; Jing-jing Fu; Yue-wen Chen; Guo-feng Tan (Food Chemistry, 2025)

Multicomponent additive-mediated interfacial engineering enables highly stable lithium-ion pouch cells under harsh working conditions - Zhi Zhang; Shuai Gao; Haipeng Guo; Yi Wang; Tong Liao; Dongsheng Zhang; Wenqi Zhu; Maohui Bai; Chaochao Fu; Xing Ou; Jixue Shen (Chemical Engineering Journal, 2025)

Single-cell omics: experimental workflow, data analyses and applications - Fengying Sun; Haoyan Li; Dongqing Sun; Shaliu Fu; Lei Gu; Xin Shao; Qinqin Wang; Xin Dong; Bin Duan; Feiyang Xing; Jun Wu; Minmin Xiao; et al. (Science China Life Sciences, 2025)

Whole-genome mutagenesis of whiteleg shrimp (Litopenaeus vannamei) by ARTP and analysis of its mutational characteristics - Qiang Fu; Jingxin Zhou; Sheng Luan; Kun Luo; Baolong Chen; Jiawang Cao; Xupeng Li; Qun Xing; Jie Kong; Xianhong Meng (Aquaculture, 2024)

Precipitation versus dissolution at the phosphorus and Solanum nigrum L. root exudate interface: Implications for lead rebound in rhizosphere soils - Jingwei Zhang; Hao Shi; Yiquan Xing; Yixin Chen; Jiacheng Li; Haojie Fu; Guoqing Dai; Zhaojie Cui; Lei Wang; Xinxin Li (Science of The Total Environment, 2024)

Hydrogeochemical differences drive distinct microbial community assembly and arsenic biotransformation in unconfined and confined groundwater of the geothermal system - Ling-Zhi Zhang; Shi-ping Xing; Fu-Yi Huang; Wei Xiu; Jonathan R. Lloyd; Christopher Rensing; Yi Zhao; Huaming Guo (Science of The Total Environment, 2024)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

Distinct accumulation patterns, translocation efficiencies, and impacts of nano-fertilizer and nano-pesticide in wheat through foliar versus soil application - Erkai He; Xing Li; Xueqing Xu; Zhuozhong Fu; Ana Romero-Freire; Hao Qiu (Journal of Hazardous Materials, 2024)

Simultaneous removal of PAHs and heavy metals from soil by combining electrokinetic-assisted delivery of persulfate and ultrasound activation - Dongdong Wen; Caihong Gao; Yajun Zhang; Enlu Xing; Jiabin Yao; Rongbing Fu (Journal of Hazardous Materials, 2024)

Comparison of the short- and long-term effects of zinc ions on the anaerobic mesophilic co-digestion of food waste and waste activated sludge: Digester performance, antibiotic resistance gene reduction and the microbial community - Bao-Shan Xing; Yi-Meng Su; Yu-Lin Fu; Yi-Fan Wu; Chen-Hao Yan; Xiaochang C. Wang; Yu-You Li; Rong Chen (Journal of Hazardous Materials, 2024)

The dynamic patterns of critical ecological areas in the Yellow River Basin are driven primarily by climate factors but threatened by human activities - Yunlong Zhang; Zhengyuan Zhao; Jie Zhu; Yuelu Wang; Haoyue Wang; Bojie Fu; Yihe Lü; Wei Jiang; Ying Hu; Xing Wu (Journal of Environmental Management, 2024)

Metabolomics integrated with mass spectrometry imaging reveals novel action of tetramethylpyrazine in migraine - Ziwei Xing; Yu Chen; Junren Chen; Cheng Peng; Fu Peng; Dan Li (Food Chemistry, 2024)

Structural properties and antioxidant capacity of different aminated starch-phenolic acid conjugates - Feng-Kun An; Meng-Yun Li; Hai-Lu Luo; Xing-Long Liu; Zhen Fu; Min-Hong Ren (Food Chemistry, 2024)

Environmental Persistent Free Radicals in highly polluted soils and the association with polycyclic aromatic compounds - Yongqiang Zhang; Yousong Zhou; Hanchen Wang; Kai Xiao; Zhihan Luo; Yaojie Li; Ran Xing; Ke Jiang; Donglei Fu; Wenxin Liu; Shu Tao; Guofeng Shen (Environmental Research, 2024)

Molecular characterization of major oxidative potential active species in ambient PM2.5: Emissions from biomass burning and ship exhaust - Chunbo Xing; Yaling Zeng; Xin Yang; Antai Zhang; Jinghao Zhai; Baohua Cai; Shao Shi; Yin Zhang; Yujie Zhang; Tzung-May Fu; Lei Zhu; Huizhong Shen; et al. (Environmental Pollution, 2024)

Combining APCS-MLR model to evaluate the distribution and sources of rare earth elements in a large catchment - Xinyi Fu; Xing Chen; Fazhi Xie; Zihan Zhang; Tianqi Ma; Xiang Dong; Liugen Zheng (Environmental Pollution, 2024)

PFOS sub-chronic exposure selectively activates Aβ clearance pathway to improve the cognitive ability of AD mice - Haijing Zhang; Chao Zhang; Qin Wang; Wenliang Fu; Weiwei Xing; Peng Jin; Haowei Wu; Yuanjing Bu; Dongqun Xu; Donggang Xu (Environmental Pollution, 2024)

Synergistically enhanced heterogeneous activation of dissolved oxygen for aqueous carbamazepine degradation over S(III) coupled with siderite - Yuning Fang; Fei Wang; Hongze Fang; Zhaosheng Lei; Wei Song; Caixia Fu; Xing Du; Zhihong Wang; Zhiwei Zhao (Environmental Pollution, 2024)

Clay composition heterogeneity in sediments from mountainous catchments with contrasting bedrock lithology in SE China coast - Ling Wang; Xing Jian; Haowei Mei; Xiaotian Shen; Hanjing Fu (CATENA, 2024)

PRDX1 Interfering Peptide Disrupts Amino Acids 70–90 of PRDX1 to Inhibit the TLR4/NF-κB Signaling Pathway and Attenuate Neuroinflammation and Ischemic Brain Injury - Xiang-Yu Ma; Cheng-yu Qi; Xing-yi Xu; Hui Li; Chang-Dong Liu; Xiang-Ru Wen; Yan-Yan Fu; Yan Liu; Jia Liang; Cheng-Yu Huang; Dan-Dan Li; Yan Li; et al. (Molecular Neurobiology, 2024)

A general three-component polarimetric SAR interferometry target decomposition - Shuaifeng Hu; Qinghua Xie; J. David Ballester-Berman; Qi Dou; Xing Peng; Youjun Wang; Haiqiang Fu; Jianjun Zhu (Advances in Space Research, 2024)

Effect of nitrogen and phosphorus level on growth, development and biochemical composition of Neoporphyra haitanensis conchocelis - Xiujuan Wang; Xing Ren; Hui Zhu; Donghuan Fu; Peng Zhang; Yubo Wu (New Zealand Journal of Marine and Freshwater Research, 2024)
Neoporphyra haitanensis is an important economic alga. A 3 × 2 factorial layout containing three nitrogen levels (1, 5, 10 mg L −1 ) and two phosphorus levels (1, 5 mg L −1 ) were designed to examine the effect of nitrogen and phosphorus levels on physiological responses of N. haitanensis conchocelis during growth phase (trial I) and development phase (trial II). In trial I, a higher phosphorus concentration inhibited the relative growth rate of N. haitanensis conchoceli at each nitrogen level. Contents of chlorophyll a and carotenoids were higher at high nitrogen level. Contents of phospholipids were higher at high phosphorus concentration at 5 mg L −1 nitrogen level. In trial II, high phosphorus concentration increased the formation of conchosporangia at 1 mg L −1 nitrogen level. Higher contents of phycoerythrin and phycocyanin were at high nitrogen level. Higher contents of phospholipids were at high phosphorus concentration at 1 mg L −1 nitrogen level. Higher contents of triglycerides were at low nitrogen level both in trial I and II. These results indicated that high nitrogen level increased the contents of pigment. High phosphorus level favoured the formation of conchosporangia and deposition of phospholipids. These results lay the groundwork for research into mechanism of growth and development of N. haitanensis .

The critical role of electron donating rate of pyrogenic carbon in mediating the degradation of phenols in the aquatic environment - Liang Zeng; Sizhe Yang; Quan Chen; Wang Fu; Min Wu; Patryk Oleszczuk; Bo Pan; Baoshan Xing (Water Research, 2024)

Optimal operation of CCHP system with duality operation strategy considering hydrogen trading and carbon capture - Zhi-Feng Liu; Ya-He Huang; Qing Kang; Ze-Qi Li; Jing Lu; Rui-Zheng Gu; Xing-Fu Luo; Xiao-Rui Chen; You-Yuan Liu; Yu Tang; Liang Guo (Sustainable Cities and Society, 2024)

Urbanization impacts on evapotranspiration change across seven typical urban agglomerations in China - Wanqiu Xing; Zhiyu Feng; Xin Cao; Jianyu Fu; Weiguang Wang (Science of The Total Environment, 2024)

Detrital muscovite 40Ar/39Ar geochronology and provenance of Cenozoic deposits in the Qaidam basin, northern Tibetan Plateau and comparison with detrital zircon and apatite records - Shuhuai Ye; Xing Jian; Ling Fu; Wei Zhang; Xiaotian Shen; Ping Guan (Marine and Petroleum Geology, 2024)

Soil moisture retrieval over agricultural fields with machine learning: A comparison of quad-, compact-, and dual-polarimetric time-series SAR data - Changchang Lv; Qinghua Xie; Xing Peng; Qi Dou; Jinfei Wang; Juan M. Lopez-Sanchez; Jiali Shang; Lei Chen; Haiqiang Fu; Jianjun Zhu; Yang Song (Journal of Hydrology, 2024)

Determining the evaporation and evolution of surface water in a large catchment using isotopes and multiple models - Xiang Dong; Xing Chen; Fazhi Xie; Liugen Zheng; Zihan Zhang; Xinyi Fu; Tianqi Ma (Journal of Contaminant Hydrology, 2024)

Characterization of a short-term processing technology of black garlic with low 5-HMF content - Jun Liu; Jing Li; Shihao Ge; Xiaoyu Fu; Jiamin Zhu; Mengnan Wang; Yanrong Wang; Xiaoxiao Huang; Xinzheng Qin; Yixian Tu; Jun Xing; Chao Ma; et al. (Food Control, 2024)

Poly(ethylene oxide)-based composite solid electrolyte modified by Li7La3Zr2O12 inorganic filler with grafted imidazolium-based ionic liquids functional groups - Yanhua Zhang; Yumei Xiao; Zijun Tang; Liuli Zou; Qingting Liu; Xudong Fu; Xing Xiang; Jiadong Deng (Chemical Engineering Journal, 2024)

Integrated transcriptomic and metabolomic analysis reveals the underlying mechanisms for male reproductive toxicity of polystyrene nanoplastics in mouse spermatocyte-derived GC-2spd(ts) cells - Hang Han; Zhen Zhang; Bo Xu; Liyang Ding; Hong Yang; Tiantian He; Xing Du; Xiuying Pei; Xufeng Fu (Toxicology in Vitro, 2024)

Cytotoxic steroidal glycosides from Paris rugosa rhizomes - Jian-Ke Jia; Jun Yang; Xing-Zhi Yang; Ji-Feng Luo; Xiao-Yan Duan; Ying-Li Yang; Jin-Fu Wan; Yue-Hu Wang (Phytochemistry Letters, 2024)

Using salted egg white in steamed bread: Impact on functional and structural characteristics - Adil M. Abker; Zhijun Xia; Gan Hu; Xiaowen Fu; Yixin Zhang; Yongguo Jin; Meihu Ma; Xing Fu (Food Chemistry, 2024)

Egg white fermentation by lactic acid bacteria: Effects on gel characteristics and preliminary investigation of suitable genera - Xiaohui Lv; Haobo Jin; Xing Fu; Jiran Lv; Rong Chen; Manqi Shi; Yunzheng Lv; Yongguo Jin (Food Bioscience, 2024)

Research progress of protein fibrils: A review of formation mechanism, characterization and applications in the food field - Yixin Zhang; Xiaohui Lv; Adil M. Abker; Deog-Hwan Oh; Jihan Mohamed Kassem; Mohamed Salama; Xing Fu (Food Hydrocolloids, 2024)

Self-standing COF-MOF composite sandwich membranes with high permeability for dye separation - Bingbing Chen; Xing Gao; Xiaojiao Hou; Yuanlin Fu; Yuhang Li; Fuqiang Fan; Tieqiang Wang; Fanbao Meng; Yu Fu; Junchao Ma (Desalination, 2024)

Enhanced uranium extraction using a nanostructured photothermal hydrogel membrane - Zhipeng Liu; Kai Feng; Xinle Zhang; Linhui Fu; Jiaxin Ren; Rui Gao; Shihao Ding; Wenqian Xing; Yiwen Li; Jiaji Cheng; Qiang Li; Jiang Gong; et al. (Chemical Engineering Journal, 2024)

Atorvastatin exerts a preventive effect against steroid-induced necrosis of the femoral head by modulating Wnt5a release - Junfeng Wu; Tao Chen; Minghang Zhang; Xing Li; Rongkun Fu; Jianzhong Xu; Andreas Nüssler; Chenxi Gu (Archives of Toxicology, 2024)

Allergenicity, assembly and applications of ovalbumin in egg white: a review - Bin Ma; Xing Fu; Ping Zhu; Zhaoxin Lu; Jiafeng Niu; Fengxia Lu (Critical Reviews in Food Science and Nutrition, 2024)

Refractory COD removal from bio-treated paper wastewater using powdered activated coke adsorption technology with ozonation regeneration: Performance and molecular insights - Ying An; Huimin Zhang; Li Fu; Chen Tang; Mengyu Wang; Yunxin Xing; Fuqiang Xu; Xiao Sun; Zhen Zhou (Chemosphere, 2024)

Stereo visual-inertial localization algorithm for orchard robots based on point-line features - Xing Xu; Jinming Liang; Jianying Li; Guang Wu; Jieli Duan; Mohui Jin; Han Fu (Computers and Electronics in Agriculture, 2024)

Ecotoxicological assessment, oxidative response, and enzyme activity disorder of the rotifer Brachionus asplanchnoidis exposed to a toxic cocktail of spent lithium-ion battery leachate - Yi-fan Feng; Yu Zhang; Run-jia Yang; Si-qi Li; Xiao-jie Liu; Cui Han; Yi-fu Xing; Jia-xin Yang (Journal of Hazardous Materials, 2024)

Degradation of sulfamethazine in coastal aquaculture tailwater by Na2S2O4@iron-electrode electrooxidation combined with ceramic membrane process - Wei Song; Yuning Fang; Hongze Fang; Deming Gu; Xing Du; Sen Xu; Caixia Fu; Yu Zhou; Zhihong Wang (Environmental Pollution, 2024)

Direct numerical simulations of internal flow inside deformed bubble by phase-field-based lattice Boltzmann method - Huahai Zhang; Shaotong Fu; Xing Xiang; Weite Su; Zhenjiang Guo; Limin Wang (Chemical Engineering Journal, 2024)

Failure Mechanism and Active Support of Large-Span Tunnel with Unstable Rock Blocks: A Case Study - Wen-xu Li; Zhi-chao Xue; Le-min Liu; Shuo Zhang; Fu-yong Zhang; Wei-teng Li; Xin-jie Man; Xing Shao; Ming-fa Wang; Chang-an Zhang (Geotechnical and Geological Engineering, 2024)

Disrupting the Dorsolateral Prefrontal Cortex Attenuates the Difference in Decision-Making for Altruistic Punishment Between the Gain and Loss Contexts - Yingjie Liu; Hongbo Xing; Yuan Gao; Xiaohua Bian; Xin Fu; Baxter DiFabrizio; He Wang (Brain Topography, 2024)

Genetic analysis of Discogobio (Cypriniformes: Cyprinidae) in the Central Yunnan Basin: Effects of geological events and conservation perspectives - Xing‐Jin Che; Yuan‐Wei Zhang; An‐Li Wu; Li‐Mei Zhang; Xiao‐Fu Pan; Mo Wang; Jun‐Xing Yang; Xiao‐Ai Wang (Zoologica Scripta, 2024)
Geological events can have a major effect on the genetic structure and differentiation of fish populations. The relative importance of key geological events on the distribution and genetic structure of endemic fish of the genus Discogobio in the Yunnan–Guizhou Plateau has not yet been evaluated. Studies of the phylogeography of Discogobio fishes could provide insights into spatial and temporal changes in their population size, dispersal history, and extent of geographical isolation, and the data acquired in such studies can be used to aid their conservation. Here, we used single‐nucleotide polymorphisms (SNP) to characterize the phylogeography of Discogobio fishes. Our analysis supports the endemicity of Discogobio . However, Discogobio samples from different regions contained multiple ancestral components, including admixed and diversified genetic components. This might stem from polymorphism of the ancestors themselves or the infiltration of genes caused by hybridization between Discogobio species. We estimated that the most recent common ancestor (MRCA) of Discogobio fish in the Central Yunnan Basin was approximately 4.63–3.83 million years ago (Ma). We also inferred that the evolution of Discogobio in the Central Yunnan Basin was closely related to the expansion and contraction of the lake basin around 2.59–0.13 Ma. We proposed measures that could be implemented to conserve remaining populations and their corresponding habitats to prevent further declines and preserve the biodiversity of this unique genus.

Improved permeability in ceramsite@powdered activated carbon (PAC)-MnOx coupled gravity-driven ceramic membrane (GDCM) for manganese and ammonia nitrogen removal with intermittent short-term vertical aeration - Wei Song; Zhitian Peng; Jiawan Li; Xiaokai Wang; Caixia Fu; Xing Du; Ke Kuang; Ziyuan Wang; Zhihong Wang; Zhiwei Zhao (Journal of Hazardous Materials, 2024)

Responses of physico-chemical properties and CH4 adsorption/desorption behaviors of diverse rank coal matrices to microwave radiation - Xing Tang; Xuexiang Fu; Jie Zou; Dengfeng Zhang (Gas Science and Engineering, 2024)

Transglutaminase cross-linking ovalbumin-flaxseed oil emulsion gels: Properties, microstructure, and performance in oxidative stability - Yue Tian; Shurui Wang; Jiran Lv; Meihu Ma; Yongguo Jin; Xing Fu (Food Chemistry, 2024)

Rapid and sensitive aptamer-linked immunosorbent assay with aptamer-templated silver nanoparticles for detection of aflatoxin B1 in medicinal and edible food - Dai Lu; Xing Tian; Yixiong Yang; Zixuan Fu; Qian Zhao; Bin Li; Wei Wang (Food Bioscience, 2024)

Optimal nitrogen management increases nitrogen use efficiency of direct-seeded double-season rice using ultrashort-duration cultivars - Guodong Yang; Hongshun Xiang; Yifan Fu; Changzai Zhou; Xinyu Wang; Shen Yuan; Xing Yu; Shaobing Peng (Field Crops Research, 2024)

Molecular-level insight into the origin-dependent adsorption fractionation of dissolved organic matter on ferrihydrite in aquatic environment: Implications for carbon sink in eutrophic lakes - Chengyu Suo; Wensi Zhao; Shasha Liu; Rui Fu; Yi Ren; Yue Qiu; Yuxin Zhang; Zhongqi He; Baoshan Xing; Fengchang Wu (Chemical Engineering Journal, 2024)

Experimental Study on an Innovative Method for Pre-split Blasting to Protect Withdrawal Roadways - Jun Yang; Xing Wu; Qiang Fu; Shilin Hou; Hongxu Song; Hongyu Jin; Yuxuan Liu; Jiarui Tang (Rock Mechanics and Rock Engineering, 2024)

Thermal History of Cambrian Burgess Shale-Type Deposits: New Insights from the Early Cambrian Chengjiang and Qingjiang Fossils of South China - Yuheng Qiao; Linhao Cui; Guangyuan Xing; Dongjing Fu; Chao Chang; Robert Gaines; Xingliang Zhang (Journal of Earth Science, 2024)

Upward soil arching effect under unloading: mechanism, theory and engineering application - Ren-Peng Chen; Han-Lin Wang; Xiang-Shen Fu; Fanyan Meng; Qi-Wei Liu; Xing-Tao Lin (Transportation Geotechnics, 2024)

Nanobubbles improve peroxymonosulfate-based advanced oxidation: High efficiency, low toxicity/cost, and novel collaborative mechanism - Jun Bo Zhang; Jia Jie Zou; Chaomeng Dai; Jiajun Hu; Xueji You; Min-tian Gao; Jixiang Li; Rongbing Fu; Yalei Zhang; Kah Hon Leong; Xing Song Xu (Journal of Hazardous Materials, 2024)

Effects of freeze-thaw cycles on the quality of Hot-dry noodles: From the moisture, starch, and protein characteristics - Liuyu Wan; Xiude Wu; Peng Xu; Yaonan Xing; Shensheng Xiao; Yang Fu; Xuedong Wang (Food Chemistry, 2024)

A NIR-II quantum dot-assisted dual-color imaging strategy enables simultaneous tracking of two subtypes of extracellular vesicles in vivo - Xing-Chi Liu; He-Jing Zhang; Rui Xu; Jing Liu; Hou-Fu Xia; Qi-Hui Xie; Zhi-Quan Tian; Zi-Li Yu; Gang Chen (Chemical Engineering Journal, 2024)

Molecular Role of Melatonin in Regulating Abiotic Stress Adaptive Responses in Plants - Li Jia; Xing Liu; Yishou Huang; Fan Sun; Xinyu Zhang; Wenxuan Fu; Liping Huang (Journal of Plant Growth Regulation, 2024)

Unveiling toxicity profile for food risk components: A manually curated toxicological databank of food-relevant chemicals - Xing-Xing Shi; Fan Wang; Zhi-Zheng Wang; Guang-Yi Huang; Min Li; Jesus Simal-Gandara; Ge-Fei Hao; Guang-Fu Yang (Critical Reviews in Food Science and Nutrition, 2024)

Bi-2-(2-phenethyl)chromone derivatives from agarwood of Aquilaria filaria in the Philippines - Hong-Run Yang; Hao Wang; Pei Wang; Fang-Zheng Liu; Hong-Xing Chai; Cai-Hong Cai; Li Yang; Jing-Zhe Yuan; Bei Jiang; Wen-Li Mei; Hao-Fu Dai (Phytochemistry, 2024)

Variable climatic conditions dominate decreased wetland vulnerability on the Qinghai‒Tibet Plateau: Insights from the ecosystem pattern-process-function framework - Zhengyuan Zhao; Bojie Fu; Yihe Lü; Ting Li; Lei Deng; Yuelu Wang; Da Lü; Yi Wang; Xing Wu (Journal of Cleaner Production, 2024)

Preparation of Fe3O4 magnetic nanomaterials for the enrichment of phosvitin phosphopeptides - Shuze Ren; Songming Li; Mahmoud Abou-Elsoud; Rui Cui; Xing Fu; Xi Huang (Food Bioscience, 2024)

Polydopamine-immobilized lysozyme for the fabrication of antibacterial films and its application in the preservation of fresh pork - Aichun Lv; Guangsen Fan; Zhe Yang; Xinyue Zhang; Muhammad Moeid Khan; Xing Fu (Food Packaging and Shelf Life, 2024)

Analysis of historical evolution characteristics and collapse process on July 18, 2023, of a dangerous rock mass at Guanyinyan in Baoxing County, Sichuan Province, China - Xing Wang; Xiaodong Fu; Kai Wu; Haifeng Ding; Wenjie Du; Qian Sheng; Jian Chen (Landslides, 2024)

Damage constitutive model for soft rocks and its experimental verification on silty mudstone considering cyclic rock‒water interactions - Xiao-Wei Yu; Hong-Yuan Fu; Ling Zeng; Jie Liu; Xing-Yu Qiu (Bulletin of Engineering Geology and the Environment, 2024)

Source-specific probabilistic health risk assessment of heavy metals in surface water of the Yangtze River Basin - Xing Chen; Xinyi Fu; Guolian Li; Jiamei Zhang; Haibin Li; Fazhi Xie (Science of The Total Environment, 2024)

Novel method for identifying the heaviest QED atom - Jing-Hang Fu; Sen Jia; Xing-Yu Zhou; Yu-Jie Zhang; Cheng-Ping Shen; Chang-Zheng Yuan (Science Bulletin, 2024)

Salt dynamic changes between seawater and phreatic brine in muddy tidal flats under tidal influence - Yufeng Zhang; Xiaoteng Xiao; Zengbing Sun; Bingxiao Lei; Mingbo Li; Xiujun Guo; Tengfei Fu; Cheng Xing (Journal of Hydrology, 2024)

Graphitic carbon nitride nanosheets mitigate cadmium toxicity in L. by promoting cadmium retention in root and improving photosynthetic performance - Kai Xu; Yunyu Guo; Chenghua Xing; Ronglong Fu; Bin Zou; Rongchuan Liu; Luyi Cai; Jianfang Yan; Xi-Lin Wu; Miaozhen Cai (Journal of Environmental Sciences, 2024)

The investigation of wetting and agglomerating mechanism of short-chain fluorocarbon surfactant suppressing coal dust from macro and molecular scales - Xuhan Ding; Kai Wang; Zhenmin Luo; Qingyun Fu; Tianting Wang; Qian Xu; Xin Yi; Renkun Dai; Haipeng Jiang; Zhenqiang Xing (Chemical Engineering Journal, 2024)

Refining granite generation by interrogation of zircon and monazite U-Th-Pb and Hf/Nd-O isotopes - Xing Zhang; Yuanbao Wu; Bin Fu; Wenxiang Zhang; Long Li; Guangyan Zhou; Rui Li; Zhaochu Hu; Yu He; Zhengwei Qin (Chemical Geology, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

Association between polycyclic aromatic hydrocarbons and infertility in U.S. women: National Health and Nutrition Examination Survey 2013–2016 - Xiaomei Wu; Suixiang Wang; Xiaoxiao Lin; Huanzhu Liang; Yingying Wu; Yuxuan Tan; Huixian Zeng; Qian Chen; Jie Wang; Feng Huang; Ziang Guo; Puyi Xing; et al. (Reproductive Toxicology, 2024)

Effect of anions on sonochemical degradation of PPCPs and their DBPs formation potential - Yu-qiong Gao; Ke-xuan Li; Qian Zeng; Fu-xiang Tian; Ze-ning Fan; Gang-yi Xing; Nai-yun Gao (Journal of Water Process Engineering, 2024)

Efficient trimethoprim removal via cooperation of radical and non-radical pathways in UV/peroxymonosulfate: Kinetics, mechanisms and disinfection by-products-associated risks - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Juan Wang; Yu-Qiong Gao; Dong-Su Bi; Bo Wang; Xing-Yan Mu; Xiao-Jun Hu (Journal of Environmental Chemical Engineering, 2024)

Synergistic effects of aluminum doping and amino functionalization to enhance adsorption capacity of ultrathin-nanosheet-assembled calcium silicate hydrate architectures for effective removal of Pb2+ and Cu2+ from aqueous solution - Yujin Xing; Shicheng Liu; Wenzhong Wang; Yujie Liang; Junli Fu; Qing Zhou; Lijuan Wang; Shimeng Huang (Journal of Environmental Chemical Engineering, 2024)

Structural characteristics and antioxidant activity of Chinese giant salamander enzymatic hydrolysate-glucose conjugates induced by ultrasound Maillard reaction - Jing-jing Fu; Fan-yu He; Xing-tong Zhu; Zhen Wang; Yang-na Huang; Jin-xiu Yu; Zhi-ping Wu; Yue-wen Chen (Food Bioscience, 2024)

Nrf2-mediated ferroptosis of spermatogenic cells involved in male reproductive toxicity induced by polystyrene nanoplastics in mice - Xufeng Fu; Hang Han; Hong Yang; Bo Xu; Wenjie Dai; Ling Liu; Tiantian He; Xing Du; Xiuying Pei (Journal of Zhejiang University-SCIENCE B, 2024)

Toxic effects of microplastics and nitrite exposure on intestinal histology, digestion, immunity, and microbial community of shrimp Litopenaeus vannamei - Yi-fu Xing; Xuan-yi Zhu; Jian-hua Huang; Yu-xiu Nan; Ya-fei Duan; Jia-song Zhang (Marine Pollution Bulletin, 2024)

Soil freeze–thaw cycles affect spring phenology by changing phenological sensitivity in the Northern Hemisphere - Ting Li; Bojie Fu; Yihe Lü; Chenjun Du; Zhengyuan Zhao; Fangfang Wang; Guangyao Gao; Xing Wu (Science of The Total Environment, 2024)

Chuaria Walcott from the early Cambrian Qingjiang biota: a taxon persisted for billions of years - Rui-Yun Li; Dong-Jing Fu; Xing-Liang Zhang (Palaeoworld, 2024)

Behavioral and molecular response of the insect parasitic nematode Steinernema carpocapsae to plant volatiles - Peng-hua Bai; Jin-Ping Yu; Rui-rui Hu; Qian-wen Fu; Hai-chao Wu; Xing-yue Li; Guo-hao Zu; Bao-sheng Liu; Yu Zhang (Journal of Invertebrate Pathology, 2024)

Source apportionment and predictable driving factors contribute to antibiotics profiles in Changshou Lake of the Three Gorges Reservoir area, China - Yue Mu; Bobin Tang; Xian Cheng; Yuanhang Fu; Weibin Huang; Jing Wang; Dewang Ming; Liangshu Xing; Jinzhong Zhang (Journal of Hazardous Materials, 2024)

The impact of ultrasound treatment combined with flaxseed gum on the foaming properties of egg white - Yue Tian; Jingzi Pi; Jiran Lv; Yinxia Chen; Meihu Ma; Xing Fu (Food Hydrocolloids, 2024)

A comparative study on the degradation of carbamazepine by UV laser/chlorine and UV laser/PS processes: Performance and mechanisms - Qi Fu; Xing-Xing Wang; Huan He; Tian-Yang Zhang; Jian Lu; Meng-Yuan Xu; Renjie Pan; Tong-Cheng Cao; Mohamed Gamal El-Din; Bin Xu (Chemical Engineering Journal, 2024)

Mechanical interlocking induced emission in two-dimensional covalent organic frameworks - Ruo-Meng Zhu; Wang-Kang Han; Yong Liu; Jia-Xing Fu; Jing-Dong Feng; Jinfang Zhang; Huan Pang; Zhi-Guo Gu (Chemical Engineering Journal, 2024)

Feeding experience on hairy vetch induces a loss of host-specific adaptation to maize and changes in the gut microbiota communities of the fall armyworm - Lin Ma; Dao-Tong Wang; Qi-Lin Ren; Lei Zhang; Yun-Xia Cheng; Xing-Fu Jiang (Journal of Pest Science, 2024)

Effectiveness of a novel composite filler to enhance phosphorus removal in constructed wetlands - Kaiyuan Gu; Xiongwei Yang; Xing Yan; Chenggang He; Wanchong Mao; Fengkun Xiao; Xiaomeng Wei; Xinxi Fu; Yonglei Jiang (Environmental Science and Pollution Research, 2024)

A Data-Driven Approach to Identify Major Air Pollutants in Shanghai Port Area and Their Contributing Factors - Xing-Zhou Li; Zhong-Ren Peng; Qingyan Fu; Qian Wang; Jun Pan; Hongdi He (Journal of Marine Science and Engineering, 2024)
Air pollution is a growing concern in metropolitan areas worldwide, and Shanghai, as one of the world’s busiest ports, faces significant challenges in local air pollution control. Assessing the contribution of a specific port to air pollution is essential for effective environmental management and public health improvement, making the analysis of air pollution contributions at a selected port in Shanghai a pertinent research focus. This study aims to delve into the distribution patterns of atmospheric pollutants in port areas and their influencing factors, utilizing a data-driven approach to unveil the relationship between pollution sources and dispersion. Through a comparative analysis of pollution levels in the port’s interior, surrounding regions, and urban area concentrations, we ascertain that carbon monoxide (CO) and nitric oxide (NO) are the primary pollutants in the port, with concentrations significantly exceeding those of the surrounding areas and urban area levels. These two pollutants exhibit an hourly pattern, with lower levels during the day and higher concentrations at night. Employing a random forest model, this study quantitatively analyzes the contribution rates of different factors to pollutant concentrations. The results indicate that NO concentration is primarily influenced by operational intensity and wind speed, while CO concentration is mainly affected by meteorological factors. Further, an orthogonal experiment reveals that maintaining daily operational vehicle numbers within 5000 effectively controls NO pollution, especially at low wind speeds. Additionally, humidity and temperature exhibit similar trends in influencing NO and CO, with heightened pollution occurring within the range of 75% to 90% humidity and 6 °C to 10 °C temperature. Severe pollution accumulates under stagnant wind conditions with wind speeds below 0.2 m/s. The results help to explore the underlying mechanisms of port pollution further and use machine learning for early pollution prediction, aiding timely warnings and emission reduction strategy formulation.

Metabolic coupling of arsenic, carbon, nitrogen, and sulfur in high arsenic geothermal groundwater: Evidence from molecular mechanisms to community ecology - Ling-Zhi Zhang; Shi-ping Xing; Fu-Yi Huang; Wei Xiu; Christopher Rensing; Yi Zhao; Huaming Guo (Water Research, 2024)

Development of trenchless rehabilitation for underground pipelines from an academic perspective - Dongmin Xi; Hongfang Lu; Xing Zou; Yun Fu; Houming Ni; Baicheng Li (Tunnelling and Underground Space Technology, 2024)

Impact of antioxidants on PM2.5 oxidative potential, radical level, and cytotoxicity - Yixiang Wang; Chunbo Xing; Baohua Cai; Wenhui Qiu; Jinghao Zhai; Yaling Zeng; Antai Zhang; Shao Shi; Yujie Zhang; Xin Yang; Tzung-May Fu; Huizhong Shen; et al. (Science of The Total Environment, 2024)

Lanostane triterpenoids from the fruiting bodies of Ganoderma amboinense - Li Yang; Guan-Hai Dong; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Jia-Ju Lu; You-Gen Wu; Hao-Fu Dai; You-Xing Zhao (Phytochemistry, 2024)

Two unprecedented 2-(2-phenethyl)chromone dimers from red soil agarwood of Aquilaria crassna - Hong-Xing Chai; Hao Wang; Jun Zeng; Wen-Hua Dong; Wen-Li Mei; Bei Jiang; Wei Li; Hao-Fu Dai (Phytochemistry Letters, 2024)

Gravity driven membrane bioreactor simulates the effect of permeable brick on pollution reduction of rainwater runoff in Low Impact Development (LID) - Xiao Ma; Zhenhao Liang; Jiawan Li; Caixia Fu; Wei Song; Xing Du; Yu Zhou; Feng Liu (Journal of Water Process Engineering, 2024)

Deciphering the thick filaments assembly behavior of myosin as affected by enzymatic deamidation - Yanyun Zhang; Wenyan Fu; Dongmei Liu; Xing Chen; Peng Zhou (Food Chemistry, 2024)

Heterostructure nanozymes with sustainable tumor microenvironment regulation and reinforced hyperthermia-responsive catalytic activities for orchestrated osteosarcoma catalytic therapy - Xing Zhang; Xiang Li; Mengying Fu; Jeremiah Ong'achwa Machuki; Wandong Wang; Liang Wu; Qun Zhao; Ning Xin; Lei Hua; Fenglei Gao (Chemical Engineering Journal, 2024)

Dietary Nanometer Selenium Enhances the Selenium Accumulation, Nutrient Composition and Antioxidant Status of Paramisgurnus dabryanus spp. - Jianhua Chen; Shaopeng Xing; Haixin Xu; Honggeng Zhu; Huiyun Fu; Haihua Wang; Fugui Li; Ming Zhu (Fishes, 2024)
Selenium, an essential trace element, exerts beneficial effects on aquatic animals when present in suitable concentrations. This study investigates the effect of dietary nanometer selenium (Nano-Se) on the muscle selenium accumulation, nutrient composition, and antioxidant ability of Paramisgurnus dabryanus spp. Nano-Se was supplemented in the basal diets at levels of 0, 0.1, 0.2, 0.4, and 0.6 mg/kg. Three hundred fish, averaging 5.21 ± 0.06 g, were randomly divided into five groups and fed the experimental diet for 6 weeks. Fish with a dietary Nano-Se supplement of 0.2 mg/kg exhibited activities of SOD, GSH-Px, AKP, and CAT in the liver, which were significantly higher (p

Detrital zircon geochronology and provenance of Cenozoic deposits in the Qaidam basin, northern Tibetan plateau: An overview with new data, implications and perspectives - Xing Jian; Ping Guan; Ling Fu; Wei Zhang; Xiaotian Shen; Hanjing Fu; Ling Wang (Marine and Petroleum Geology, 2024)

Catalytic activation of percarbonate with synthesized carrollite for efficient decomposition of bisphenol S: Performance, degradation mechanism and toxicity assessment - Shicheng Liu; Sitong Liu; Huabin Chen; Yujin Xing; Wenzhong Wang; Lijuan Wang; Yujie Liang; Junli Fu; Chen Zhang (Journal of Hazardous Materials, 2024)

Plasma-catalyzed combined dynamic wave scrubbing: A novel method for highly efficient removal of multiple pollutants from flue gas at low temperatures - Wei Xie; Tao Zhu; Bo Yuan; Shunjiang Fu; Zhishan Mao; Zefu Ye; Zhujun Zhu; Xing Zhang (Journal of Hazardous Materials, 2024)

Deploying photovoltaic arrays in degraded grasslands is a promising win-win strategy for promoting grassland restoration and resolving land use conflicts - Bin Zhang; Ruohui Zhang; You Li; Shiwen Wang; Minghui Zhang; Fu Xing (Journal of Environmental Management, 2024)

Salt transport dynamics across the sediment-underground brine interface driven by tidal hydrology and benthic crab burrowing in muddy tidal flats - Tengfei Fu; Yufeng Zhang; Xiujun Guo; Cheng Xing; Xiaoteng Xiao; Bingxiao Lei; Zengbing Sun; Mingbo Li (Estuarine, Coastal and Shelf Science, 2024)

Characterization and fine mapping of a maize lesion mimic mutant (Les8) with enhanced resistance to Curvularia leaf spot and southern leaf blight - Jiankun Li; Tianyuan Fan; Ying Zhang; Ye Xing; Mengyao Chen; Ying Wang; Jie Gao; Na Zhang; Jinjun Tian; Chenyang Zhao; Sihan Zhen; Junjie Fu; et al. (Theoretical and Applied Genetics, 2024)

Metabolic diversity shapes vegetation-enhanced methane oxidation in landfill covers: Multi-omics study of rhizosphere microorganisms - Shangjie Chen; Wenting Fu; Limin Cai; Zhilin Xing; Baozhong Mou; Yongqiong Wang; Shan Wu; Tiantao Zhao (Waste Management, 2023)

Integrative application of biochar and arbuscular mycorrhizal fungi for enhanced chromium resistance in Medicago sativa - Jinglong Li; Gengxue Fu; Shuping Xing; Baodong Chen; Songlin Wu; Haiyan Feng; Guang Yang; Yaoyu Zhou; Xin Zhang (Science of The Total Environment, 2023)

Biochar establishing syntrophic partnership between exoelectrogens to facilitate extracellular electron transfer - Gaojun Wang; Lu Chen; Yao Xing; Changxi Sun; Peng Fu; Qian Li; Rong Chen (Science of The Total Environment, 2023)

Diverse indole-diterpenoids with protein tyrosine phosphatase 1B inhibitory activities from the marine coral-derived fungus Aspergillus sp. ZF-104 - Fei Zhang; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Qing-Yun Ma; Lu-Ting Dai; Li-Man Zhou; Hao-Fu Dai; Fan-Dong Kong; Du-Qiang Luo; You-Xing Zhao (Phytochemistry, 2023)

Identification of critical ecological areas using the ecosystem multifunctionality-stability-integrity framework: A case study in the Yellow River basin, China - Yunlong Zhang; Yuelu Wang; Bojie Fu; Yihe Lü; Xiao Liang; Yingying Yang; Ruiming Ma; Shengjun Yan; Xing Wu (Journal of Environmental Management, 2023)

Quality deterioration of frozen dough bread during terminal freezing and thawing: From the insight of moisture and starch properties - Hongyan Liu; Yaonan Xing; Dezheng Liu; Qian Yang; Shensheng Xiao; Yang Fu; Xuedong Wang (Food Bioscience, 2023)

Ultrasound-assisted glycation on ovalbumin fibrosis: A novel, efficient immobilization for lipase - Yixin Zhang; Jihong Liu; Jiran Lv; Qiuyu Li; Deog-Hwan Oh; Xing Fu (Food Bioscience, 2023)

Experimental Research on the Preparation of Composite Adsorbent Based on Iron Manganese Mud to Remove Sb(III) from Water - Yashu Yuan; Pengyu Cao; Liwei Zhang; Li Zhang; Di Luo; Xing Jin; Jinxiang Fu (Water, Air, & Soil Pollution, 2023)

Failure history, mechanism, and recent run-out reproduction of the Xinhua Village landslide triggered by the 2022 Ms 6.1 Lushan earthquake - Wenjie Du; Kai Wu; Xiaodong Fu; Qian Sheng; Jian Chen; Xing Wang (Landslides, 2023)

CDK6 is a novel predictive and prognosis biomarker correlated with immune infiltrates in multiple human neoplasms, including small cell lung carcinoma - Guo-Sheng Li; Zhi-Guang Huang; Dong-Ming Li; Yu-Lu Tang; Jin-Hua Zheng; Lin Yang; Yue Feng; Jun-Xi Peng; Jing-Xiao Li; Yu-Xing Tang; Neng-Yong Zeng; Mei-Hua Jin; et al. (Functional & Integrative Genomics, 2023)

Modeling of errors resulting from vehicle motions for CHZII mobile gravimeter and its performance verification during marine surveys - Hai-bo Tu; Jian-gang He; Ming Hu; Xing-hui Liang; Lei-jun Liu; Qin-qin Dong; Sun-jun Liu; Hui Zhang; Yong-tao Fu; Jun-jian Lang; Heng Sun; Lin-tao Liu (Applied Geophysics, 2023)

Enhancing effect of cobalt phthalocyanine dispersion on electrocatalytic reduction of CO2 towards methanol - Tianxiang Guo; Xilai Wang; Xiaodong Xing; Zhixiang Fu; Changxin Ma; Alemayehu Hailu Bedane; Lingfeng Kong (Environmental Science and Pollution Research, 2023)

Light grazing reduces gaseous nitrogen emissions from temperate grassland soils during freeze‒thaw cycles: An intact core incubation study - Chenjun Du; Xing Wu; Fangfang Wang; Rui Wang; Xunhua Zheng; Yihe Lü; Bojie Fu (Soil Biology and Biochemistry, 2023)

Lanostane triterpenoids with anti-proliferative and PTP1B/α-glucosidase inhibitory activities from the fruiting bodies of Ganoderma calidophilum - Li Yang; Ting-Ting Zhang; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Jia-Ju Lu; Zhi-Fang Yu; Hao-Fu Dai; You-Xing Zhao (Phytochemistry, 2023)

Scene-aware refinement network for unsupervised monocular depth estimation in ultra-low altitude oblique photography of UAV - Kailong Yu; Hao Li; Linjie Xing; Tao Wen; Die Fu; Yang Yang; Chengjiang Zhou; Rong Chang; Shan Zhao; Lin Xing; Haicheng Bai (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Salt tide affecting algae-laden micropolluted surface water treatment and membrane performance based on BDD electro-oxidation coupled with ceramic membrane process - Xing Du; Bingxuan Li; Zhongjian Zhuang; Ke Kuang; Wei Song; Dachao Lin; Caixia Fu; Zhihong Wang (Environmental Research, 2023)

Precise classification and regional delineation of maturity groups in soybean cultivars across China - Wenwen Song; Luping Liu; Shi Sun; Tingting Wu; Haiyan Zeng; Shiyan Tian; Bincheng Sun; Wenbin Li; Lijun Liu; Shuming Wang; Han Xing; Xin’an Zhou; et al. (European Journal of Agronomy, 2023)

Bias in sediment chemical weathering intensity evaluation: A numerical simulation study - Hanjing Fu; Xing Jian; Hanqing Pan (Earth-Science Reviews, 2023)

Age, provenance and tectonic setting of the Tonian–Cryogenian clastic successions in the northwest Bikou terrane, NW Yangtze Block, Central China - Zhidong Gu; Xing Jian; Guixia Liu; Xiaotian Shen; Hanjing Fu; Xiufen Zhai; Hua Jiang (Precambrian Research, 2023)

Catalytic degradation of benzene at room temperature over FeN4O2 sites embedded in porous carbon - Hui Ding; Lingxiao Xue; Jiahao Cui; Yongqiang Wang; Dan Zhao; Xing Zhi; Rui Liu; Jianfeng Fu; Shejiang Liu; Bingfeng Fu; Jiahui Shi; Ximeng Xu; et al. (Journal of Hazardous Materials, 2023)

Light-driven sustainable enhancement of Cr(VI) reduction via the combination of Cr(VI)-reducing bacteria, Paraclostridium bifermentans with CdS nanoparticles - Yilin Le; Xing He; Mengnan Liu; Xue Liu; Shidong Zhou; Rongrong Xie; Yu Fu; Huilei Wang; Jianzhong Sun (Journal of Environmental Chemical Engineering, 2023)

Abundance, community and driving factor of nitrifiers in western China plateau - Dongdan Yuan; Chaochen Fu; Lei Zheng; Qiuyang Tan; Xue Wang; Yuzi Xing; Haoming Wu; Qi Tian (Environmental Research, 2023)

Degradation of ofloxacin by high-efficiency almond shell-based biochar via peroxymonosulfate activation: A study of the effect of pore structure - Yi-meng Huang; Fu-zhi Huang; Bing-jun Dong; Xiao-qiang Cao; Ya-nan Shang; Xing Xu (Chemical Engineering Journal, 2023)

Soil and water conservation effects of different types of vegetation cover on runoff and erosion driven by climate and underlying surface conditions - Yanting Hu; Fu Zhang; Zhuzhu Luo; Nasem Badreldin; Glenn Benoy; Zisheng Xing (CATENA, 2023)

Study on the Method of Pressure Relief and Energy Absorption for Protecting Roadway Under Thick and Hard Roof - Qiang Fu; Jun Yang; Hongxu Song; Xing Wu; Yuxuan Liu; Xingjian Wei (Rock Mechanics and Rock Engineering, 2023)

Peptide YY inhibits transcription and replication of hepatitis B virus by suppressing promoter/enhancer activity - Xiaolun Xu; Weiping Zhou; Xing Tian; Zhongjia Jiang; Xuanhe Fu; Jun Cao; Ye Sun; Biao Yang; Xueqian Li; Yanting Li; Chunmeng Zhang; Guangyan Liu (Virus Genes, 2023)

Telomere length, oxidative stress and their links with growth and survival in a lizard facing climate warming - Qiong Zhang; Xing-Zhi Han; Pablo Burraco; Xin Hao; Li-Wei Teng; Zhen-Sheng Liu; Fu-Shun Zhang; Wei-Guo Du (Science of The Total Environment, 2023)

Energy-oriented control retrofit for existing HVAC system adopting data-driven MPC – Methodology, implementation and field test - Bao Yue; Bing Su; Fu Xiao; Anbang Li; Kehua Li; Shen Li; Rui Yan; Qiuzhuang Lian; Ao Li; Yuanyang Li; Xing Fang; Xingang Liang (Energy and Buildings, 2023)

Two lanostane triterpenoids with α -glucosidase inhibitory activity from the fruiting bodies of Ganoderma weberianum - De Xian Kong; Qing Yun Ma; Li Yang; Qing Yi Xie; Chun Ying Deng; Hao Fu Dai; Yan Hua; You Xing Zhao (Natural Product Research, 2023)

Decoupled local climate and chemical weathering intensity of fine-grained siliciclastic sediments from a paleo-megalake: An example from the Qaidam basin, northern Tibetan Plateau - Ling Wang; Xing Jian; Hanjing Fu; Wei Zhang; Fei Shang; Ling Fu (Sedimentary Geology, 2023)

Urinary Amino-PAHs in relation to diesel engine emissions and urinary mutagenicity - Junfeng (Jim) Zhang; Yuxin Zheng; Roel Vermeulen; Xing (Lucy) Liu; Yufei Dai; Wei Hu; Linchen He; Yan Lin; Dianzhi Ren; Huawei Duan; Yong Niu; Jun Xu; et al. (International Journal of Hygiene and Environmental Health, 2023)

A yolk-shell Pd decorated Au@CeO2 with Schottky junction for long-lived charge separation and bandgap optimization to enhance sonodynamic therapy - Weiwei Sheng; Xiunan Wu; Mengying Fu; Cheng Chen; Zetai Bai; Mengyuan Xing; Chun Zhang; Lijuan Chong; Jingjing Li; Fenglei Gao (Chemical Engineering Journal, 2023)

Dual-emitting cellulose nanocrystal hybrid materials with circularly polarized luminescence for anti-counterfeiting labels - Lingxiao Xing; Guihua Li; Yaping Sun; Xu Wang; Zaiwu Yuan; Yingjuan Fu; Menghua Qin (Carbohydrate Polymers, 2023)

Graph neural network-based spatio-temporal indoor environment prediction and optimal control for central air-conditioning systems - Jing Zhang; Fu Xiao; Ao Li; Tianyou Ma; Kan Xu; Hanbei Zhang; Rui Yan; Xing Fang; Yuanyang Li; Dan Wang (Building and Environment, 2023)

Microecological health assessment of water environment and sediment based on metagenomics: a case study of Guixi River in Chongqing, China - Xia Su; Fu-qing Xu; Shang-jie Chen; Fang Gou; Yun-chun Shi; Zhi-lin Xing; Ren-qing Peng; Ying-ying Deng; Ten Zhang; Juan Xiong; Tian-tao Zhao (Environmental Monitoring and Assessment, 2023)

Polyacrylonitrile fiber with light-driven intelligent reversible and switchable wettability as an environmental benign solid base for biodiesel production - Huan-Xing Zhou; Qing-Qing Sun; Zhong-Qiu Liu; Jie-Wen Duan; Tingjun Fu; Yujing Liu; Anguo Ying (Journal of Cleaner Production, 2023)

Effect of boron and nitrogen modulation in metal atoms anchoring on flower-like carbon superstructure for efficient ammonia electrosynthesis - Yanchao Zhao; Shuo Zhang; Cong Han; Qian Lu; Qiuju Fu; Huimin Jiang; Lingzhi Yang; Yanlong Xing; Qiuju Zheng; Jianxing Shen; Liting Yan; Xuebo Zhao (Chemical Engineering Journal, 2023)

Designing Er3+ Single-doped ternary sulfide for highly efficient upconversion luminescence under 1550 nm excitation - Hong Wang; Zhe He; Ke Cai; Limin Wei; Yang Xu; Yao Fu; Mingming Xing; Ying Tian (Chemical Engineering Journal, 2023)

QTL mapping and identification of candidate genes for cold tolerance at the germination stage in wild rice - Ying-Hua Pan; Bao-Xuan Nong; Lei Chen; Xing-Hai Yang; Xiu-Zhong Xia; Zong-Qiong Zhang; Dong-Jin Qing; Ju Gao; Cheng-Cui Huang; Dan-Ting Li; Guo-Fu Deng (Genes & Genomics, 2023)

Response of soil fungal community to chromium contamination in agricultural soils with different physicochemical properties - Chuning Ji; Jiu Huang; Xuemeng Zhang; Guang Yang; Shuping Xing; Wei Fu; Zhipeng Hao; Baodong Chen; Xin Zhang (Science of The Total Environment, 2023)

Two new α-pyrone derivatives from sponge-derived fungus Curvularia sp. ZYX-Z-4 - Qing-Hui Yan; Li Yang; Qing-Yun Ma; Qing-Yi Xie; Hao-Fu Dai; Ying Fu; You-Xing Zhao (Phytochemistry Letters, 2023)

Miocene Moschidae (Mammalia, Ruminantia) from the Linxia Basin (China) connect Europe and Asia and show an early evolutionary diversity of a today monogeneric family - Manuela Aiglstorfer; Shi-Qi Wang; Jie Cheng; Luda Xing; Jiao Fu; Bastien Mennecart (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Gradient removal of Si and P impurities from phosphogypsum and preparation of anhydrous calcium sulfate - Mingshun Wang; Xing Yuan; Wenyan Dong; Qiang Fu; Xianquan Ao; Qianlin Chen (Journal of Environmental Chemical Engineering, 2023)

Leaky Gut Plays a Critical Role in the Pathophysiology of Autism in Mice by Activating the Lipopolysaccharide-Mediated Toll-Like Receptor 4–Myeloid Differentiation Factor 88–Nuclear Factor Kappa B Signaling Pathway - Fang Li; Haoran Ke; Siqi Wang; Wei Mao; Cexiong Fu; Xi Chen; Qingqing Fu; Xiaori Qin; Yonghua Huang; Bidan Li; Shibing Li; Jingying Xing; et al. (Neuroscience Bulletin, 2023)
Increased intestinal barrier permeability, leaky gut, has been reported in patients with autism. However, its contribution to the development of autism has not been determined. We selected dextran sulfate sodium (DSS) to disrupt and metformin to repair the intestinal barrier in BTBR T + tf/J autistic mice to test this hypothesis. DSS treatment resulted in a decreased affinity for social proximity; however, autistic behaviors in mice were improved after the administration of metformin. We found an increased affinity for social proximity/social memory and decreased repetitive and anxiety-related behaviors. The concentration of lipopolysaccharides in blood decreased after the administration of metformin. The expression levels of the key molecules in the toll-like receptor 4 (TLR4)–myeloid differentiation factor 88 (MyD88)–nuclear factor kappa B (NF-κB) pathway and their downstream inflammatory cytokines in the cerebral cortex were both repressed. Thus, “leaky gut” could be a trigger for the development of autism via activation of the lipopolysaccharide-mediated TLR4–MyD88–NF-κB pathway.

Nitrogen Addition Changes the Allelopathic Effects of the Root Leachate from the Invasive Weed Stellera chamaejasme L. on a Dominant Grass in the Songnen Grassland - Chen Chen; Fu Xing; Zhuo Li; Ruohui Zhang (Journal of Plant Biology, 2023)

OrMKK3 Influences Morphology and Grain Size in Rice - Ying Hua Pan; Li Jun Gao; Yun Tao Liang; Yan Zhao; Hai Fu Liang; Wei Wei Chen; Xing Hai Yang; Dong Jin Qing; Ju Gao; Hao Wu; Juan Huang; Wei Yong Zhou; et al. (Journal of Plant Biology, 2023)

Convergence and divergence emerging in climatic controls of polynomial trends for northern ecosystem productivity over 2000–2018 - Wenxin Zhang; Hongxiao Jin; Sadegh Jamali; Zheng Duan; Mousong Wu; Youhua Ran; Jonas Ardö; Lars Eklundh; Anna Maria Jönsson; Huaiwei Sun; Guojie Hu; Xiaodong Wu; et al. (Science of The Total Environment, 2023)

Tree mycorrhizal type controls over soil water-extractable organic matter quantity and biodegradation in a subtropical forest of southern China - Hui-Min Chen; Fu-Xi Shi; Jia-Wen Xu; Xing-Ping Liu; Rong Mao (Forest Ecology and Management, 2023)

Mechanistic studies of polyphenols reducing the trypsin inhibitory activity of ovomucoid: Structure, conformation, and interactions - Rui Cui; Shengnan Ji; Minquan Xia; Xing Fu; Xi Huang (Food Chemistry, 2023)

Modification of ovalbumin by the enzymatic method: Consequences for foaming characteristics of fibrils - Jingzi Pi; Jia Wang; Jiran Lv; Yongguo Jin; Deog-Hwan Oh; Xing Fu (Food Hydrocolloids, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A Novel Method of Combined Deep Hole Blasting for Gob-Side Roadway Protection - Jun Yang; Qiang Fu; Yubing Gao; Xing Wu; Xu Chang; Changjiang Li (Rock Mechanics and Rock Engineering, 2023)

Gold-silver alloy hollow nanoshells-based lateral flow immunoassay for colorimetric, photothermal, and SERS tri-mode detection of SARS-CoV-2 neutralizing antibody - Tianyu Zhao; Penghui Liang; Jiaqi Ren; Jinyue Zhu; Xianning Yang; Hongyu Bian; Jingwen Li; Xiaofeng Cui; Chunhui Fu; Jinyan Xing; Congying Wen; Jingbin Zeng (Analytica Chimica Acta, 2023)

Rayleigh surface wave inversion based on an improved Archimedes optimization algorithm - Zhen-An Yao; Ren Wang; Fu Yu; Long-Feng Chen; Hong-Xing Li; Xiang-Teng Wang; Pan Wang (Applied Geophysics, 2023)

Cooling water intake system safety analysis based on impingement probability - Xiaocheng Fu; Fenglei Du; Xiaodong Huang; Juan Pei; Zhenglou Zhang; Xiaofeng Xing; Xiang Pu (Frontiers in Marine Science, 2023)
Invasion or aggregation of marine organisms in cooling water intake systems (CWIS) has gradually become an important problem affecting the safety of nuclear power plants with environmental and climate changes. In this study, a 3-dimensional numerical model (TELEMAC-3D) was used to determine the impingement probability in a typical nuclear power plant with a once-through cooling system, and the effect on CWIS safety. The factors controlling impingement probability were also analyzed. Results show that (1) impingement probability decreased rapidly with an increase in distance from the CWIS. In addition, the distance of the impingement effect of a nuclear power plant with six units was mainly within 1 km of the CWIS. (2) Impingement probability increased with water withdrawal, and as distance to the CWIS increased, the increase in probability increased. (3) Generally, an increase in tide strength led to a decrease impingement probability. (4) Near the CWIS, the impingement probabilities of areas upstream or downstream of the CWIS along the tidal flow direction were much higher than those not in those areas. (5) An increase in water depth significantly reduced impingement probability. When the water depth of the CWIS increased from 5 m to 15 m, impingement probability was reduced up to 30%. Based on the above findings, the following suggestions were made to minimize the impingement effects on CWIS safety: first, the CWIS of coastal nuclear power plants should be set in an area with low aquatic biomass, strong tides, deep water, and few surface species within the range of 1 km, and second, the amount of cooling water withdrawal or velocity should be reduced as much as possible.

Two new indole alkaloids isolated from a mangrove-derived fungus Colletotrichum sp. HD-1 - Dan He; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Hong-Juan Zhu; Hao-Fu Dai; You-Gen Wu; Dong-Mei Yang; You-Xing Zhao (Phytochemistry Letters, 2023)

Benchmarking high performance HVAC Rule-Based controls with advanced intelligent Controllers: A case study in a Multi-Zone system in Modelica - Xing Lu; Yangyang Fu; Zheng O'Neill (Energy and Buildings, 2023)

Mechanistic insights into efficient photocatalytic H2O2 production of 2D/2D g-C3N4/In2S3 photocatalyst by tracking charge flow direction - Huabin Chen; Yujin Xing; Shicheng Liu; Yujie Liang; Junli Fu; Lijuan Wang; Wenzhong Wang (Chemical Engineering Journal, 2023)

Modulation of non-covalent wet adhesion and cohesion via proximally immobilized non-lysine pair structure - Pengxu Wang; Qing Liu; Wenliang Fu; Chao Zhang; Guiling Cai; Weiwei Xing; Hongliang Dai; Hongya Geng; Donggang Xu (Chemical Engineering Journal, 2023)

Salvia miltiorrhiza polysaccharide and its related metabolite 5-methoxyindole-3-carboxaldehyde ameliorate experimental colitis by regulating Nrf2/Keap1 signaling pathway - Yu-Ping Fu; Xi Peng; Chao-Wen Zhang; Quan-Xing Jiang; Cen-Yu Li; Berit Smestad Paulsen; Frode Rise; Chao Huang; Bin Feng; Li-Xia Li; Xing-Fu Chen; Ren-Yong Jia; et al. (Carbohydrate Polymers, 2023)

New hydrous phases in the Al2O3-SiO2-H2O system under the mantle transition zone conditions - Baoyun Wang; Jin Liu; Suyu Fu; Pu Xiao; Li Li; Xing Ding; Wansheng Xiao (Science China Earth Sciences, 2023)

Mechanical deterioration effect and damage evolution characteristics of soft sandstone with different water-immersed heights under uniaxial compression - Han-Dong Liu; Shuai Liu; Hai-Ning Liu; Jia-Xing Chen; Zhi-Guo Xia; Ju-Yun Zhai; Yun-You Fu (Bulletin of Engineering Geology and the Environment, 2023)

Seasonal variation of driving factors of ambient PM2.5 oxidative potential in Shenzhen, China - Chunbo Xing; Yixiang Wang; Xin Yang; Yaling Zeng; Jinghao Zhai; Baohua Cai; Antai Zhang; Tzung-May Fu; Lei Zhu; Ying Li; Xinming Wang; Yanli Zhang (Science of The Total Environment, 2023)

Resource use efficiencies, environmental footprints and net ecosystem economic benefit of direct-seeded double-season rice in central China - Xing Yu; Le Xu; Shen Yuan; Guodong Yang; Hongshun Xiang; Yifan Fu; Jianliang Huang; Shaobing Peng (Journal of Cleaner Production, 2023)

Degradation of levofloxacin in wastewater by photoelectric and ultrasonic synergy with TiO2/g-C3N4@AC combined electrode - Zihao Xing; Zijing Wang; Wenhui Chen; Manying Zhang; Xiaofei Fu; Yong Gao (Journal of Environmental Management, 2023)

A hybrid deep learning model for regional O3 and NO2 concentrations prediction based on spatiotemporal dependencies in air quality monitoring network - Cui-lin Wu; Hong-di He; Rui-feng Song; Xing-hang Zhu; Zhong-ren Peng; Qing-yan Fu; Jun Pan (Environmental Pollution, 2023)

Linking trait network to growth performance of submerged macrophytes in response to ammonium pulse - Guixiang Yuan; Xiaoyao Tan; Peiqin Guo; Ke Xing; Zhenglong Chen; Dongbo Li; Sizhe Yu; Hui Peng; Wei Li; Hui Fu; Erik Jeppesen (Water Research, 2023)

Targeted metabolomics analysis identified the role of FOXA1 in the change in glutamate-glutamine metabolic pattern of BaP malignantly transformed 16HBE cells - Yunkun Xing; Zhiyu Liu; Xue Ma; Chuan Zhou; Yu Wang; Biyun Yao; Juanling Fu; Yanmin Qi; Peng Zhao (Toxicology and Applied Pharmacology, 2023)

The potential for carbon sequestration by afforestation can be limited in dryland river basins under the pressure of high human activity - Yingying Yang; Yihe Lü; Bojie Fu; Xing Wu; Shudong Wang; Taixia Wu (Science of The Total Environment, 2023)

Seasonal divergence of evapotranspiration sensitivity to vegetation changes – A proportionality-hypothesis-based analytical solution - Jianyu Fu; Weiguang Wang; Bingjun Liu; Yang Lu; Wanqiu Xing; Mingzhu Cao; Shifeng Zhu; Tiesheng Guan; Jia Wei; Zefeng Chen (Journal of Hydrology, 2023)

Remediation of lindane contaminated soil by fluidization-like dielectric barrier discharge - Shuo Zhang; Zhen Liu; Shuran Li; Shihao Zhang; Hui Fu; Xuan Tu; Wenyi Xu; Xing Shen; Keping Yan; Ping Gan; Xiujuan Feng (Journal of Hazardous Materials, 2023)

The effects of high-intensity ultrasound and oil types on the physicochemical properties of egg white protein emulsions - Adil M. Abker; Shurui Wang; Shihan Chen; Meihu Ma; Xing Fu (Journal of Food Engineering, 2023)

Selenium alleviates cadmium-induced mitophagy through FUNDC1-mediated mitochondrial quality control pathway in the lungs of sheep - Shixuan Lin; Fan Yang; Mingwen Hu; Jing Chen; Guiping Chen; Aiming Hu; Xiong Li; Danghua Fu; Chenghong Xing; Zhiwei Xiong; Yunhui Wu; Huabin Cao (Environmental Pollution, 2023)

A novel method of creating machine learning-based time series meta-models for building energy analysis - Guangchen Li; Wei Tian; Hu Zhang; Xing Fu (Energy and Buildings, 2023)

Facilitating both anionic and cationic redox processes in Na-rich layered cathode materials by heteroatomic doping - Ziwei Chen; Maolin Yang; Zhongyuan Huang; Yanda Fu; Zhefeng Chen; Simo Li; Minzhi zhan; Rui Wang; Mihai Chu; Rui Qi; Xing Cheng; Zhewen Ma; et al. (Chemical Engineering Journal, 2023)

Porewater dissolved inorganic carbon released due to artificial sediment scouring in the Yellow River - Xing-yu Huang; Dong Zhang; Fu-shun Wang; Zhi-qi Zhao; Ai-chun Chen; Jun-wen Zhang; Cong Zhang; Li Wu; Yu-hong Li; Bing-juan Ma; Qi-yan Feng (Applied Geochemistry, 2023)

CRISPR-based DNA methylation editing of NNT rescues the cisplatin resistance of lung cancer cells by reducing autophagy - Chi Xu; Shuyun Jiang; Xingyu Ma; Zeyong Jiang; Youguang Pan; Xiang Li; Liying Zhang; Hao Zhou; Shen Chen; Xiumei Xing; Liping Chen; Wenfan Fu; et al. (Archives of Toxicology, 2023)

Wastewater treatment by anodic oxidation in electrochemical advanced oxidation process: Advance in mechanism, direct and indirect oxidation detection methods - Rui Fu; Peng-Shuang Zhang; Yuan-Xing Jiang; Lin Sun; Xu-Hui Sun (Chemosphere, 2023)

Insights into the role of the microbial community lifestyle strategies in variations of the dissolved organic matter molecular composition along an effluent-dominated river - Xing Wang; Minda Yu; Xiaosong He; Jing Su; Beidou Xi; Yuanyuan Sun; Xuemei Fu; Yaojia Wang; Mingxia Zheng (Chemosphere, 2023)

Water microecology is affected by seasons but not sediments: A spatiotemporal dynamics survey of bacterial community composition in Lake Changshou—The largest artificial lake in southwest China - Ai-ling Chen; Fu-qing Xu; Xia Su; Fu-pan Zhang; Wan-chao Tian; Shang-jie Chen; Fang Gou; Zhi-lin Xing; Jin-xin Xiang; Juan Li; Tian-tao Zhao (Marine Pollution Bulletin, 2023)

RETRACTED: Recent progresses, challenges, and opportunities of carbon-based materials applied in heavy metal polluted soil remediation - Tianhong Fu; Baige Zhang; Xing Gao; Shihao Cui; Chung-Yu Guan; Yujin Zhang; Bangxi Zhang; Yutao Peng (Science of The Total Environment, 2023)

An assessment of L-band surface soil moisture products from SMOS and SMAP in the tropical areas - Hongliang Ma; Xiaojun Li; Jiangyuan Zeng; Xiang Zhang; Jianzhi Dong; Nengcheng Chen; Lei Fan; Morteza Sadeghi; Frédéric Frappart; Xiangzhuo Liu; Mengjia Wang; Huan Wang; et al. (Remote Sensing of Environment, 2023)

Enhanced degradation performance and mechanisms of decabromodiphenylether in homogeneous system of Fe3+ activated dithionite - Wei Song; Zhuoyue Wang; Ji Li; Xiaolei Zhang; Caixia Fu; Xing Du; Ningjie Wang; Qi Song; Zhihong Wang; Pankaj Bhatt; Shunni Zhu (Journal of Cleaner Production, 2023)

Discovery of a fossil dwarf antelope outside of Africa and its implications for the late Miocene ecosystem in the northeast margin of the Tibetan Plateau - Shi-Qi Wang; Jimin Sun; Chunxiao Li; Shi-Jie Li; Jiao Fu; Qigao Jiangzuo; Luda Xing; Rong Yang (Gondwana Research, 2023)

Selective luminescent sensing of teflubenzuron and oxyfluorfen by a resorcin[4]arene-based metal-organic framework - Bing-Bing Lu; Zhi-Xin Xing; Yong-Shun Bao; Fei Ye; Ying Fu (Chemical Engineering Journal, 2023)

Synthesis of amorphous Nickel-Cobalt hydroxides with high areal capacitance by one-step electrodeposition using polymeric additive - Wenxuan Hu; Huakang Fu; Lu Chen; Xing Wu; Biao Geng; Yanling Huang; Yifei Xu; Miao Du; Guorong Shan; Yihu Song; Ziliang Wu; Qiang Zheng (Chemical Engineering Journal, 2023)

Chitin and chitin-based biomaterials: A review of advances in processing and food applications - Jiran Lv; Xiaohui Lv; Meihu Ma; Deog-Hwan Oh; Zhengqiang Jiang; Xing Fu (Carbohydrate Polymers, 2023)

Extraction and spatiotemporal changes of open-pit mines during 1985–2020 using Google Earth Engine: A case study of Qingzhou City, Shandong Province, China - Liu Ruifeng; Yuan Kai; Li Xing; Liu Xiaoli; Zhao Xitao; Guo Xiaocheng; Fu Juan; Cao Shixin (Environmental Monitoring and Assessment, 2023)

Lysobacter lactosilyticus sp. nov., a Novel β-Galactosidase Producing Bacterial Strain Isolated from Farmland Soil Applied with Amino Acid Fertilizer - Xiang Wang; Yu-Huan Wang; Hong-Xing Yang; Shao-Chuang Chuang; Chun-Fu Zhou; Xing Yu; Hao Zhang (Current Microbiology, 2023)

Mass movement of a long-runout catastrophic landslide on Aug. 21, 2020, in Hanyuan County of China - Xing-Yu Yuan; Zheng-Feng Chen; Wen-Xi Fu; Yue Liu; Hong-Fu Zhou; Fei Ye (Bulletin of Engineering Geology and the Environment, 2022)

Caffeine alleviates acute liver injury by inducing the expression of NEDD4L and deceasing GRP78 level via ubiquitination - Xing-Wang Hu; Xiang-Min Li; Ai-Min Wang; Yong-Ming Fu; Fang-Jie Zhang; Feng Zeng; Li-Ping Cao; Hui Long; Ying-Hui Xiong; Ji Xu; Jia Li (Inflammation Research, 2022)

Analysis and estimation of nonpoint source pollution under different land use in Anjiagou watershed, Gansu, China - Yanting Hu; Zisheng Xing; Fu Zhang; Qing Tian; Nasem Badreldin; Jinmei Zhao (Environmental Science and Pollution Research, 2022)

Fine mapping of powdery mildew and stripe rust resistance genes Pm5V/Yr5V transferred from Dasypyrum villosum into wheat without yield penalty - Ruiqi Zhang; Chuntian Lu; Xiangru Meng; Yali Fan; Jie Du; Runran Liu; Yigao Feng; Liping Xing; Petr Cápal; Kateřina Holušová; Jaroslav Doležel; Yiwei Wang; et al. (Theoretical and Applied Genetics, 2022)

Evaluating the Response of a Tunnel Subjected to Strike-Slip Fault Rupture in Conjunction with Model Test and Hybrid Discrete–Continuous Numerical Modeling - Cui Zhen; Li Jian-he; Fu Xing-wei; Sheng Qian; Zhou Guang-xin; Ma Ya-li-na; Wang Tian-qiang (Rock Mechanics and Rock Engineering, 2022)

miR-517b-3p promotes the progression of portal vein tumor thrombus via activating Wnt/β-catenin signaling pathway in hepatocellular carcinoma - Rui-Sheng Ke; Kun-Zhai Huang; De-sheng Bao; Jing-Rui Yang; Hua-xiang Wang; Li-Zhi Lv; Yi Jiang; Zhao-Hui Liu; Fu-Xing Zhang (Molecular Biology Reports, 2022)

Soil moisture regulates warming responses of autumn photosynthetic transition dates in subtropical forests - Yongshuo H. Fu; Xinxi Li; Shouzhi Chen; Zhaofei Wu; Jianrong Su; Xing Li; Shuaifeng Li; Jing Zhang; Jing Tang; Jingfeng Xiao (Global Change Biology, 2022)
Autumn phenology plays a key role in regulating the terrestrial carbon and water balance and their feedbacks to the climate. However, the mechanisms underlying autumn phenology are still poorly understood, especially in subtropical forests. In this study, we extracted the autumn photosynthetic transition dates (APTD) in subtropical China over the period 2003–2017 based on a global, fine‐resolution solar‐induced chlorophyll fluorescence (SIF) dataset (GOSIF) using four fitting methods, and then explored the temporal–spatial variations of APTD and its underlying mechanisms using partial correlation analysis and machine learning methods. We further predicted the APTD shifts under future climate warming conditions by applying process‐based and machine learning‐based models. We found that the APTD was significantly delayed, with an average rate of 7.7 days per decade, in subtropical China during 2003–2017. Both partial correlation analysis and machine learning methods revealed that soil moisture was the primary driver responsible for the APTD changes in southern subtropical monsoon evergreen forest (SEF) and middle subtropical evergreen forest (MEF), whereas solar radiation controlled the APTD variations in the northern evergreen‐broadleaf deciduous mixed forest (NMF). Combining the effects of temperature, soil moisture and radiation, we found a significantly delayed trend in APTD during the 2030–2100 period, but the trend amplitude (0.8 days per decade) was much weaker than that over 2003–2017. In addition, we found that machine learning methods outperformed process‐based models in projecting APTD. Our findings generate from different methods highlight that soil moisture is one of the key players in determining autumn photosynthetic phenological processes in subtropical forests. To comprehensively understand autumn phenological processes, in‐situ manipulative experiments are urgently needed to quantify the contributions of different environmental and physiological factors in regulating plants' response to ongoing climate change.

Performances of Evaporation and Desiccation Cracking Characteristics for Attapulgite Soils - Ting Yang; Xuguang Xing; Wei Fu; Xiaoyi Ma (Journal of Soil Science and Plant Nutrition, 2022)

Influence of Tidal Cycles on Embryonic Rotation, Hatching and Emergence of Mangrove Horseshoe Crab, Carcinoscorpius rotundicauda - Yang Kuang; Kian Ann Tan; Yijian Fu; Xin Yang; Peng Xu; Wenquan Zhen; Xueping Wang; Xing Huang; Junhua Zhu; Chun-Chieh Wang; Kit Yue Kwan (Journal of Ocean University of China, 2022)

High Microplastic Contamination in Juvenile Tri-Spine Horseshoe Crabs: A Baseline Study of Nursery Habitats in Northern Beibu Gulf, China - Xueping Wang; Hoi Shing Lo; Yijian Fu; Zhou Wu; Danmei Qin; Xing Huang; Jingmin Zhu; Siu Gin Cheung; Kit Yue Kwan (Journal of Ocean University of China, 2022)

Deformation characteristics and thresholds of the Tanjiawan landslide in the Three Gorges Reservoir Area, China - Fu-ling Zhang; Mao-lin Deng; Qing-lin Yi; Shu-qiang Lu; Wei-jun Zheng; Hai-feng Huang; Xing Zhu (Journal of Mountain Science, 2022)

Rapid onset hazards, fault-controlled landslides and multi-method emergency decision-making - Fu-yun Guo; Xing-min Meng; Tian-jun Qi; Tom Dijkstra; Jarsve Kristine Thorkildsen; Dong-xia Yue; Guan Chen; Yi Zhang; Xiao-dong Dou; Peng-qing Shi (Journal of Mountain Science, 2022)

A new picrotoxane-type sesquiterpene from Dendrobium nobile Lindl - Pei Wang; Xin Chen; Cai-Hong Cai; Fan-Dong Kong; Sheng-Zhuo Huang; Jing-Zhe Yuan; Xing-Lian Xu; Wen-Li Mei; Hao-Fu Dai (Natural Product Research, 2022)

Involvement of Opioid Peptides in the Analgesic Effect of Spinal Cord Stimulation in a Rat Model of Neuropathic Pain - Fu-Jun Zhai; Song-Ping Han; Tian-Jia Song; Ran Huo; Xing-Yu Lan; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2022)

A novel anticancer property of Lycium barbarum polysaccharide in triggering ferroptosis of breast cancer cells - Xing Du; Jingjing Zhang; Ling Liu; Bo Xu; Hang Han; Wenjie Dai; Xiuying Pei; Xufeng Fu; Shaozhang Hou (Journal of Zhejiang University-SCIENCE B, 2022)

Antifungal sesquiterpenes with post-harvest anthracnose control effect on bananas from the fungus Fusarium lateritium - Junjie Zhu; Ping Xiong; Ziyang Li; Jiazhong Li; Longsheng Lin; Xing Fu; Yuxuan Huang; Yahong Xiong; Chunyuan Li (Natural Product Research, 2022)

Artificial modification of Earth’s radiation belts by ground-based very-low-frequency (VLF) transmitters - Binbin Ni; Man Hua; Xudong Gu; Song Fu; Zheng Xiang; Xing Cao; Xin Ma (Science China Earth Sciences, 2022)

Neuroprotective effect of aldose reductase knockout in a mouse model of spinal cord injury involves NF-κB pathway - Fu-xin Han; Rui Zhang; Xin-xing Yang; Shan-bo Ma; Shi-jie Hu; Bing Li (Experimental Brain Research, 2022)

Comparative evaluation of energy consumption and emissions in the life cycle of extended-range and battery electric vehicles - Yisong Chen; Yang Yang; Yunxiang Xing; Ying Cao; Haibo Xu; Pei Fu (Arabian Journal of Geosciences, 2022)

miR-181b-5p Promotes the Progression of Cholangiocarcinoma by Targeting PARK2 via PTEN/PI3K/AKT Signaling Pathway - Zhe-Long Jiang; Fu-Xing Zhang; Hong-Liang Zhan; He-Jun Yang; Si-Yu Zhang; Zhao-Hui Liu; Yi Jiang; Li-Zhi Lv; Rui-Sheng Ke (Biochemical Genetics, 2022)

Effect of nano-CaCO3 on the physical and mechanical properties of analogue to silty mudstone materials - Hong-Yuan Fu; Shuang-Xing Qi; Zhen-Ning Shi; Ling Zeng; Hong-Bin Zhao (Arabian Journal of Geosciences, 2021)

Molecular identification and phylogenetic analysis of fungal pathogens isolated from diseased fish in Xinjiang, China - Yan‐Zhen Zhang; Qing‐Dian Han; Long‐Wei Fu; Yong‐Xing Wang; Zhi‐Hai Sui; Yun‐Guo Liu (Journal of Fish Biology, 2021)
The outbreaks of fungal diseases in cultured fish have been severe in recent years, which is harmful to the healthy and sustainable development of fish farming. In this study, an investigation was conducted for significant fungal infections of 12 species of fish in four regions in Xinjiang, China, to understand the distribution of local fish fungal pathogens. Twenty‐six fungal strains with pathogenicity were isolated, and the challenge experiment showed that eight strains from Changji area had high infection rate to fish eggs. Based on internal transcribed spacer sequence data and molecular analysis, the 26 strains were classified into nine different species of six fungal genera. Phylogenetic analysis showed that all strains were divided into two clades, namely Cluster 1 (contains only the genus Mucor ) and Cluster 2 (consists of five small branches), and the distribution of strains from the same region was scattered in two clusters. There is no strict host selectivity for these fungi to infect fish. Mucor sp. are the main fungal pathogen of fish in these four regions, whereas Hypophthalmichthys molitrix and Carassius auratus are two types of fish that were susceptible to pathogen. In addition, the environmental adaptability experiments showed that eight highly pathogenic strains have different adaptability to the environment, and their optimum temperature and pH were 25°C and 7.0, respectively, whereas the concentration of NaCl was negatively correlated with the growth of strains. Therefore, these results indicated that the coinfection of multiple fungal pathogens in a culture region should be considered in the future study.

Impact of rhizosphere microorganisms on arsenic (As) transformation and accumulation in a traditional Chinese medical plant - Jiao-Jiao Li; Long Yang; Cui-Ping Miao; Ya-Jun Teng; Zi-Hao Fu; Chang-Lei Cheng; Xue-Xiu Chang; Yu Qian; Li-Xing Zhao (Environmental Science and Pollution Research, 2021)

A proteomic analysis of Bcl-2 regulation of cell cycle arrest: insight into the mechanisms - Xing Du; Jingjing Xiao; Xufeng Fu; Bo Xu; Hang Han; Yin Wang; Xiuying Pei (Journal of Zhejiang University-SCIENCE B, 2021)

Aquamicrobium zhengzhouense sp. nov., a Bacterium Isolated from Farmland Soil Applied with Amino Acid Fertilizer - Xiang Wang; Chun-Fu Zhou; Jia-Rong Cheng; Sheng-Fei Cao; Hong-Xing Yang; Jian-Rong Zhao (Current Microbiology, 2021)

Landslide mapping and analysis along the China-Pakistan Karakoram Highway based on SBAS-InSAR detection in 2017 - Xiao-jun Su; Yi Zhang; Xing-min Meng; Dong-xia Yue; Jin-hui Ma; Fu-yun Guo; Zi-qiang Zhou; Mohib Ur Rehman; Zainab Khalid; Guan Chen; Run-qiang Zeng; Fu-meng Zhao (Journal of Mountain Science, 2021)

Deformation of the Zhangjiazhuang high-speed railway tunnel: an analysis of causal mechanisms using geomorphological surveys and D-InSAR monitoring - Xing-min Meng; Tian-jun Qi; Yan Zhao; Tom Dijkstra; Wei Shi; Yin-fei Luo; Yuan-zhao Wu; Xiao-jun Su; Fu-meng Zhao; Jin-hui Ma; Yi Zhang; Guan Chen; et al. (Journal of Mountain Science, 2021)

Tectono-magmatic events of the Qilian orogenic belt in northern Tibet: new insights from detrital zircon geochronology of river sands - Shuo Zhang; Xing Jian; Alex Pullen; Ling Fu; Hanghai Liang; Dongming Hong; Wei Zhang (International Geology Review, 2021)

A new chlorine-containing iridoid glycoside from Plantago maxima - Liang-Liang Ma; Lu-Lu Wang; Yue-Feng Zhang; Xiang-Fu Jiang; Xin-Liu Zhu; Ke Pan; Chuan-Xing Wan; Zhong-Bo Zhou (Natural Product Research, 2021)

A reciprocal egg-swap experiment reveals sources of variation in developmental success among populations of a desert lizard - Xin Hao; Chen-Xu Wang; Xing-Zhi Han; Yang Wang; Qiong Zhang; Fu-Shun Zhang; Bao-Jun Sun; Wei-Guo Du (Oecologia, 2021)

Clinical study on empirical and diagnostic-driven (pre-emptive) therapy of voriconazole in severe aplastic anaemia patients with invasive fungal disease after intensive immunosuppressive therapy - Yuhong Wu; Li Yan; Huaquan Wang; Hong Liu; Limin Xing; Rong Fu; Zonghong Shao (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Cryostructures and ground ice content in ice-rich permafrost area of the Qinghai-Tibet Plateau with Computed Tomography Scanning - Xing-wen Fan; Zhan-ju Lin; Ze-yong Gao; Xiang-lian Meng; Fu-jun Niu; Jing Luo; Guo-an Yin; Fu-jun Zhou; Ai-yu Lan (Journal of Mountain Science, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Field tests of micro screw anchor piles under different loading conditions at three soil sites - Shi-Jin Feng; Wen-Ding Fu; Hong-Xin Chen; Hong-Xing Li; Yan-Li Xie; Shao-Feng Lv; Jin Li (Bulletin of Engineering Geology and the Environment, 2021)

The Effect of Atractylodes macrocephala Polysaccharides on Rabbit’s Host Defense Peptide (RSRAH) mRNA Expression - Guihua Fu; Yang Zhang; Yinglun Li; Xing He; Xiaofen Li; Peng Cheng; Hongwei Chen (International Journal of Peptide Research and Therapeutics, 2020)

Differences in evaporite geochemistry of the greater Ordos Ordovician salt basin, China: evidence from the M56 submember of the Majiagou Formation - Fu Fan; Fan-Wei Meng; Yong-Sheng Zhang; Mian-Ping Zheng; Kui Su; En-Yuan Xing (Carbonates and Evaporites, 2020)

SNP of AHSA2 gene in three cattle breeds using snapshot technology - Shu-Zhu Cheng; E. Guang-Xin; Cheng-Li Liu; Wang-Dui Basang; Yan-Bin Zhu; Ri-Su Na; Yan-Guo Han; Yan Zeng; Xiao Wang; Wei-Wei Ni; Bai-Gao Yang; Xing-Hai Duan; et al. (Journal of Genetics, 2020)

Biological-chemical comprehensive effects of goethite addition on nitrous oxide emissions in paddy soils - Jichao Zuo; Hongqing Hu; Qingling Fu; Jun Zhu; Zhiqiang Xing (Journal of Soils and Sediments, 2020)

Transcriptional analysis reveals physiological response to acute acidification stress of barramundi Lates calcarifer (Bloch) in coastal areas - Zhenhua Ma; Xing Zheng; Zhengyi Fu; Siqi Lin; Gang Yu; Jian G. Qin (Fish Physiology and Biochemistry, 2020)

Dinitrogen (N2) pulse emissions during freeze-thaw cycles from montane grassland soil - Xing Wu; Zhe Chen; Ralf Kiese; Jin Fu; Silvia Gschwendter; Michael Schloter; Chunyan Liu; Klaus Butterbach-Bahl; Benjamin Wolf; Michael Dannenmann (Biology and Fertility of Soils, 2020)
Short-lived pulses of soil nitrous oxide (N 2 O) emissions during freeze-thaw periods can dominate annual cumulative N 2 O fluxes from temperate managed and natural soils. However, the effects of freeze thaw cycles (FTCs) on dinitrogen (N 2 ) emissions, i.e., the dominant terminal product of the denitrification process, and ratios of N 2 /N 2 O emissions have remained largely unknown because methodological difficulties were so far hampering detailed studies. Here, we quantified both N 2 and N 2 O emissions of montane grassland soils exposed to three subsequent FTCs under two different soil moisture levels (40 and 80% WFPS) and under manure addition at 80% WFPS. In addition, we also quantified abundance and expression of functional genes involved in nitrification and denitrification to better understand microbial drivers of gaseous N losses. Our study shows that each freeze thaw cycle was associated with pulse emissions of both N 2 O and N 2 , with soil N 2 emissions exceeding N 2 O emissions by a factor of 5–30. Increasing soil moisture from 40 to 80% WFPS and addition of cow slurry increased the cumulative FTC N 2 emissions by 102% and 77%, respectively. For N 2 O, increasing soil moisture from 40 to 80% WFPS and addition of slurry increased the cumulative emissions by 147% and 42%, respectively. Denitrification gene cnorB and nosZ clade I transcript levels showed high explanatory power for N 2 O and N 2 emissions, thereby reflecting both N gas flux dynamics due to FTC and effects of different water availability and fertilizer addition. In agreement with several other studies for various ecosystems, we show here for mountainous grassland soils that pulse emissions of N 2 O were observed during freeze-thaw. More importantly, this study shows that the freeze-thaw N 2 pulse emissions strongly exceeded those of N 2 O in magnitude, which indicates that N 2 emissions during FTCs could represent an important N loss pathway within the grassland N mass balances. However, their actual significance needs to be assessed under field conditions using intact plant-soil systems.

Effects of different treatments on genes related to polysaccharide content in Dendrobium huoshanense - Jun Dai; Xing-bang Han; Nai-fu Chen; Cun-wu Chen; Nai-dong Chen; Xiang-wen Song; Xue-ping Jiang; Yu-juan Wang (Brazilian Journal of Botany, 2020)

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Responses of Primary Afferent Fibers to Acupuncture-Like Peripheral Stimulation at Different Frequencies: Characterization by Single-Unit Recording in Rats - Ran Huo; Song-Ping Han; Feng-Yu Liu; Xiao-Jing Shou; Ling-Yu Liu; Tian-Jia Song; Fu-Jun Zhai; Rong Zhang; Guo-Gang Xing; Ji-Sheng Han (Neuroscience Bulletin, 2020)

Deciphering the possible role of H2O2 in methylmercury-induced neurotoxicity in Xenopus laevis - Xufeng Fu; Xiuyu Yang; Xing Du; Qinghua Cui (Molecular & Cellular Toxicology, 2020)
Backgrounds Methylmercury (MeHg) is regarded as a developmental neurotoxicant but the detailed mechanism remains not completely clear. Methods The Xenopus laevis embryos were exposed to methylmercury chloride and the expression of neurodevelopment and oxidative stress genes was detected by qRT-PCR or Western blotting. PC12 cells were exposed to various levels of H 2 O 2 , and then cell cycle, neurite length, neurodevelopment-related genes, protein expression of apoptosis and autophagy were detected. Results The genes of neurodevelopment and oxidative stress were disrupted by methylmercury chloride and H 2 O 2 were increased interestingly in X. laevis embryos. Then, PC12 cells were exposed to H 2 O 2 and the results showed the cell cycle, neurite length, and neurodevelopment-related genes, the proteins apoptosis and autophagy were changed. Conclusion These results supported the idea that neurodevelopment-related gene expression was regulated by oxidative stress and that apoptosis and autophagy pathways were activated by H 2 O 2 and involved in methylmercury neurotoxicity.

Phytochemical constituents of the pericarps of Illicium difengpi and their anti-inflammatory activity - De-Sheng Ning; Yu-Xia Fu; Li-Yan Peng; Hui Tang; Lian-Chun Li; Xing-De Wu; Yu-Song Huang; Zheng-Hong Pan (Natural Product Research, 2020)

Tectonic affinity of the Khanka Massif in the easternmost Central Asian Orogenic Belt: evidence from detrital zircon geochronology of Permian sedimentary rocks - Kai-Chen Xing; Feng Wang; Wen-Liang Xu; Fu-Hong Gao (International Geology Review, 2020)

Soil bacteria and fungi respond differently to plant diversity and plant family composition during the secondary succession of abandoned farmland on the Loess Plateau, China - Zekun Zhong; Xinyi Zhang; Xing Wang; Shuyue Fu; Shaojun Wu; Xuqiao Lu; Chengjie Ren; Xinhui Han; Gaihe Yang (Plant and Soil, 2020)

Comparative effects on arsenic uptake between iron (hydro)oxides on root surface and rhizosphere of rice in an alkaline paddy soil - Yongqiang Yang; Hongqing Hu; Qingling Fu; Zhiqiang Xing; Xingyu Chen; Jun Zhu (Environmental Science and Pollution Research, 2020)

EFFECT OF A ROOT‐ZONE INJECTION IRRIGATION METHOD ON WATER PRODUCTIVITY AND APPLE PRODUCTION IN A SEMI‐ARID REGION IN NORTH‐WESTERN CHINA - Yan‐Ping Wang; Lin‐Sen Zhang; Yan Mu; Wei‐Hong Liu; Fu‐Xing Guo; Tian‐Ran Chang (Irrigation and Drainage, 2020)
Within the Chinese Loess Plateau, water resources are scarce and irrigation efficiency is a challenging issue. Traditional surface drip irrigation (SDI) methods have failed to improve irrigation efficiency and reduce surface evaporation in the region. An easy‐to‐install and practicable root‐zone injection irrigation (RII) method, with a low risk of emitter clogging and which uses subsurface infiltration‐promoting apparatuses (SIPA) to deliver water directly to the root zone, was designed and tested in an apple orchard over 3 years in northern Shaanxi, China. In the 0–0.6 m soil layer (where the apple roots are concentrated), the RII method produced consistently higher soil water content than the SDI method over all three growing seasons. The soil water content was consistently higher than 60% of field capacity, thus meeting the water requirements of fruit‐bearing apple trees. In addition, the RII method alleviated soil desiccation, significantly increased apple yields and improved fruit quality compared with the SDI method using the same volume of irrigation water. Both irrigation efficiency and water‐use efficiency were improved with the RII method. These results provide a theoretical basis for the utilization of the RII irrigation method in apple orchards in semi‐arid regions, which may improve water conservation and the sustainability of apple production. © 2019 John Wiley & Sons, Ltd.

The response of reference evapotranspiration to climate change in Xinjiang, China: Historical changes, driving forces, and future projections - Qing Dong; Weiguang Wang; Quanxi Shao; Wanqiu Xing; Yimin Ding; Jianyu Fu (International Journal of Climatology, 2020)
Reference evapotranspiration (ET 0 ), which is an indicator of atmospheric evaporation demand over a hypothetical reference surface, is expected to alter along with global climate change. In this study, the changes and driving forces of historical ET 0 and its future projections in Xinjiang, China, were comprehensively conducted. The trend analysis revealed that regional ET 0 decreased significantly at a rate of −4.1 mm/year 2 during 1961–1993 and increased at a rate of 3.4 mm/year 2 during 1994–2010. To explore the possible causes, the contributions of major climatic variables to the ET 0 trends were derived based on the differential equation method. During 1961–1993, the decreasing trend of ET 0 was primarily ascribed to the wind speed. The integrated negative effect from the decrease in wind speed ( U ) and increase in relative humidity ( RH ) was more significant than the positive effect from the increase in air temperature ( T ), resulting in the decrease in ET 0 . During 1994–2010, combined with increasing T and decreasing RH , the increase in U offset the effect of the net radiation ( R n ) decrease and led to an increase in ET 0 . Future ET 0 projections over three periods (2010–2039, 2040–2069, and 2070–2099, which are named as 2020s, 2050s, and 2080s, respectively) were conducted based on the general circulation models under two representative concentration pathways scenarios (RCP4.5 and RCP8.5). A continuous increasing trend in ET 0 was demonstrated in the 21st century. The increase in ET 0 will increase the irrigated water resource consumption and bring new challenge to water resource management in this area.

Stress associated protein 1 regulates the development of glandular trichomes in Artemisia annua - Yuting Wang; Xueqing Fu; Lihui Xie; Wei Qin; Ling Li; Xiaofen Sun; Shihai Xing; Kexuan Tang (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Life cycle environmental and economic assessment of coal seam gas-based electricity generation - Jingmin Hong; Zhaohe Yu; Xing Fu; Jinglan Hong (The International Journal of Life Cycle Assessment, 2019)

Microsatellite records for volume 11, issue 3 - Pengfei Hu; Hao-Xiang Liu; Ying Pan; Yan-Fu Qu; Xueqi Tian; Ke-Xin Wang; Yu-Heng Wei; Xue-Ping Wu; Xiumei Xing; Zhengyi Zhang; Pei Zhao; Yu-Tian Zhao; et al. (Conservation Genetics Resources, 2019)

An integrated prevention strategy to address problems associated with continuous cropping of watermelon caused by Fusarium oxysporum - Fu-Yan Liu; Qiang Zhu; Hu-Rong Yang; Jun Zhou; Chuan-Chao Dai; Xing-Xiang Wang (European Journal of Plant Pathology, 2019)

Extreme stress threatened double rice production in Southern China during 1981–2010 - Sheng-Li Liu; Xing Wang; Shou-Tian Ma; Xin Zhao; Fu Chen; Xiao-Ping Xiao; Rattan Lal; Hai-Lin Zhang (Theoretical and Applied Climatology, 2019)

Instability Mechanism and Control of Roadway Subjected to Severe Mining Dynamic Load with Double Roadway Layout Mining Face - Fu-lian He; Yong-qiang Zhao; Fu-xing Xie; Jun Liu (Geotechnical and Geological Engineering, 2019)

Regulation and metabolic engineering strategies for permeases of Saccharomyces cerevisiae - Peng Zhang; Qian Chen; Guiming Fu; linglin Xia; Xing Hu (World Journal of Microbiology and Biotechnology, 2019)

The associations of air pollution exposure during pregnancy with fetal growth and anthropometric measurements at birth: a systematic review and meta-analysis - Li Fu; Yi Chen; Xinyi Yang; Zuyao Yang; Sha Liu; Lei Pei; Baixiang Feng; Ganxiang Cao; Xin Liu; Hualiang Lin; Xing Li; Yufeng Ye; et al. (Environmental Science and Pollution Research, 2019)

Engineering SrCuxO composition to tailor the degradation activity toward organic pollutant under dark ambient conditions - Huihuang Chen; Weng Fu; Yulin Xing; Jinxuan Zhang; Jiangang Ku (Environmental Science and Pollution Research, 2019)

A Highly Selective Fluorescence “Turn on” and Absorbance-Ratiometric Detection of Al3+ in Totally H2O and its Application in Test Paper - Xue-Jiao Sun; Yu-Qing Ma; Hong Fu; Zhi-Yong Xing; Zhi-Gang Sun; Yue Shen; Jin-Long Li (Journal of Fluorescence, 2019)

Genomic and biological characterization of the Vibrio alginolyticus-infecting “Podoviridae” bacteriophage, vB_ValP_IME271 - Fei Li; Shaozhen Xing; Kaifei Fu; Shuping Zhao; Jianfei Liu; Yigang Tong; Lijun Zhou (Virus Genes, 2019)

Current genetic diversity in eight local Chinese sheep populations - Guang-Xin E; Yue-Hui Ma; Ming-Xing Chu; Qiong-Hua Hong; Yong-Fu Huang (Molecular Biology Reports, 2019)

Intraguild predation between Harmonia axyridis and Aphidius gifuensis: effects of starvation period, plant dimension and extraguild prey density - Xing-Lin Yu; Yi Feng; Wen-Yan Fu; Yuan-Xing Sun; Tong-Xian Liu (BioControl, 2019)

Total and available metal concentrations in soils from six long-term fertilization sites across China - Dong-Xing Guan; Fu-Sheng Sun; Guang-Hui Yu; Matthew L. Polizzotto; Yun-Gen Liu (Environmental Science and Pollution Research, 2018)

A new abietane diterpenoid from the roots of Tripterygium regelii - Zhi-Hua Jiang; Yan-Ping Liu; Miao He; Jin-Hua Zhao; Ting-Ting Wang; Xing-Yang Feng; Hao Yue; Ren-Bo An; Yan-Hui Fu (Natural Product Research, 2018)

Artificial intelligence in drug design - Feisheng Zhong; Jing Xing; Xutong Li; Xiaohong Liu; Zunyun Fu; Zhaoping Xiong; Dong Lu; Xiaolong Wu; Jihui Zhao; Xiaoqin Tan; Fei Li; Xiaomin Luo; et al. (Science China Life Sciences, 2018)

Effects of a proline solution cover on the geochemical and mineralogical characteristics of high-sulfur coal gangue - Youfa Luo; Yonggui Wu; Tianling Fu; Hu Wang; Rongrong Xing; Zhilin Zheng (Acta Geochimica, 2018)

Antifungal and Biocontrol Evaluation of Four Lysobacter Strains Against Clubroot Disease - Lina Fu; Hanmei Li; Lanfang Wei; Jun Yang; Qi Liu; Yating Wang; Xing Wang; Guanghai Ji (Indian Journal of Microbiology, 2018)

Haploid plant regeneration from hardy kiwifruit (Actinidia arguta Planch.) anther culture - Guang-Fu Wang; Hong-Yan Qin; Dan Sun; Shu-Tian Fan; Yi-Ming Yang; Zhen-Xing Wang; Pei-Llei Xu; Ying Zhao; Ying-Xue Liu; Jun Ai (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

PGC-1α coordinates with Bcl-2 to control the cell cycle in U251 cells through reducing ROS - Kun Yao; Xu-feng Fu; Xing Du; Yan Li; Shan-shan Yang; Min Yu; Qing-hua Cui (Journal of Zhejiang University-SCIENCE B, 2018)

Mixed Cadzow filtering method in fractional Fourier domain - Zhong-Lin Cao; Jun-Xing Cao; Fu-Rong Wu; Guang-Ming He; Qiang Zhou; Yu-Lin Wu (Applied Geophysics, 2018)

Revealing histological and morphological features of female reproductive system in tree shrew (Tupaia belangeri) - Shan Zhong; Shi-yao Zhang; Hui-jie Xing; Xiao-tan Zhang; Guang Wang; Yong-ping Bao; Jiang-nan Fu; Xuesong Yang (Zoomorphology, 2018)

The effects of vegetation on runoff and soil loss: Multidimensional structure analysis and scale characteristics - Jianbo Liu; Guangyao Gao; Shuai Wang; Lei Jiao; Xing Wu; Bojie Fu (Journal of Geographical Sciences, 2018)

New progress in understanding the origins of modern humans in China - Xing Gao; Fei Peng; QiaoMei Fu; Feng Li (Science China Earth Sciences, 2017)

Effect of Temperature–Water Coupled Actions on Joint Morphology - Jing-shuo Liu; Ping Cao; Jie Liu; Jin-xing Fan; Guo-guo Ning; Fu-liang Li (Geotechnical and Geological Engineering, 2017)

Fiber-type distribution and expression of myosin heavy chain isoforms in newborn heterozygous myostatin-knockout pigs - Xiao-Xu Xing; Mei-Fu Xuan; Long Jin; Qing Guo; Zhao-Bo Luo; Jun-Xia Wang; Qi-Rong Luo; Guang-Lei Zhang; Cheng-Du Cui; Zheng-Yun Cui; Jin-Dan Kang; Xi-Jun Yin (Biotechnology Letters, 2017)

Complete genome sequence of a novel, virulent Ahjdlikevirus bacteriophage that infects Enterococcus faecium - Shaozhen Xing; Xianglilan Zhang; Qiang Sun; Jian Wang; Zhiqiang Mi; Guangqian Pei; Yong Huang; Xiaoping An; Kaifei Fu; Lijun Zhou; Baohua Zhao; Yigang Tong (Archives of Virology, 2017)

The nitrate‐reduction gene cluster components exert lineage‐dependent contributions to optimization of Sinorhizobium symbiosis with soybeans - Li Xue Liu; Qin Qin Li; Yun Zeng Zhang; Yue Hu; Jian Jiao; Hui Juan Guo; Xing Xing Zhang; Biliang Zhang; Wen Xin Chen; Chang Fu Tian (Environmental Microbiology, 2017)
Summary Receiving nodulation and nitrogen fixation genes does not guarantee rhizobia an effective symbiosis with legumes. Here, variations in gene content were determined for three Sinorhizobium species showing contrasting symbiotic efficiency on soybeans. A nitrate‐reduction gene cluster absent in S. sojae was found to be essential for symbiotic adaptations of S. fredii and S . sp. III. In S. fredii , the deletion mutation of the nap (nitrate reductase), instead of nir (nitrite reductase) and nor (nitric oxide reductase), led to defects in nitrogen‐fixation (Fix – ). By contrast, none of these core nitrate‐reduction genes were required for the symbiosis of S . sp. III. However, within the same gene cluster, the deletion of hemN1 (encoding oxygen‐independent coproporphyrinogen III oxidase) in both S. fredii and S . sp. III led to the formation of nitrogen‐fixing (Fix + ) but ineffective (Eff – ) nodules. These Fix + /Eff – nodules were characterized by significantly lower enzyme activity of glutamine synthetase indicating rhizobial modulation of nitrogen‐assimilation by plants. A distant homologue of HemN1 from S. sojae can complement this defect in S. fredii and S . sp. III, but exhibited a more pleotropic role in symbiosis establishment. These findings highlighted the lineage‐dependent optimization of symbiotic functions in different rhizobial species associated with the same host.

Field testing of the surface electromagnetic prospecting system - Qing-Yun Di; Chang-Min Fu; Zhi-Guo An; Cheng Xu; Ya-Lu Wang; Zhong-Xing Wang (Applied Geophysics, 2017)

The Neuron-Specific Protein TMEM59L Mediates Oxidative Stress-Induced Cell Death - Qiuyang Zheng; Xiaoyuan Zheng; Lishan Zhang; Hong Luo; Lingzhi Qian; Xing Fu; Yiqian Liu; Yuehong Gao; Mengxi Niu; Jian Meng; Muxian Zhang; Guojun Bu; et al. (Molecular Neurobiology, 2017)

Acute psychoactive and toxic effects of D. metel on mice explained by 1H NMR based metabolomics approach - Yonghong Fu; Zhihong Si; Pumin Li; Minghui Li; He Zhao; Lei Jiang; Yuexiao Xing; Wei Hong; Lingyu Ruan; Jun-Song Wang (Metabolic Brain Disease, 2017)

The increased expression of follicle-stimulating hormone leads to a decrease of fecundity in transgenic Large White female pigs - Kai Jiang; Pan Xu; Wanbo Li; Qiang Yang; Longyun Li; Chuanmin Qiao; Huanfa Gong; Hao Zheng; Zhimin Zhou; Hao Fu; Qiuyan Li; Yuyun Xing; et al. (Transgenic Research, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

Pyrosequencing of rpoB uncovers a significant biogeographical pattern of rhizobial species in soybean rhizosphere - Xing Xing Zhang; Hui Juan Guo; Jian Jiao; Pan Zhang; Hui Yang Xiong; Wen Xin Chen; Chang Fu Tian (Journal of Biogeography, 2017)
Aim Most culture‐independent studies of bacterial biogeography have been at genus or higher taxonomic levels, although many important processes mediated by bacteria are at the strain or species level, such as the competitive nodulation of rhizobia on legumes. Here, at the intra‐species level, we characterized the structural variation in rhizobial populations in soybean rhizosphere under field conditions across 32 sampling sites in three eco‐regions. Location North‐east (Heilongjiang), north (Hebei–Shandong) and south (Jiangxi) China. Methods The intra‐species diversity of rhizobia in soybean rhizospheres was investigated by rpoB pyrosequencing. Soybean nodule isolates were characterized using repetitive extragenic palindromic PCR , restriction fragment length polymorphism of 16S‐23S intergenic sequences and rpoB PCR sequencing. Patterns and processes of biogeography of identified rhizobia were studied. Results Significant biogeographical patterns of rhizosphere rhizobia at the species level were found, and the abundant species in the rhizosphere were generally the dominant microsymbionts in soybean nodules. The distribution of rhizobial species in the rhizosphere across eco‐regions correlated with combined effects of spatial, vegetative, edaphic and climatic variables. Gene flow and genetic differentiation analyses revealed that there was no dispersal limitation among geographical populations of the same rhizobial species, and drift or subsequent diversification might be involved in shaping the biogeographical pattern in addition to environmental factors. Main conclusions These results constitute the first report of the existence of rhizobial biogeography in legume rhizospheres at the species level, contrasting with most studies, which focused on nodule isolates. The method developed in this study could be used to uncover, at high resolution, the diversity of local rhizobial populations in soils. This information is crucial for choosing suitable strains or species as inoculants for a specific legume host under local field conditions. Moreover, a similar strategy could be used to study other bacteria with important ecological functions.

Treatment of decabromodiphenyl ether (BDE209) contaminated soil by solubilizer-enhanced electrokinetics coupled with ZVI-PRB - Rongbing Fu; Dongdong Wen; Xing Chen; Yingying Gu; Zhen Xu; Wei Zhang (Environmental Science and Pollution Research, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Joint 3D traveltime calculation based on fast marching method and wavefront construction - Hui Sun; Jian-Guo Sun; Zhang-Qing Sun; Fu-Xing Han; Zhi-Qiang Liu; Ming-Chen Liu; Zheng-Hui Gao; Xiu-Lin Shi (Applied Geophysics, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Early Cretaceous porphyry copper mineralization in Northeast China: the Changfagou example - Yong Zhang; Shu–Wen Xing; Chao Li; Shi–Fu Liang; Zheng–Tao Yu; Xiao–Hui Du; Yan Wang; Zeng–Jie Zhang; Yu–Bo Ma (International Geology Review, 2017)

First discovery of a Palaeoproterozoic A-type granite in southern Wuyishan terrane, Cathaysia Block: evidence from geochronology, geochemistry, and Nd–Hf–O isotopes - Zhi-Hong Chen; Ling Zhao; Dan-Dan Chen; Xi-Lin Zhao; Guang-Fu Xing (International Geology Review, 2017)

Seroprevalence and risk factors of bovine viral diarrhoea virus (BVDV) infection in yaks (Bos grunniens) in northwest China - Jian-Gang Ma; Wei Cong; Fu-Heng Zhang; Sheng-Yong Feng; Dong-Hui Zhou; Yi-Ming Wang; Xing-Quan Zhu; Hong Yin; Gui-Xue Hu (Tropical Animal Health and Production, 2016)

SfP53 and filamentous actin (F-actin) are the targets of viral pesticide AcMNPV-BmK IT (P10/PH) in host Spodoptera frugiperda 9 cells - Leixi Cao; Xing Li; Shuhua Zheng; Aihua Liang; Yuejun Fu (Biotechnology Letters, 2016)

Geochemistry of Altungol cap dolostones from the Tarim Basin, NW China - Fan Feng; Ping Guan; Wenhui Liu; Wei Zhang; Peixian Liu; Xing Jian; Ling Fu (Arabian Journal of Geosciences, 2016)

Subinhibitory concentrations of phloretin repress the virulence of Salmonella typhimurium and protect against Salmonella typhimurium infection - Wu Shuai-Cheng; Fu Ben-Dong; Chu Xiu-Ling; Su Jian-Qing; Fu Yun-Xing; Cui Zhen-Qiang; Xu Dao-Xiu; Wu Zong-Mei (Antonie van Leeuwenhoek, 2016)

Transcriptome analysis of sika deer in China - Bo-Yin Jia; Heng-Xing Ba; Gui-Wu Wang; Ying Yang; Xue-Zhe Cui; Ying-Hua Peng; Jun-Jun Zheng; Xiu-Mei Xing; Fu-He Yang (Molecular Genetics and Genomics, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Effect of organic solvent on fungicide toxicity to Sclerotinia sclerotiorum and Botrytis cinerea - Hong-Jie Liang; Xiao-Ming Lu; Zu-Qing Zhu; Fu-Xing Zhu (European Journal of Plant Pathology, 2016)

PCI-24781 can improve in vitro and in vivo developmental capacity of pig somatic cell nuclear transfer embryos - Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Yu-Chen Zhang; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Xi-Jun Yin; Jin-Dan Kang (Biotechnology Letters, 2016)

Statistical downscaling of reference evapotranspiration in Haihe River Basin: applicability assessment and application to future projection - Wanqiu Xing; Weiguang Wang; Quanxi Shao; John Taylor; Yimin Ding; Jianyu Fu; Xiaozhou Feng (Hydrological Sciences Journal, 2016)

Levels, congener profile and inventory of polychlorinated biphenyls in sediment from the Songhua River in the vicinity of cement plant, China: a case study - Song Cui; Qiang Fu; Yi-Fan Li; Wen-long Li; Tian-xiao Li; Min Wang; Zhen-xiang Xing; Lu-ji Zhang (Environmental Science and Pollution Research, 2016)

Comprehensive analyses of the initiation and landslide-generated wave processes of the 24 June 2015 Hongyanzi landslide at the Three Gorges Reservoir, China - Jia-wen Zhou; Fu-gang Xu; Xing-guo Yang; Yu-chuan Yang; Peng-yuan Lu (Landslides, 2016)

Effects of seasonal variations on soil microbial community composition of two typical zonal vegetation types in the Wuyi Mountains - Ze-yan Wu; Wen-xiong Lin; Jian-juan Li; Jin-fu Liu; Bai-lian Li; Lin-kun Wu; Chang-xun Fang; Zhi-xing Zhang (Journal of Mountain Science, 2016)

Dispersion function of Rayleigh waves in porous layered half-space system - Shou-Guo Yan; Fu-Li Xie; Chang-Zheng Li; Bi-Xing Zhang (Applied Geophysics, 2016)

A new kaurane diterpenoid from Isodon inflexus - Guang-Hua Xu; Xing-Fu Cai; Xuejun Jin; Jung Joon Lee (Natural Product Research, 2016)

CHD3 chromatin-remodeling factor PICKLE regulates floral transition partially via modulating LEAFY expression at the chromatin level in Arabidopsis - Xing Fu; Chaonan Li; Qing Liang; Yangyang Zhou; Hang He; Liu-Min Fan (Science China Life Sciences, 2016)

Mechanism of Rock Burst Occurrence in Specially Thick Coal Seam with Rock Parting - Jian-chao Wang; Fu-xing Jiang; Xiang-jun Meng; Xu-you Wang; Si-tao Zhu; Yu Feng (Rock Mechanics and Rock Engineering, 2016)

Palaeoproterozoic A-type magmatism in northern Wuyishan terrane, Southeast China: petrogenesis and tectonic implications - Zhi-Hong Chen; Guang-Fu Xing; Xi-Lin Zhao (International Geology Review, 2016)

One new 19- nor cucurbitane-type triterpenoid from the stems of Momordica charantia - Yong-chao Li; Xin-juan Xu; Jing Yang; Xing-gang Wu; Qing-yun Fu (Natural Product Research, 2016)

Roles of microRNA and signaling pathway in osteoarthritis pathogenesis - Bin Xu; Yao-yao Li; Jun Ma; Fu-xing Pei (Journal of Zhejiang University-SCIENCE B, 2016)

PGC-1α regulates the cell cycle through ATP and ROS in CH1 cells - Xu-feng Fu; Kun Yao; Xing Du; Yan Li; Xiu-yu Yang; Min Yu; Mei-zhang Li; Qing-hua Cui (Journal of Zhejiang University-SCIENCE B, 2016)

Cardioprotective Effect of Anisodamine Against Myocardial Ischemia Injury and its Influence on Cardiomyocytes Apoptosis - Kun Xing; Xianghua Fu; Lingling Jiang; Yanbo Wang; Wei Li; Xinshun Gu; Guozhen Hao; Qing Miao; Xiaolin Ge; Yuhong Peng; Wei Geng; Shiru Bai; et al. (Cell Biochemistry and Biophysics, 2015)

Characterization and expression analysis of Calmodulin (CaM) in orange-spotted grouper (Epinephelus coioides) in response to Vibrio alginolyticus challenge - Sheng-Wei Luo; Fu-Xing Xie; Yuan Liu; Wei-Na Wang (Ecotoxicology, 2015)

Regulation analysis of AcMNPV-mediated expression of a Chinese scorpion neurotoxin under the IE1, P10 and PH promoter in vivo and its use as a potential bio-insecticide - Yuejun Fu; Xing Li; Jun Du; Shuhua Zheng; Aihua Liang (Biotechnology Letters, 2015)

Enzymatic hydrolysis of 7-xylosyltaxanes by an extracellular xylosidase from Cellulosimicrobium cellulans - Tong-Yi Dou; Hong-Wei Luan; Xing-Bao Liu; Shi-Yang Li; Xun-Fu Du; Ling Yang (Biotechnology Letters, 2015)

Baseline sensitivity and control efficacy of fluazinam against Sclerotinia sclerotiorum - Hong-Jie Liang; Ya-Li Di; Jin-Li Li; Fu-Xing Zhu (European Journal of Plant Pathology, 2015)

Multiple Mesozoic magma processes formed the 240–185 Ma composite Weishan pluton, South China: evidence from geochronology, geochemistry, and Sr-Nd isotopes - Xing Ding; Wei-Dong Sun; Wei-Feng Chen; Pei-Rong Chen; Tao Sun; Sai-Jun Sun; Chiou-Ting Lin; Fu-Kun Chen (International Geology Review, 2015)

A mathematical model for determining the maximum impact stress on a downstream structure induced by dam-break flow in mountain rivers - Fu-gang Xu; Xing-guo Yang; Jia-wen Zhou (Arabian Journal of Geosciences, 2015)

Induction of plant virus defense response by brassinosteroids and brassinosteroid signaling in Arabidopsis thaliana - Da-Wei Zhang; Xing-Guang Deng; Fa-Qiong Fu; Hong-Hui Lin (Planta, 2015)

Cell-density-dependent manifestation of partial characteristics for neuronal precursors in a newly established human gliosarcoma cell line - Pei-Sen Yao; De-Zhi Kang; Xing-Fu Wang; Ru-Ying Lin; Zu-Cheng Ye (In Vitro Cellular & Developmental Biology - Animal, 2015)

Association of an Exon SNP of SLC2A9 Gene with Hyperuricemia Complicated with Type 2 Diabetes Mellitus in the Chinese Male Han Population - Shi-Chao Xing; Xu-Fu Wang; Zhi-Min Miao; Xue-Zhi Zhang; Jun Zheng; Ying Yuan (Cell Biochemistry and Biophysics, 2015)

Intercropping enhances soil carbon and nitrogen - Wen‐Feng Cong; Ellis Hoffland; Long Li; Johan Six; Jian‐Hao Sun; Xing‐Guo Bao; Fu‐Suo Zhang; Wopke Van Der Werf (Global Change Biology, 2015)
Intercropping, the simultaneous cultivation of multiple crop species in a single field, increases aboveground productivity due to species complementarity. We hypothesized that intercrops may have greater belowground productivity than sole crops, and sequester more soil carbon over time due to greater input of root litter. Here, we demonstrate a divergence in soil organic carbon (C) and nitrogen (N) content over 7 years in a field experiment that compared rotational strip intercrop systems and ordinary crop rotations. Soil organic C content in the top 20 cm was 4% ± 1% greater in intercrops than in sole crops, indicating a difference in C sequestration rate between intercrop and sole crop systems of 184 ± 86 kg C ha −1 yr −1 . Soil organic N content in the top 20 cm was 11% ± 1% greater in intercrops than in sole crops, indicating a difference in N sequestration rate between intercrop and sole crop systems of 45 ± 10 kg N ha −1 yr −1 . Total root biomass in intercrops was on average 23% greater than the average root biomass in sole crops, providing a possible mechanism for the observed divergence in soil C sequestration between sole crop and intercrop systems. A lowering of the soil δ 15 N signature suggested that increased biological N fixation and/or reduced gaseous N losses contributed to the increases in soil N in intercrop rotations with faba bean. Increases in soil N in wheat/maize intercrop pointed to contributions from a broader suite of mechanisms for N retention, e.g., complementary N uptake strategies of the intercropped plant species. Our results indicate that soil C sequestration potential of strip intercropping is similar in magnitude to that of currently recommended management practises to conserve organic matter in soil. Intercropping can contribute to multiple agroecosystem services by increased yield, better soil quality and soil C sequestration.

Association of ACP1 gene polymorphisms and coronary artery disease in northeast Chinese population - TIANBAO LI; XUESONG XU; JIANZHUO LI; SHU XING; LIN ZHANG; WANNAN LI; JUNFENG MA; XUEQI FU (Journal of Genetics, 2015)

The effect of temperature on repeat swimming performance in juvenile qingbo (Spinibarbus sinensis) - Xu Pang; Xing-Zhong Yuan; Zhen-Dong Cao; Yao-Guang Zhang; Shi-Jian Fu (Fish Physiology and Biochemistry, 2015)

Baseline sensitivity and control efficacy of DMI fungicide epoxiconazole against Sclerotinia sclerotiorum - Jin-Li Li; Xiang-Yang Liu; Ya-Li Di; Hong-Jie Liang; Fu-Xing Zhu (European Journal of Plant Pathology, 2015)

Experimental Study of the Effect on Bone Metabolism and Bone Histomorphometry of Osteoporosis Rats with Birdpecking and Revolving Moxibustion on Twelve Back-Shu Points - Hong-Shi Zhang; Tie Li; Xing-Shan Liu; Fu-Chun Wang; Xin Yao; Li Yan; Wu-Jin Liang (Cell Biochemistry and Biophysics, 2015)

Construction of a lentiviral T/A vector for direct analysis of PCR-amplified promoters - Fu-xian Yu; Zhi-wei Zhu; Xiao-yu Chen; Jing Huang; Tuan-yuan Shi; Jun-xing Li; Jian-zhi Pan (Molecular Biology Reports, 2014)

Effects of grazing exclusion on soil carbon and nitrogen storage in semi-arid grassland in Inner Mongolia, China - Xing Wu; Zongshan Li; Bojie Fu; Fei Lu; Dongbo Wang; Huifeng Liu; Guohua Liu (Chinese Geographical Science, 2014)

Isolation and characterization of microsatellite loci in Euphorbia lamarckii Sweet (Euphorbiaceae) from the Canary Islands - Yan-Shu Li; Ye Sun; Fa-Guo Wang; Fu-Wu Xing (Conservation Genetics Resources, 2014)

Genetic diversity and differentiation in the critically endangered orchid (Amitostigma hemipilioides): implications for conservation - Qin Yang; Yan Fu; Yong-qing Wang; Yun Wang; Wen-hua Zhang; Xing-yuan Li; Yong-Quan Reng; Jie Zhang (Plant Systematics and Evolution, 2014)

A dwarfing mutant caused by deactivation function of alpha subunit of the heterotrimeric G-protein in rice - De-wei Yang; Xiang-hua Zheng; Chao-ping Cheng; Wen-da Wang; Deng-hui Xing; Li-bin Lu; Chen-de Liu; Ning Ye; Mei-juan Zeng; Xin-fu Ye (Euphytica, 2014)

Improved Insecticidal Toxicity by Fusing Cry1Ac of Bacillus thuringiensis with Av3 of Anemonia viridis - Fu Yan; Xing Cheng; Xuezhi Ding; Ting Yao; Hanna Chen; Wenping Li; Shengbiao Hu; Ziquan Yu; Yunjun Sun; Youming Zhang; Liqiu Xia (Current Microbiology, 2014)

Repositioning Suture of the Erector Spinae Muscle for Lumbar Spine Surgery via the Posterior Approach: A Prospective Randomized Study - Yu-Jie Wu; Zhi-Yi Fu; Xiao-Peng Hu; Jiang Shao; Xing-Zhen Liu; Wen-Jie Jin (Cell Biochemistry and Biophysics, 2014)

Clodronate liposomes reduce excessive scar formation in a mouse model of burn injury by reducing collagen deposition and TGF-β1 expression - Shao-wei Lu; Xing-mei Zhang; Hong-min Luo; Yu-cai Fu; Ming-yan Xu; Shi-jie Tang (Molecular Biology Reports, 2014)

Snow cover and soil moisture controls of freeze–thaw-related soil gas fluxes from a typical semi-arid grassland soil: a laboratory experiment - Xing Wu; Nicolas Brüggemann; Klaus Butterbach-Bahl; Bojie Fu; Guohua Liu (Biology and Fertility of Soils, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Differential expression of VGLUT1 or VGLUT2 in the trigeminothalamic or trigeminocerebellar projection neurons in the rat - Shun-Nan Ge; Zhi-Hong Li; Jun Tang; Yunfei Ma; Hiroyuki Hioki; Ting Zhang; Ya-Cheng Lu; Fu-Xing Zhang; Noboru Mizuno; Takeshi Kaneko; Ying-Ying Liu; Mandy Siu Yu Lung; et al. (Brain Structure and Function, 2014)

New 18-oxygenated polyhydroxy steroid from a South China Sea soft coral Sarcophyton sp. - Ling-Ling Sun; Xiu-Mei Fu; Xiu-Bao Li; Qian Xing; Chang-Yun Wang (Natural Product Research, 2013)

miR-155 inhibits oxidized low-density lipoprotein-induced apoptosis of RAW264.7 cells - Guo-fu Zhu; Li-xia Yang; Rui-wei Guo; Hong Liu; Yan-kun Shi; Hong Wang; Jin-shan Ye; Zhi-hua Yang; Xing Liang (Molecular and Cellular Biochemistry, 2013)

Petrogenesis of a Palaeoproterozoic S-type granite, central Wuyishan terrane, SE China: implications for early crustal evolution of the Cathaysia Block - Zhi-Hong Chen; Guang-Fu Xing (International Geology Review, 2013)

Promoting role of an endophyte on the growth and contents of kinsenosides and flavonoids of Anoectochilus formosanus Hayata, a rare and threatened medicinal Orchidaceae plant - Fu-sheng Zhang; Ya-li Lv; Yue Zhao; Shun-xing Guo (Journal of Zhejiang University-SCIENCE B, 2013)

Functional analyses of a flavonol synthase–like gene from Camellia nitidissima reveal its roles in flavonoid metabolism during floral pigmentation - Xing-Wen Zhou; Zheng-Qi Fan; Yue Chen; Yu-Lin Zhu; Ji-Yuan Li; Heng-Fu Yin (Journal of Biosciences, 2013)

Research on the imaging of concrete defect based on the pulse compression technique - Chang-Zheng Li; Bi-Xing Zhang; Fang-Fang Shi; Fu-Li Xie (Applied Geophysics, 2013)

Tetracyclic spirooxindole blockers of hNaV1.7: activity in vitro and in CFA-induced inflammatory pain model - Sultan Chowdhury; Shifeng Liu; Jay A. Cadieux; Tom Hsieh; Mikhail Chafeev; Shaoyi Sun; Qi Jia; Jianyu Sun; Mark Wood; Jonathan Langille; Serguei Sviridov; Jianmin Fu; et al. (Medicinal Chemistry Research, 2013)

Quantitative assessment of the effect of ABCA1 gene polymorphism on the risk of Alzheimer’s disease - Xiao-Feng Wang; Yuan-Wu Cao; Zhen-Zhou Feng; Da Fu; Yu-Shui Ma; Feng Zhang; Xiao-Xing Jiang; Yun-Chao Shao (Molecular Biology Reports, 2013)

The effects of temperature and exercise training on swimming performance in juvenile qingbo (Spinibarbus sinensis) - Xu Pang; Xing-Zhong Yuan; Zhen-Dong Cao; Shi-Jian Fu (Journal of Comparative Physiology B, 2013)

Coping with climate-induced water stresses through time and space in the mountains of Southwest China - Yufang Su; Jianchu Xu; Andy Wilkes; Juliet Lu; Qiaohong Li; Yao Fu; Xing Ma; R. Edward Grumbine (Regional Environmental Change, 2012)

Foraging responses of clonal plants to multi-patch environmental heterogeneity: spatial preference and temporal reversibility - Ying Gao; Fu Xing; Yongjun Jin; Dandan Nie; Ying Wang (Plant and Soil, 2012)

Tomographic inversion for microseismic source parameters in mining - Hua-Xiang Miao; Fu-Xing Jiang; Xue-Juan Song; Shu-Hua Yang; Jun-Ru Jiao (Applied Geophysics, 2012)

The influence of sea water velocity variation on seismic traveltimes, ray paths, and amplitude - Fu-Xing Han; Jian-Guo Sun; Kun Wang (Applied Geophysics, 2012)

Anomalous temperature–growth response of Abies faxoniana to sustained freezing stress along elevational gradients in China’s Western Sichuan Province - Zong Shan Li; Guo Hua Liu; Bo Jie Fu; Chan Juan Hu; Shu Zheng Luo; Xing Liang Liu; Fei He (Trees, 2012)

Comparative mapping reveals similar linkage of functional genes to QTL of yield-related traits between Brassica napus and Oryza sativa - FUPENG LI; CHAOZHI MA; QINGFANG CHEN; TOUMING LIU; JINXIONG SHEN; JINXING TU; YONGZHONG XING; TINGDONG FU (Journal of Genetics, 2012)

Geochemical characteristics and petrogenesis of Permian basaltic rocks in Keping area, Western Tarim basin: A record of plume-lithosphere interaction - Junchuan Yu; Xuanxue Mo; Xuehui Yu; Guochen Dong; Qiang Fu; Fengcun Xing (Journal of Earth Science, 2012)

Exploration of biguanido–oxovanadium complexes as potent and selective inhibitors of protein tyrosine phosphatases - Liping Lu; Xiaoli Gao; Miaoli Zhu; Sulian Wang; Qiong Wu; Shu Xing; Xueqi Fu; Zhiwei Liu; Maolin Guo (BioMetals, 2012)

Automatically positioning microseismic sources in mining by the stereo tomographic method using full wavefields - Hua-Xiang Miao; Fu-Xing Jiang; Xue-Juan Song; Jian-Yong Song; Shu-Hua Yang; Jun-Ru Jiao (Applied Geophysics, 2012)

Agrobacterium-mediated genetic transformation and regeneration of transgenic plants using leaf segments as explants in Valencia sweet orange - Ehsan Ullah Khan; Xing-Zheng Fu; Ji-Hong Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Spontaneous retroperitoneal hemorrhage after hemodialysis involving anticoagulant agents - Wen-xing Fan; Zheng-xu Deng; Fang Liu; Rong-bo Liu; Ling He; Bogati Amrit; Li Zang; Jing-wen Li; Xian-rong Liu; Song-min Huang; Ping Fu (Journal of Zhejiang University-SCIENCE B, 2012)

Suppression of lung cancer metastasis-related protein 1 (LCMR1) inhibits the growth of colorectal cancer cells - E Ji-Fu; Jun-Jie Xing; Li-Qiang Hao; Chuan-Gang Fu (Molecular Biology Reports, 2012)

Effect of dirhamnolipid on the removal of phenol catalyzed by laccase in aqueous solution - Zhi-Feng Liu; Guang-Ming Zeng; Hua Zhong; Xing-Zhong Yuan; Hai-Yan Fu; Mei-Fang Zhou; Xiao-Ling Ma; Hui Li; Jian-Bing Li (World Journal of Microbiology and Biotechnology, 2012)

Construction and characterization of a normalized cDNA library from the river snail Bellamya aeruginosa after exposure to copper - Zi-Cheng Li; Li-Hui An; Qing Fu; Ying Liu; Lei Zhang; Hao Chen; Xing-Ru Zhao; Li-Jing Wang; Bing-Hui Zheng; Lin-Bo Zhang (Ecotoxicology, 2012)

Potent inhibition of protein tyrosine phosphatases by copper complexes with multi-benzimidazole derivatives - Ying Li; Liping Lu; Miaoli Zhu; Qingming Wang; Caixia Yuan; Shu Xing; Xueqi Fu; Yuhua Mei (BioMetals, 2011)

Noradrenaline regulates substance P release from rat dorsal root ganglion neurons in vitro - Yan-Jie Wang; Xing-Fu Li; Feng Ding; Qiang Shu; Li-Jun Song; Xiao Yu; Hua-Xiang Liu (Neuroscience Bulletin, 2011)

Digital design of scaffold for mandibular defect repair based on tissue engineering - Yun-feng Liu; Fu-dong Zhu; Xing-tao Dong; Wei Peng (Journal of Zhejiang University-SCIENCE B, 2011)

Sex difference in QTc prolongation in chronic institutionalized patients with schizophrenia on long-term treatment with typical and atypical antipsychotics - Fu De Yang; Xiang Qun Wang; Xiu Ping Liu; Ke Xin Zhao; Wei Hong Fu; Xue Ru Hao; Xing Li Zhang; Guo Shu Huang; Sheng Cai Qu; Jing Shen Bai; Xu Feng Huang; Thomas R. Kosten; et al. (Psychopharmacology, 2011)

A new bioorganic fertilizer can effectively control banana wilt by strong colonization with Bacillus subtilis N11 - Nan Zhang; Kai Wu; Xin He; Shu-qing Li; Zhen-hua Zhang; Biao Shen; Xing-ming Yang; Rui-fu Zhang; Qi-wei Huang; Qi-rong Shen (Plant and Soil, 2011)

Reagentless biosensor based on layer-by-layer assembly of functional multiwall carbon nanotubes and enzyme-mediator biocomposite - Xing-hua Zhou; Feng-na Xi; Yi-ming Zhang; Xian-fu Lin (Journal of Zhejiang University-SCIENCE B, 2011)

Malignant transformation of 293 cells induced by ectopic expression of human Nanog - Yan-Li Lin; Zheng-Bin Han; Fu-Yin Xiong; Li-Yuan Tian; Xiao-Jie Wu; Shi-Wei Xue; Yan-Rong Zhou; Ji-Xian Deng; Hong-Xing Chen (Molecular and Cellular Biochemistry, 2011)

Molecular characterisation of cereal cyst nematodes in winter wheat on the Huang-Huai floodplain of China using RFLP and rDNA-ITS sequence analyses - Bo Fu; Hong-xia Yuan; Yu Zhang; Xing-song Hou; Gao-lei Nian; Peng Zhang; Xiao-ping Xing; Bing-jian Sun; Ian T. Riley; Hong-lian Li (Australasian Plant Pathology, 2011)

Inflammatory bowel disease unclassified - Ning Zhou; Wei-xing Chen; Shao-hua Chen; Cheng-fu Xu; You-ming Li (Journal of Zhejiang University-SCIENCE B, 2011)

The Association of the Metalloproteinase-3 Gene Promoter Polymorphisms and the Middle Cerebral Artery Stenosis - Chunli Fu; Yingqi Xing; Xiaonan Song (Cell Biochemistry and Biophysics, 2011)

Analyzing coastal wetland change in the Yancheng National Nature Reserve, China - Chang-Qing Ke; Dong Zhang; Fu-Qiang Wang; Shu-Xing Chen; Christance Schmullius; Wolfgang-Martin Boerner; Hui Wang (Regional Environmental Change, 2011)

A large indel mutation of the bovine ADD1/SREBP1c gene and its effects on growth traits in some native cattle breeds from China - Yong-Zhen Huang; En-Ping Zhang; Jing Wang; Yong-Tao Huai; Liang Ma; Fu-Ying Chen; Xian-Yong Lan; Chu-Zhao Lei; Xing-Tang Fang; Ju-Qiang Wang; Hong Chen (Molecular Biology Reports, 2011)

Special Distribution of Polybrominated Diphenyl Ethers in Brain Tissues of Free-range Domestic Hens and Ducks from a Village near an Electronic Waste Recycling Site in South China - Zhong-Zhi Yang; Yong-Fang Li; Shan Fu; Xing-Ru Zhao (Bulletin of Environmental Contamination and Toxicology, 2011)

Carbon and nitrogen storage in plant and soil as related to nitrogen and water amendment in a temperate steppe of northern China - Fu-Mei Lü; Xiao-Tao Lü; Wei Liu; Xu Han; Guang-Ming Zhang; De-Liang Kong; Xing-Guo Han (Biology and Fertility of Soils, 2011)

Nash model parameter uncertainty analysis by AM-MCMC based on BFS and probabilistic flood forecasting - Zhenxiang Xing; Xiaofang Rui; Qiang Fu; Yi Ji; Shijiang Zhu (Chinese Geographical Science, 2011)

Silencing USP22 by asymmetric structure of interfering RNA inhibits proliferation and induces cell cycle arrest in bladder cancer cells - Lei Lv; Xing-yuan Xiao; Zhao-hui Gu; Fu-qing Zeng; Lu-qi Huang; Guo-song Jiang (Molecular and Cellular Biochemistry, 2011)

IL-6/STAT3/TFF3 signaling regulates human biliary epithelial cell migration and wound healing in vitro - Gui-xing Jiang; Xiang-yu Zhong; Yun-fu Cui; Wei Liu; Sheng Tai; Zhi-dong Wang; Yu-guang Shi; Shi-yong Zhao; Chun-long Li (Molecular Biology Reports, 2010)

Inhibition protein tyrosine phosphatases by an oxovanadium glutamate complex, Na2[VO(Glu)2(CH3OH)](Glu = glutamate) - Liping Lu; Sulian Wang; Miaoli Zhu; Zhiwei Liu; Maolin Guo; Shu Xing; Xueqi Fu (BioMetals, 2010)

Threatened fishes of the world: Ptychobarbus chungtienensis Tsao 1964 (Cyprinidae) - Xiao-Fu Pan; Jian Yang; Xiao-Yong Chen; Jun-Xing Yang (Environmental Biology of Fishes, 2010)

Endemic Seed Plant Species from Hainan Island: A Checklist - Javier Francisco-Ortega; Fa-Guo Wang; Zhong-Sheng Wang; Fu-Wu Xing; Hong Liu; Han Xu; Wei-Xiang Xu; Yi-Bo Luo; Xi-Qiang Song; Stephan Gale; David E. Boufford; Mike Maunder; et al. (The Botanical Review, 2010)

Seed Plant Endemism on Hainan Island: A Framework for Conservation Actions - Javier Francisco-Ortega; Zhong-Sheng Wang; Fa-Guo Wang; Fu-Wu Xing; Hong Liu; Han Xu; Wei-Xiang Xu; Yi-Bo Luo; Xi-Qiang Song; Stephan Gale; David E. Boufford; Mike Maunder; et al. (The Botanical Review, 2010)

Biodiversity and distribution of endophytic fungi associated with Panax quinquefolium L. cultivated in a forest reserve - Xiaoke Xing; Shunxing Guo; Jianguo Fu (Symbiosis, 2010)

Selection and characterization of a high-temperature tolerant strain of Porphyra haitanensis Chang et Zheng (Bangiales, Rhodophyta) - Xing-Hong Yan; Feng Lv; Chang-Jun Liu; Yue-Fu Zheng (Journal of Applied Phycology, 2010)

A new cytotoxic iridoid from Callicarpa nudiflora - Wen-Li Mei; Zhuang Han; Hai-Bin Cui; You-Xing Zhao; Yuan-Yuan Deng; Hao-Fu Dai (Natural Product Research, 2010)

Investigations on boron levels in drinking water sources in China - Ren-ji Xu; Xiao-ru Xing; Qun-fang Zhou; Gui-bin Jiang; Fu-sheng Wei (Environmental Monitoring and Assessment, 2010)

Meiotic nondisjunction in resynthesized Brassica napus and generation of aneuploids through microspore culture and their characterization - Jing Wen; Xin-hua Zeng; Yuan-yuan Pu; Li-ping Qi; Zai-yun Li; Jin-xing Tu; Chao-zhi Ma; Jin-xiong Shen; Ting-dong Fu (Euphytica, 2010)

Chloroplast transformation of rapeseed (Brassica napus) by particle bombardment of cotyledons - Lin Cheng; He-Ping Li; Bo Qu; Tao Huang; Jin-Xing Tu; Ting-Dong Fu; Yu-Cai Liao (Plant Cell Reports, 2010)

Molecular cloning and characterization of hatching enzyme-like gene in the silkworm, Bombyx mori - Fu-hao Lu; Shun-ming Tang; Xing-jia Shen; Na Wang; Qiao-ling Zhao; Guo-zheng Zhang; Xi-jie Guo (Molecular Biology Reports, 2010)

First-principle conformational analysis of glycine residues in the αβ-tubulin dimer - Gang Yang; Cheng Xing; Cheng-Bu Liu; Yu-Jie Fu; Li-Jun Zhou; Yuan-Gang Zu (Interdisciplinary Sciences: Computational Life Sciences, 2009)

Insulin inhibits myocardial ischemia-induced apoptosis and alleviates chronic adverse changes in post-ischemic cardiac structure and function - Wenjuan Xing; Wenjun Yan; Feng Fu; Yulan Jin; Lele Ji; Wenchong Liu; Li Wang; Anlin Lv; Yunyan Duan; Jun Zhang; Haifeng Zhang; Feng Gao (Apoptosis, 2009)

Quantification of silkworm coactivator of MBF1 mRNA by SYBR Green I real-time RT-PCR reveals tissue- and stage-specific transcription levels - Guang-li Li; Bhaskar Roy; Xing-hua Li; Wan-fu Yue; Xiao-feng Wu; Jian-mei Liu; Chuan-xi Zhang; Yun-gen Miao (Molecular Biology Reports, 2009)

Threatened fishes of the world: Sinocyclocheilus grahami (Regan) 1904 (Cyprinidae) - Xiao-Fu Pan; Xiao-Yong Chen; Jun-Xing Yang (Environmental Biology of Fishes, 2009)

A High Polymorphism Level in Rhinopithecus roxellana - Deng Pan; Hong-Xing Hu; Shi-Jie Meng; Zheng-Ming Men; Yun-Xin Fu; Ya-Ping Zhang (International Journal of Primatology, 2009)

Somatic Embryogenesis and in vitro Flowering in Saposhnikovia divaricata - Qi Qiao; Fu-Wu Xing; Ya-Ping Xiao; Hong-Feng Chen (Journal of Plant Growth Regulation, 2009)

High-level expression of orange fluorescent protein in the silkworm larvae by the Bac-to-Bac system - Jian-mei Liu; Wan Chi Cheong David; Denis Tsz-Ming Ip; Xing-hua Li; Guang-li Li; Xiao-feng Wu; Wan-fu Yue; Chuan-xi Zhang; Yun-gen Miao (Molecular Biology Reports, 2009)

Silkworm powder containing manganese superoxide dismutase regulated the immunity and inhibited the growth of Hepatoma 22 cell in mice - Wan-Fu Yue; Wen Deng; Xing-Hua Li; Bhaskar Roy; Guang-Li Li; Jian-Mei Liu; Xiao-Feng Wu; Hong-Xiang Sun; Min-Li Yao; Wan Chi Cheong David; Yun-Gen Miao (Molecular Biology Reports, 2009)

Manganese superoxide dismutase expressed in silkworm larvae, Bombyx mori L enhances the NK activity and splenocyte proliferation against Sarcoma 180 tumor cells in vivo - Wan-Fu Yue; Min-Li Yao; Jian-Mei Liu; Guang-Li Li; Xing-Hua Li; Xiao-Feng Wu; Wen Deng; Hong-Xiang Sun; Ji-Yong Zhou; Chuan-Xi Zhang; Yun-Gen Miao (Molecular Biology Reports, 2009)

Effects of silkworm larvae powder containing manganese superoxide dismutase on immune activity of mice - Wan-Fu Yue; Jian-Mei Liu; Guang-Li Li; Xing-Hua Li; Xiao-Feng Wu; Jian-Tong Sun; Hong-Xiang Sun; Yun-Gen Miao (Molecular Biology Reports, 2008)

Improving ovary and embryo culture techniques for efficient resynthesis of Brassica napus from reciprocal crosses between yellow-seeded diploids B. rapa and B. oleracea - Jing wen; Jin-xing Tu; Zai-yun Li; Ting-dong Fu; Chao-zhi Ma; Jin-xiong Shen (Euphytica, 2008)

Solid lipid nanoparticles loading adefovir dipivoxil for antiviral therapy - Zhang Xing-guo; Miao Jing; Li Min-wei; Jiang Sai-ping; Hu Fu-qiang; Du Yong-zhong (Journal of Zhejiang University-SCIENCE B, 2008)

Research on the Components of Dust Fall in Hohhot in Comparison with Surface Soil Components in Different Lands of Inner Mongolia Plateau - Chun-xing Hai; Chun-shin Yuan; Guang-tong Liu; Xiao-jia Li; Fu Zhang; Xiu-jiang Zhang (Water, Air, & Soil Pollution, 2008)

Disarming and sequencing of Agrobacterium rhizogenes strain K599 (NCPPB2659) plasmid pRi2659 - S. Luke Mankin; D. Steven Hill; Paula M. Olhoft; Effie Toren; Allan R. Wenck; Lawrence Nea; Liqun Xing; Jeffrey A. Brown; Huihua Fu; Lesley Ireland; Hongmei Jia; Helke Hillebrand; et al. (In Vitro Cellular & Developmental Biology - Plant, 2007)

Localization of vesicular glutamate transporters in the peripheral vestibular system of rat - Yuan Wang; You-Wang Pang; Yu-Lin Dong; Fu-Xing Zhang; Jin-Lian Li; Yun-Qing Li (Neuroscience Bulletin, 2007)

Proteomic analysis of the serum in patients with idiopathic pulmonary arterial hypertension - Min Yu; Xing-xiang Wang; Fu-rong Zhang; Yun-peng Shang; Yu-xi Du; Hong-juan Chen; Jun-zhu Chen (Journal of Zhejiang University-SCIENCE B, 2007)

Generation and characterization of low phytic acid germplasm in rice (Oryza sativa L.) - Qing-Long Liu; Xiu-Hong Xu; Xue-Liang Ren; Hao-Wei Fu; Dian-Xing Wu; Qing-Yao Shu (Theoretical and Applied Genetics, 2007)

Identification of poly-reactive natural IgM antibody that recognizes late apoptotic cells and promotes phagocytosis of the cells - Meng Fu; Ping-shen Fan; Wei Li; Cheng-xin Li; Ying Xing; Jing-gang An; Gang Wang; Xue-li Fan; Tian-wen Gao; Yu-feng Liu; Shigaku Ikeda (Apoptosis, 2007)

Soil microbial biomass as affected by non-flooded plastic mulching cultivation in rice - Yong-Shan Li; Liang-Huan Wu; Xing-Hua Lu; Li-Mei Zhao; Qiao-Lan Fan; Fu-Suo Zhang (Biology and Fertility of Soils, 2006)

Prediction of heterosis using QTLs for yield traits in rapeseed (Brassica napus L.) - Jin-Xiong Shen; Ting-Dong Fu; Guang-Sheng Yang; Jin-Xing Tu; Chao-Zhi Ma (Euphytica, 2006)

Identification and characterization of piggyBac-like elements in the genome of domesticated silkworm, Bombyx mori - Han-Fu Xu; Qing-You Xia; Chun Liu; Ting-Cai Cheng; Ping Zhao; Jun Duan; Xing-Fu Zha; Shi-Ping Liu (Molecular Genetics and Genomics, 2006)

Effects of dietary supplementation with Clostridium butyricum on the growth performance and humoral immune response in Miichthys miiuy - Zeng-fu Song; Tian-xing Wu; Li-sheng Cai; Li-jing Zhang; Xiao-dong Zheng (Journal of Zhejiang University-SCIENCE B, 2006)

Salicylic Acid Enhances Jaceosidin and Syringin Production in Cell Cultures of Saussurea medusa - Zhen-Zhen Yu; Chun-Xiang Fu; Ying-Shan Han; Yong-Xing Li; De-Xiu Zhao (Biotechnology Letters, 2006)

Molecular validation of multiple allele inheritance for dominant genic male sterility gene in Brassica napus L - Lai-Qiang Song; Ting-Dong Fu; Jin-Xing Tu; Cao-Zhi Ma; Guang-Sheng Yang (Theoretical and Applied Genetics, 2006)

Bioaugmentation of Bromoamine Acid Degradation with Sphingomonas xenophaga QYY and DNA Fingerprint Analysis of Augmented Systems - Yuanyuan Qu; Jiti Zhou; Jing Wang; Zhiyong Song; Linlin Xing; Xiang Fu (Biodegradation, 2006)

Specific amino acid restriction inhibits attachment and spreading of human melanoma via modulation of the integrin/focal adhesion kinase pathway and actin cytoskeleton remodeling - Ya-Min Fu; Hui Zhang; Mingjie Ding; Yi-Qi Li; Xing Fu; Zu-Xi Yu; Gary G. Meadows (Clinical & Experimental Metastasis, 2005)

Inheritance of seed colour and identification of RAPD and AFLP markers linked to the seed colour gene in rapeseed (Brassica napus L.) - Liu Zhi-wen; Fu Ting-dong; Tu Jin-xing; Chen Bao-yuan (Theoretical and Applied Genetics, 2005)

Heavy metal accumulation in tissue/organs of a sea cucumber, Holothuria leucospilota - Jun Xing; Fu-Shiang Chia (Hydrobiologia, 1997)